Aqueous Aluminum Ion Batteries, Battery-Capacitor Hybrids, Compositions of Said Batteries and Battery-Capacitors, and Related Methods of Manufacture and Use

JP7641307B2Active Publication Date: 2025-03-06ALSYM ENERGY INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023033419
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-08
Filing Date
2023-03-06
Publication Date
2025-03-06
Estimated Expiration
2040-03-06

AI Technical Summary

Benefits of technology

【0001】酸化マンガンシートのd層間隔)を伴って、少なくとも20重量%(例えば、20重量%~40重量%、例えば40重量%~60重量%、例えば60重量%~80重量%、例えば少なくとも80重量%)の酸化マンガンを含む(例えば、これからなる、これから実質的になる、またはこれを含む)複数のシートを含む、項目28または項目29に記載のカソード。 (項目31) 前記1つまたは複数の構造が、スピネル構造、トンネル構造、サンドイッチ構造、カプセル封入構造、捕捉構造、またはそれらの組合せを含む、項目28から30のいずれか一項に記載のカソード。 (項目32) 前記1つまたは複数の構造が乱層構造を含む、項目28から31のいずれか一項に記載のカソード。 (項目33) 前記1つまたは複数の構造が、リシオフォライト構造(例えば、酸化マンガンおよび水酸化アルミニウムの交互シートを含む)(例えば、ここで、前記1つまたは複数の構造は、10nm~500マイクロメートルの範囲の寸法を有する酸化マンガンシートを含む)、フィロマンガン酸塩構造(例えば、水和されている金属酸化物を含む)、およびテクトマンガン酸塩構造のうちの1つまたは組合せを含み、これらの構造の1つまたは複数が、初期の状態であっても無秩序化されていてもよく、空孔を含んでもよい、項目28から32のいずれか一項に記載のカソード。 (項目34) 前記1つまたは複数の構造が粒子を含み(例えば、粒子であり)、前記カソードの前記粒子の少なくとも80%が、以下の範囲(例えば、±20%またはそれより良好な許容度で): (i) 50nm以上(例えば、前記粒子の少なくとも80%が、40~60nm以上の寸法を有する)、 (ii) 100nm~250nm(例えば、前記粒子の少なくとも80%が、80~120nmと200~300nmの間の寸法を有する)、 (iii) 500nm~5マイクロメートル(例えば、前記粒子の少なくとも80%が、400~600nmと4~6マイクロメートルの間の寸法を有する)、 (iv) 1マイクロメートル~10マイクロメートル、 (v) 5マイクロメートル~30マイクロメートル のうちの(少なくとも)1つの範囲内の寸法(例えば、直径)を有する、 項目28から33のいずれか一項に記載のカソード。 (項目35) 前記1つまたは複数の構造がシートを含み(例えば、シート子であり)、前記カソードの前記シートの少なくとも80%が、以下の範囲(例えば、±20%またはそれより良好な許容度で): (i) 50nm以上(例えば、前記シートの少なくとも80%が、40~60nm以上の寸法を有する)、 (ii) 100nm~250nm(例えば、前記シートの少なくとも80%が、80~120nmと200~300nmの間の寸法を有する)、 (iii) 500nm~5マイクロメートル(例えば、前記シートの少なくとも80%が、400~600nmと4~6マイクロメートルの間の寸法を有する)、 (iv) 1マイクロメートル~10マイクロメートル、 (v) 5マイクロメートル~30マイクロメートル のうちの(少なくとも)1つの範囲内の寸法(例えば、厚さ)を有する、 項目28から34のいずれか一項に記載のカソード。 (項目36) 前記酸化マンガンシート間に蓄えられた1種または複数種の非アルミニウムゲストイオンを含む、項目29から35のいずれか一項に記載のカソード。 (項目37) 酸化マンガン結晶格子の部位(例えば、格子間部位)および/またはその空孔に配設された1種または複数種の非アルミニウムゲストイオンを含む、項目29から36のいずれか一項に記載のカソード。 (項目38) 前記ゲストイオンが、プロトン、ナトリウム、リチウム、カリウム、亜鉛、ビスマス、銅、鉛、コバルト、ニッケル、カルシウム、カリウム、マグネシウム、水素、ヒドロニウム、水酸化物、酸化物-水酸化物、硫酸、硫化物、窒化物、硝酸、リン化物、リン酸、酢酸、ポリオキソメタレート(POM)および柱状体形成剤(例えば、脂肪族および/または芳香族化合物)からなる群から選択される1つまたは複数のメンバーを含む、項目36または項目37に記載のカソード。 (項目39) 酸化マンガンシート間に蓄えられた1種または複数種のアルミニウムゲストイオンを含む、項目28から38のいずれか一項に記載のカソード。 (項目40) 前記酸化マンガンシート間に蓄えられた1種または複数種の非アルミニウムゲスト分子を含む、項目29から39のいずれか一項に記載のカソード。 (項目41) 酸化マンガン結晶格子の部位(例えば、格子間部位)および/または空孔に配設された1種または複数種の非アルミニウムゲストイオンを含む、項目29から40のいずれか一項に記載のカソード。 (項目42) 前記ゲスト分子が、酸化物、水酸化物、酸化物-水酸化物、スルフィド、硫酸塩、窒化物、硝酸塩、塩化物、塩素酸塩、リン酸塩およびリン化物からなる群から選択される1つまたは複数のメンバーを含む、項目40または項目41に記載のカソード。 (項目43) 前記ゲスト分子が1種または複数種のリン酸塩を含む、項目40から42のいずれか一項に記載のカソード。 (項目44) 前記1種または複数種のリン酸塩が、ナトリウムのリン酸塩、リチウムのリン酸塩、カリウムのリン酸塩、カルシウムのリン酸塩、マグネシウムのリン酸塩およびマンガンのリン酸塩からなる群から選択されるメンバーである、項目43に記載のカソード。 (項目45) 酸化マンガンシート間に蓄えられたまたは酸化マンガン結晶格子の部位(例えば、格子間部位)および/もしくは空孔に配設されたアルミニウムのリン酸塩を含む、項目29から44のいずれか一項に記載のカソード。 (項目46) 酸化マンガンシート間に蓄えられた1種または複数種の柱状体形成剤を含む、項目29から45のいずれか一項に記載のカソード。 (項目47) 前記1種または複数種の柱状体形成剤が、ポリオキソメタレート(POM)、両親媒性分子、極性有機分子および非極性有機分子からなる群から選択される1つまたは複数のメンバーを含む、項目46に記載のカソード。 (項目48) 前記1つまたは複数の構造がそれぞれ、アルミニウム受容性ポリマーを含む、項目28から47のいずれか一項に記載のカソード。 (項目49) 前記アルミニウム受容性ポリマーが、アリザリン、アルギネート、アミジネート、キノン、キノロン、ヒドロキシキノン、クラウンエーテルおよびヒドロキシキノリンからなる群から選択されるメンバーを含む、項目48に記載のカソード。 (項目50) 前記アルミニウム受容性ポリマーが、リチウム、ナトリウム、鉛、クロム、銅、ビスマス、コバルト、亜鉛、カリウム、カルシウム、マグネシウム、マンガン、鉄、コバルト、チタン、スズ、バナジウムおよびタングステンからなる群から選択される1つまたは複数のメンバーとの錯体として存在する[例えば、ここで、前記錯体は、充電/放電中の電池において、電解質および/またはアルミニウム源電極(例えば、アノード)からのアルミニウムイオンとのイオン交換プロセスによる電気化学反応に関与する]、項目48または項目49に記載のカソード。 (項目51) 前記1つまたは複数の構造が、粒子(例えば、酸化マンガンを含む)(例えば、前記粒子は、ナノ粒子、マイクロ粒子またはナノ粒子とマイクロ粒子との組合せである)(例えば、前記粒子は、10nm~500マイクロメートルの範囲の直径を有する球体である)を含む、項目28から50のいずれか一項に記載のカソード。 (項目52) 前記電流コレクタから突き出た複数の伝導性柱状体を備える項目51に記載のカソードであって、前記粒子が前記複数の伝導性柱状体上に配設されている、カソード。 (項目53) 前記1つまたは複数の構造が、薄層フィルム(例えば、パターン形成されている薄層フィルム)を含む、項目28から50のいずれか一項に記載のカソード。 (項目54) 前記電流コレクタから突き出た複数の伝導性柱状体を備える項目53に記載のカソードであって、前記薄層フィルムが、前記複数の伝導性柱状体上に配設されている(例えば、および前記薄層フィルムは、パターン形成されて、前記電流コレクタ上の前記柱状体の分布に対応する)、カソード。 (項目55) 前記電流コレクタが、多孔質である(例えば、メッシュ、発泡体、複数の相互接続した繊維、複数の管およびシート、複数のナノチューブ、またはグラフェン様構造である)、項目28から50のいずれか一項に記載のカソード。 (項目56) 前記1つまたは複数の構造が、前記電流コレクタの細孔内または細孔表面に配設(例えば、コーティング)されている、項目55に記載のカソード。 (項目57) 前記1つまたは複数の構造が、1つまたは複数の多孔質炭素構造上にコーティングされている、項目28から54のいずれか一項に記載のカソード。 (項目58) 前記1つまたは複数の多孔質炭素構造が、炭素繊維、ナノ繊維、カーボンナノチューブ(CNT)、フラーレン、グラフェン、部分還元型酸化グラフェン、エアロゲル、キセロゲル、および相互貫入性多相材料からなる群から選択される1つまたは複数のメンバーを含む、項目57に記載のカソード。 (項目59) 前記電流コレクタに接触して前記1つまたは複数の構造を物理的に維持する(例えば、接着する)バインダー(例えば、ポリマーバインダー)をさらに含む、項目28から58のいずれか一項に記載のカソード。 (項目60) 前記バインダーが、カルボキシメチルセルロース、スチレンブタジエンゴム、ポリビニルアルコール、アルギネート、ポリプロピレン、ポリテトラフルオロエチレン、二フッ化ポリビニリデン、ポリアニリン、エポキシ、ゴム、ポリアクリル酸およびポリビニルプロピレンからなる群から選択される、項目59に記載のカソード。 (項目61) 前記バインダーが、アルギネート、PVDF、PTFE、ポリアニリン、エポキシ、カルボキシメチルセルロース、ゴム、スチレンブタジエンゴム、ポリアクリル酸、ポリビニルアルコールおよびポリビニルプロピレンからなる群から選択される、項目59に記載のカソード。 (項目62) 前記バインダーが、1つまたは複数の種の多価イオンにより事前処理されている、項目59から61のいずれか一項に記載のカソード。 (項目63) 前記1つまたは複数の種の多価イオンが、マンガン、マグネシウム、カルシウム、亜鉛、バリウムおよびアルミニウムのうちの1つまたは複数のイオンを含む、項目62に記載のカソード。 (項目64) 前記バインダーが、1つまたは複数の種の一価イオンにより事前処理されている、項目59から63のいずれか一項に記載のカソード。 (項目65) 前記1つまたは複数の種の一価イオンが、リチウム、ナトリウムおよびカリウムのうちの1つまたは複数のイオンを含む、項目64に記載のカソード。 (項目66) 前記バインダーが、ナトリウム、カリウム、マグネシウム、マンガン、アルミニウム、カルシウム、バリウム、ストロンチウムおよび亜鉛からなる群から選択される1つまたは複数のメンバーのイオンを含む、項目59から65のいずれか一項に記載のカソード。 (項目67) 前記バインダーが、水、n-メチルピロリドン、ケトン、グリコール、ジメチルスルホキシド(DMSO)およびエステルのうちの1つまたは複数、ならびに必要に応じて、水、n-メチルピロリドン、ケトン、グリコール、DMSOおよびエステルからなる群から選択される共溶媒を含む溶液から堆積させたものである、項目59から66のいずれか一項に記載のカソード。 (項目68) 前記カソードがバインダー不含である(例えば、ここで、前記1つまたは複数の構造が、化学蒸着、物理蒸着、原子層堆積、スピン-コーティングおよび電気化学堆積のうちの1つまたは複数を使用して、前記電流コレクタ上に形成されている)、項目28から54のいずれか一項に記載のカソード。 (項目69) 前記電流コレクタおよび前記1つまたは複数の構造と電気的に接触している伝導性添加剤(例えば、炭素含有添加剤)をさらに含む、項目28から68のいずれか一項に記載のカソード。 (項目70) 前記電流コレクタが、ステンレス鋼、銅、炭素、銀、金、白金、スズ、バナジウム、亜鉛、酸化スズ、インジウム、酸化インジウムスズ(ITO)、アルミニウム、ニッケル、タングステン、クロムおよびチタンからなる群から選択される1つまたは複数のメンバーを含む、項目28から69のいずれか一項に記載のカソード。 (項目71) 前記電流コレクタが、接着促進剤、伝導性促進剤または接着促進剤と伝導性促進剤の両方のコーティングを含む、項目28から70のいずれか一項に記載のカソード。 (項目72) 前記電流コレクタが、炭素、金属(例えば、スズ、亜鉛、アルミニウム、クロム、銅、ニッケル、鉄、ジルコニウム、銀、金、白金)、金属酸化物(例えば、酸化インジウムスズ、酸化スズ、酸化チタン、酸化バナジウム、酸化ジルコニウム)またはポリマー(例えば、PEDOT、PAN、パリレン)のうちの1つまたは複数のコーティングを含み、前記コーティングが、接着促進剤、電子伝導性促進剤およびイオン伝導性阻害剤のうちの1つまたは複数として働く、項目28から71のいずれか一項に記載のカソード。 (項目73) イオン電池(例えば、アルミニウムイオン電池または水系アルミニウムイオン電池、例えば、項目1から23のいずれか一項に記載の電池)のためのカソードであって、 前記カソードは、ある量の溶液を電流コレクタ上に堆積させるステップを含む方法によって作製され、ここで、前記溶液は、 酸化マンガン、層化アルミノシリケートおよびアルミニウム受容性ポリマーからなる群から選択される1つまたは複数のメンバー、ならびに 1つまたは複数の溶媒(例えば、水、N-メチルピロリドンおよびエタノールからなる群から選択される) を含む、カソード。 (項目74) 前記1つまたは複数のメンバーが、 酸素源(例えば、および必要に応じて酸化剤化学触媒)の存在下、1種または複数種の酸化マンガン前駆体を塩基と反応させるステップ、および 必要に応じて、前記反応ステップ後に酸化マンガンを水熱処理するステップ を含む方法によって作製された酸化マンガンを含み、 前記1種または複数種の前駆体がそれぞれ、マンガン塩、リチウム塩、ナトリウム塩、マグネシウム塩、ニッケル、亜鉛、アルミニウム、無機酸および過マンガン酸塩からなる群から選択され、 ここで、前記マンガン塩が、硫酸塩、(i)硝酸塩、(ii)塩化物、(iii)酢酸塩、(iv)リン酸塩、(v)過塩素酸塩、(vi)フッ化物および(vii)臭化物のうちの1つまたは複数を含み、 前記過マンガン酸塩が、(i)ナトリウムおよび(ii)カリウムのうちの1つまたは複数を含む、 項目73に記載のカソード。 (項目75) 前記塩基が、水酸化リチウム、水酸化ナトリウム、水酸化カリウム、水酸化カルシウムを含む、項目74に記載のカソード。 (項目76) 前記酸素源が、溶存酸素ガスまたは過酸化物(例えば、過酸化水素)である、項目74または項目75に記載のカソード。 (項目77) 前記溶液が、バインダー(例えば、ポリマーバインダー、例えば、1種または複数種のアルミニウム塩を含む電解質溶液により浸透可能なポリマーバインダー)および伝導性添加剤(例えば、炭素含有添加剤)のうちの1つまたは複数をさらに含む、項目73から76のいずれか一項に記載のカソード。 (項目78) 前記堆積させるステップが、ドクターブレード法、スピンコーティング法、コンマコーティング法またはスロット-ダイコーティング法を含む、項目73から77のいずれか一項に記載のカソード。 (項目79) 前記方法が、前記堆積させた溶液および前記電流コレクタをカレンダー加工するステップをさらに含む、項目73から78のいずれか一項に記載のカソード。 (項目80) 前記カソードが、1つまたは複数の相の酸化マンガンを含み、前記1つまたは複数の相が、アルファ相、ベータ相、ラムダ相、ラムスデライト相、アモルファス相、ガンマ相、デルタ相およびイプシロン相からなる群から選択される、項目28から79のいずれか一項に記載のカソード。 (項目81) 前記1つまたは複数の相が、2つまたはそれより多い相(例えば、3つまたはそれより多い相)である、項目80に記載のカソード。 (項目82) 前記2つまたはそれより多い相のうちの主要な1つが、前記カソードの少なくとも40重量%であり、前記2つまたはそれより多い相の残りすべてが、前記カソードの50重量%以下である、項目81に記載のカソード。 (項目83) 前記酸化マンガンが、前記カソードの充電および放電(例えば、イオン挿入および除去)の間に、少なくとも1つの相変化を経るよう配設されている、項目80から82のいずれか一項に記載のカソード。 (項目84) 前記カソードが、層化構造(例えば、フィロマンガン酸塩)、トンネル構造(例えば、テクトマンガン酸塩)、スピネル構造、ラムスデライト構造またはアモルファス構造を有する酸化マンガンを含む、項目28から83のいずれか一項に記載のカソード。 (項目85) 前記カソードが酸化マンガンを含み、前記酸化マンガン中のマンガンが、Mn(II)、Mn(II-x)、Mn(III)、Mn(III-x)、Mn(IV)、Mn(IV-x)、Mn(V)、Mn(V-x)、Mn(VI)、Mn(VI-x)、Mn(VII)およびMn(VII-x)(xは、0~1の間である)からなる群から選択される1つまたは複数の酸化状態を有する、項目28から84のいずれか一項に記載のカソード。 (項目86) 前記1つまたは複数の構造が酸化マンガンを含み、前記酸化マンガンは、大部分(例えば、少なくとも70重量%、少なくとも80重量%、または少なくとも90重量%)がデルタ相の酸化マンガンである、項目28から85のいずれか一項に記載のカソード。 (項目87) イオン電池(例えば、アルミニウムイオン電池または水系アルミニウムイオン電池、例えば、項目1から27のいずれか一項に記載の電池)のためのカソードであって、 電流コレクタ上に酸化マンガンおよび1種または複数種の犠牲材料を同時に堆積させるステップ、および 前記1種または複数種の犠牲材料を除去するステップ を含む方法によって作製される、カソード。 (項目88) 前記1種または複数種の犠牲材料が、アリザリン、アミジネート、キノン、アルギネート、ゼオライト、キノロン、ヒドロキシキノン、ヒドロキシキノリン、ケイ素、銅、コバルト、クロム、ニッケル、鉄、(例えば、ケイ素、銅、コバルト、クロム、ニッケルまたは鉄の)酸化物、水酸化物、硫酸塩、硝酸塩およびリン酸塩からなる群から選択される1つまたは複数のメンバーを含む、項目87に記載のカソード。 (項目89) 前記同時に堆積させるステップが、同時熱的蒸発、同時スパッタリング、共押出または同時コーティング(例えば、スピン-コーティング法、ドクターブレード法またはスロット-ダイコーティング法)を含む、項目87または項目88に記載のカソード。 (項目90) イオン電池(例えば、アルミニウムイオン電池または水系アルミニウムイオン電池、例えば、項目1から27のいずれか一項に記載の電池)のためのカソードを製造するための方法であって、 ある量の溶液を電流コレクタ上に堆積させるステップを含み、ここで、前記溶液は、 酸化マンガン、層化アルミノシリケートおよびアルミニウム受容性ポリマーからなる群から選択される1つまたは複数のメンバー、ならびに 1つまたは複数の溶媒(例えば、水、N-メチルピロリドンおよびエタノールからなる群から選択される) を含む、方法。 (項目91) 酸素源(例えば、および必要に応じて酸化剤化学触媒)の存在下、1種または複数種の酸化マンガン前駆体を塩基と反応させるステップ、および 必要に応じて、前記反応ステップ後に酸化マンガンを水熱処理するステップ によって酸化マンガンを製造するステップをさらに含み、 前記1種または複数種の前駆体がそれぞれ、マンガン塩、リチウム塩、ナトリウム塩、マグネシウム塩、ニッケル、亜鉛、アルミニウム、無機酸および過マンガン酸塩からなる群から選択され、 ここで、前記マンガン塩が、硫酸塩、(i)硝酸塩、(ii)塩化物、(iii)酢酸塩、(iv)リン酸塩、(v)過塩素酸塩、(vi)フッ化物および(vii)臭化物のうちの1つまたは複数を含み、 前記過マンガン酸塩が、(i)ナトリウムおよび(ii)カリウムのうちの1つまたは複数を含む、 項目90に記載の方法。 (項目92) 前記塩基が、水酸化リチウム、水酸化ナトリウム、水酸化カリウム、および水酸化カルシウムの1つまたは複数を含む、項目91に記載の方法。 (項目93) 前記酸素源が、溶存酸素ガスまたは過酸化物(例えば、過酸化水素)である、項目91または項目92に記載の方法。 (項目94) 前記溶液が、バインダー(例えば、ポリマーバインダー、例えば、1種または複数種のアルミニウム塩を含む電解質溶液により浸透可能なポリマーバインダー)および伝導性添加剤(例えば、炭素含有添加剤)のうちの1つまたは複数をさらに含む、項目90から93のいずれか一項に記載の方法。 (項目95) 前記堆積させるステップが、ドクターブレード法、スピンコーティング法、コンマコーティング法またはスロット-ダイコーティング法を含む、項目90から95のいずれか一項に記載の方法。 (項目96) 前記堆積させた溶液および前記電流コレクタをカレンダー加工するステップをさらに含む、項目90から95のいずれか一項に記載の方法。 (項目97) 前記溶液が、水、n-メチルピロリドン、ケトン、グリコール、ジメチルスルホキシド(DMSO)およびエステルからなる群から選択される1つまたは複数のメンバー、ならびに必要に応じて、水、n-メチルピロリドン、ケトン、グリコール、DMSOおよびエステルからなる群から選択される共溶媒を含む、項目90から96のいずれか一項に記載の方法。 (項目98) 前記溶液が、(i)アルギネート、PVDF、PTFE、ポリアニリン、エポキシ、カルボキシメチルセルロース、ゴム、スチレンブタジエンゴム、ポリアクリル酸、ポリビニルアルコールおよびポリビニルプロピレンからなる群から選択されるバインダー、ならびに(ii)ナトリウム、リチウム、カリウム、マグネシウム、マンガン、アルミニウム、カルシウム、バリウム、ストロンチウムおよび亜鉛からなる群から選択されるイオン種を含む、項目90から97のいずれか一項に記載の方法。 (項目99) イオン電池(例えば、アルミニウムイオン電池または水系アルミニウムイオン電池、例えば、項目1から27のいずれか一項に記載の電池)のためのカソードを製造するための方法であって、 電流コレクタ上に酸化マンガンおよび1種または複数種の犠牲材料を同時に堆積させるステップ、および 前記1種または複数種の犠牲材料を除去するステップ を含む、方法。 (項目100) 前記1種または複数種の犠牲材料が、アリザリン、アミジネート、キノン、アルギネート、ゼオライト、キノロン、ヒドロキシキノン、ヒドロキシキノリン、ケイ素、銅、コバルト、クロム、ニッケル、鉄、(例えば、ケイ素、銅、コバルト、クロム、ニッケルまたは鉄の)酸化物、水酸化物、硫酸塩、硝酸塩およびリン酸塩からなる群から選択される1つまたは複数のメンバーを含む、項目99に記載の方法。 (項目101) 前記同時に堆積させるステップが、同時熱的蒸発、同時スパッタリング、共押出または同時コーティング(例えば、スピン-コーティング法、ドクターブレード法またはスロット-ダイコーティング法)からなる群から選択される1つまたは複数のメンバーを含む、項目99または項目100に記載の方法。 (項目102) 1つまたは複数の構造(例えば、1つまたは複数のホイル、薄層フィルムまたは粒子)を備える、イオン電池(例えば、アルミニウムイオン電池または水系アルミニウムイオン電池、例えば、項目1から27のいずれか一項に記載の電池)のためのアノードであって、 前記1つまたは複数の構造がそれぞれ、アルミニウム、アルミニウム合金およびアルミニウムコンポジットからなる群から選択される1つまたは複数のアルミニウム含有メンバーを含み、前記アノードが、0.001重量%~100重量%のアルミニウムである(例えば、70重量%~100重量%のアルミニウム、例えば少なくとも95重量%のアルミニウム)(例えば、ここで、前記アノードは、少なくとも95重量%のアルミニウムおよび最大で5重量%の非アルミニウム種を含み、例えば、前記非アルミニウム種は、前記アノードに意図的に組み込まれた1種または複数種の合金化金属および/または酸化物を含む)(例えば、ここで、前記アルミニウムの純度は、少なくとも99.9原子%、例えば少なくとも99.99原子%、例えば99.99原子%~99.99999原子%であり、例えばここで、不純物は、0.01原子%~0.00001原子%の範囲で存在し、例えば、前記不純物は、鉄および/またはナトリウムおよび/またはマグネシウムおよび/またはシリカを含み、例えば、金属ホイル中に一般に見出される不純物)、アノード。 (項目103) 前記アノードが、アルミニウム、酸素、水素、窒素、リチウム マンガンおよび炭素のうちの1つまたは複数を含む(例えば、からなる)表面層を含む、項目102に記載のアノード。 (項目104) 前記1つまたは複数の構造のそれぞれが、ナトリウム、リチウム、カルシウム、カリウム、マグネシウム、ジルコニウム、鉛、ビスマス、チタン、バナジウム、スズ、銅、銀、金、白金、水銀、スカンジウム、硫黄、ケイ素、鉄、ケイ素、ニッケル、マンガン、クロム、セリウム、ゲルマニウム、ガリウム、タリウム、ハフニウム、インジウム、ロジウム、ルテニウム、モリブデン、パラジウム、ストロンチウム、イットリウム、バリウム、カドミウム、イリジウム、タンタル、コバルト、テルル、アンチモン、ヒ素、タングステンおよびセレンからなる群から選択される1つまたは複数の非アルミニウムメンバーを含むアルミニウム合金または混合物を含む、項目102または103に記載のアノード。 (項目105) 前記1つまたは複数の構造を含むフィルムを含み、前記1つまたは複数の構造の各々が粒子である(例えば、ここで、前記粒子は、10nm~100マイクロメートルの範囲の直径を有する)(例えば、ここで、前記フィルムは、10nm~1mmの範囲の厚さを有する)、項目102から104のいずれか一項に記載のアノード。 (項目106) 前記アノードの前記粒子の少なくとも80%が、以下の範囲(例えば、±20%またはそれより良好な許容度で): (i) 50nm以上(例えば、前記粒子の少なくとも80%が、40~60nm以上の寸法を有する)、 (ii) 100nm~500nm(例えば、前記粒子の少なくとも80%が、80~120nmと400~600nmの間の寸法を有する)、 (iii) 250nm~1マイクロメートル(例えば、前記粒子の少なくとも80%が、200~300nmと0.8~1.2マイクロメートルの間の寸法を有する)、 (iv) 500nm~5マイクロメートル(例えば、前記粒子の少なくとも80%が、400~600nmと4~6マイクロメートルの間の寸法を有する)、 (v) 1マイクロメートル~10マイクロメートル、 (vi) 5マイクロメートル~25マイクロメートル (vii) 10マイクロメートル~50マイクロメートル、および (viii) 50マイクロメートル~100マイクロメートル のうちの(少なくとも)1つの範囲内の寸法(例えば、直径)を有する、 項目105に記載のアノード。 (項目107) 前記フィルムが、前記複数の粒子と物理的に接触したポリマーバインダーをさらに含み、前記ポリマーバインダーが、カルボキシメチルセルロース、スチレンブタジエンゴム、ポリビニルアルコール、ポリプロピレンおよびポリテトラフルオロエチレンからなる群から選択される、項目105または106に記載のアノード。 (項目108) 前記フィルムが、1つまたは複数の伝導性炭素添加剤をさらに含む、項目105から107のいずれか一項に記載のアノード。 (項目109) 前記1つまたは複数の構造が、1nm~1mmの範囲の厚さを有する薄層フィルムを含む、項目102から108のいずれか一項に記載のアノード。 (項目110) 薄層フィルムが、以下の範囲(例えば、±20%またはそれより良好な許容度で): (i) 50nm以上(例えば、40~60nm以上の厚さ)、 (ii) 100nm~500nm(例えば、80~120nmと400~600nmの間の厚さ)、 (iii) 250nm~1マイクロメートル(例えば、200~300nmと0.8~1.2マイクロメートルの間の厚さ)、 (iv) 500nm~5マイクロメートル(例えば、400~600nmと4~6マイクロメートルの間の厚さ)、 (v) 1マイクロメートル~10マイクロメートル、 (vi) 5マイクロメートル~25マイクロメートル (vii) 10マイクロメートル~50マイクロメートル、および (viii) 50マイクロメートル~100マイクロメートル のうちの(少なくとも)1つの範囲内の厚さを有する、 項目109に記載のアノード。 (項目111) 前記薄層フィルムが電流コレクタ(例えば、伝導性基材)上にコーティングされている(例えば、ここで、前記伝導性基材が、炭素、鋼、ニッケル、鉄、亜鉛、アルミニウム、チタン、タングステン、銅、銀、スズ、インジウムおよびクロムからなる群から選択される1つまたは複数のメンバーを含む)、項目109または110に記載のアノード。 (項目112) 前記薄層フィルムが、炭素、金属(例えば、スズ、亜鉛、アルミニウム、クロム、銅、ニッケル、鉄、ジルコニウム、銀、金、白金)、金属酸化物(例えば、酸化インジウムスズ、酸化スズ、酸化チタン、酸化バナジウム、酸化ジルコニウム)またはポリマー(例えば、PEDOT、PAN、パリレン)のうちの1つまたは複数のコーティングをさらに含む電流コレクタ(例えば、伝導性基材)上にコーティングされており、前記コーティングが、接着促進剤、電子伝導性促進剤およびイオン伝導性阻害剤のうちの1つまたは複数として働く、項目109または110に記載のアノード。 (項目113) 前記厚さが、前記アノードおよびカソードを備える電池における前記カソードの容量に見合う容量を有する前記アノードを提供するのに十分である、項目109から111のいずれか一項に記載のアノード。 (項目114) 前記1つまたは複数の構造が、研磨された表面(例えば、機械的または電気化学的に研磨されている)を有するホイルを含む、項目102から104のいずれか一項に記載のアノード。 (項目115) 前記1つまたは複数の構造が、多孔質構造を含む(例えば、前記多孔質構造は、円形断面または矩形断面を有する細孔を含む)、項目102から114のいずれか一項に記載のアノード。 (項目116) 前記1つまたは複数の構造が、電流コレクタ(例えば、伝導性基材)から突き出た複数の柱状体を含む(例えば、ここで、前記伝導性基材が、炭素、ステンレス鋼、ニッケル、チタン、タングステン、銅およびクロムからなる群から選択される1つまたは複数のメンバーを含む)、項目102から114のいずれか一項に記載のアノード。 (項目117) 非天然の遷移的酸化アルミニウム層(例えば、0.1nm~10マイクロメートルの範囲の厚さを有する)(例えば、原子層堆積、化学蒸着、熱反応、水熱反応、エッチング、電気化学反応、酸素プラズマ反応または水酸化物処理により形成される)をさらに含む、項目102から116のいずれか一項に記載のアノード。 (項目118) 前記非天然の遷移的酸化アルミニウム層が、以下の範囲(例えば、±20%またはそれより良好な許容度で): (i) 1nm以上、 (ii) 1nm~10nm、 (iii) 5nm~20nm、 (iv) 20nm~50nm、 (v) 50nm~250nm、 (vi) 100nm~500nm、 (vii) 500nm~1マイクロメートル、および (viii) 1マイクロメートル~10マイクロメートル のうちの(少なくとも)1つの範囲内の厚さを有する、項目117に記載のアノード。 (項目119) 前記非天然の遷移的酸化アルミニウム層が、前記1つまたは複数の構造(例えば、薄層フィルムまたはホイルを含む)上に配設されている、項目118に記載のアノード。 (項目120) 前記1つまたは複数の構造上に配設されている酸化物フィルムをさらに備える(例えば、0.1nm~100マイクロメートルの範囲の厚さを有する)[例えば、ここで、前記酸化物フィルムが、パターン形成されている(例えば、前記酸化物フィルムが、前記電流コレクタ上の柱状体の分布に対応するようパターン形成されている)]、項目102から119のいずれか一項に記載のアノード。 (項目121) 前記酸化物フィルムが、以下の範囲(例えば、±20%またはそれより良好な許容度で): (i) 1nm以上、 (ii) 1nm~10nm、 (iii) 5nm~20nm、 (iv) 20nm~50nm、 (v) 50nm~250nm、 (vi) 100nm~500nm、 (vii) 500nm~1マイクロメートル、および (viii) 1マイクロメートル~10マイクロメートル のうちの(少なくとも)1つの範囲内の厚さを有する、項目120に記載のアノード。 (項目122) 前記酸化物フィルムが薄層フィルムである、項目120または121に記載のアノード。 (項目123) 前記酸化物フィルムが、複数の酸化物粒子を含むコーティングである、項目120または121に記載のアノード。 (項目124) 前記複数の酸化物粒子が、ナノ粒子、マイクロ粒子、またはナノ粒子とマイクロ粒子の両方を含む、項目123に記載のアノード。 (項目125) 前記酸化物粒子の少なくとも80%が、以下の範囲(例えば、±20%またはそれより良好な許容度で): (i) 1ナノメートル~500マイクロメートル、および (ii) 10ナノメートル~20マイクロメートル のうちの(少なくとも)1つの範囲内の寸法(例えば、直径)を有する、項目124に記載のアノード。 (項目126) 前記酸化物フィルムが、カルボキシメチルセルロース、スチレンブタジエン、ポリビニルアルコール、ポリプロピレンおよびポリテトラフルオロエチレンからなる群から選択されるポリマーバインダーをさらに含む、項目123から125のいずれか一項に記載のアノード。 (項目127) 前記酸化物フィルムが、1つまたは複数の伝導性炭素添加剤をさらに含む、項目123から126のいずれか一項に記載のアノード。 (項目128) 複数の酸化物フィルムを含み、前記複数の酸化物フィルムの各々が異なる酸化物を含む、項目102から127のいずれか一項に記載のアノード。 (項目129) 同じタイプまたは異なるタイプの複数の酸化物層を、必要に応じて前記酸化物層の間の1つまたは複数のアルミニウム層と共に、含む(例えば、アノードは、以下の順序の層:Al/Al2O3/ZrO2/Al2O3という少なくとも1つの例を含む)(例えば、アノードは、以下の順序の層:Al/Al2O3/Al/Al2O3という少なくとも1つの例を含む)、項目102から128のいずれか一項に記載のアノード。 (項目130) 前記1つまたは複数の構造が、薄層フィルムまたはホイルを含み、前記複数の酸化物フィルムの各々が、前記1つまたは複数の構造に接触している[例えば、前記薄層フィルムまたはホイル上に、列(例えば、規則正しい列)になって配列されている]、項目128または129に記載のアノード。 (項目131) 前記複数の酸化物フィルムが、前記1つまたは複数の構造上に層として配設されている、項目128または129に記載のアノード。 (項目132) 前記1つまたは複数の構造が、複数の薄層フィルムまたはホイルを含み、前記複数の薄層フィルムまたはホイルの1つまたは複数が、2つまたはそれより多くの前記酸化物フィルムの間に配設されている、項目128または129に記載のアノード。 (項目133) 前記1つまたは複数の構造から突き出た複数の酸化物柱状体を含む、項目102から116のいずれか一項に記載のアノード。 (項目134) 前記複数の酸化物柱状体が多孔質である、項目133に記載のアノード。 (項目135) 前記複数の酸化物柱状体が、繊維、ナノチューブおよびナノカラムのうちの1つまたは複数を含む、項目133または項目134に記載のアノード。 (項目136) 前記複数の酸化物柱状体が、物理蒸着、化学蒸着、原子層堆積、水熱反応、電気化学反応、電気化学堆積または熱反応によって形成される、項目133から135のいずれか一項に記載のアノード。 (項目137) 前記複数の酸化物柱状体が、フィルムを堆積させ前記フィルムをエッチングすることによって形成され、前記エッチングが、プラズマエッチング、湿式化学エッチング、反応性イオンエッチングまたは緩衝酸化物エッチングを含む、項目133から136のいずれか一項に記載のアノード。 (項目138) 前記1つまたは複数の構造上に配設されている非酸化物フィルム(例えば、前記1つまたは複数の構造上に直接、または前記非酸化物フィルムと前記1つまたは複数の構造との間に配設されている1つまたは複数の酸化物フィルムを伴って)をさらに含む、項目102から137のいずれか一項に記載のアノード。 (項目139) 前記非酸化物フィルムが、元素のスルフィド、前記元素の硫酸塩、前記元素の窒化物、前記元素の硝酸塩、前記元素のリン化物、前記元素のリン酸塩および前記元素のハロゲン化物からなる群から選択される1つまたは複数の非酸化物メンバーを含み、 前記元素が、ジルコニウム、タングステン、インジウム、クロム、コバルト、マグネシウム、鉄、ニッケル、バナジウム、チタン、亜鉛、マンガン、鉄、スズ、ケイ素、硫黄、銅、ハフニウムおよびコバルトからなる群から選択される、項目138に記載アノード。 (項目140) 前記非酸化物フィルムが薄層フィルムである、項目138または項目139に記載のアノード。 (項目141) 前記非酸化物フィルムが、(例えば、前記1つまたは複数の非酸化物メンバーを含む)複数の非酸化物粒子を含むコーティングである、項目138または項目139に記載のアノード。 (項目142) 前記複数の非酸化物粒子が、ナノ粒子、マイクロ粒子、またはナノ粒子とマイクロ粒子の両方を含む、項目141に記載のアノード。 (項目143) 前記1つまたは複数の構造上に配設されているポリマー層を含む(例えば、ここで、前記ポリマー層による前記1つまたは複数の構造の表面被覆率が1%~100%であり、例えば、前記1つまたは複数の構造の表面の少なくとも50%が、前記ポリマー層により被覆されている)(例えば、ここで、前記ポリマー層は、0.1nm~100マイクロメートルの範囲の厚さを有する)[例えば、ここで、前記ポリマー層は、以下の範囲(例えば、±20%またはそれより良好な許容度で):(i)1nm以上;(ii)1nm~10nm;(iii)5nm~20nm;(iv)20nm~50nm;(v)50nm~250nm;(vi)100nm~500nm;(vii)500nm~1マイクロメートル;および(viii)1マイクロメートル~10マイクロメートルのうちの(少なくとも)1つの範囲内の厚さを有する]、項目102から142のいずれか一項に記載のアノード。 (項目144) 前記ポリマー層が、パリレン、ポリビニルアルコール、アルギン酸、PTFE、ポリエチレンオキシド、セルロース(およびその誘導体)、ポリスルホン(PES)、1つまたは複数のアクリレートのポリマー、アルギネート(例えば、ナトリウム、カルシウム、アルミニウム、カリウム、マグネシウムまたは亜鉛を含む)、キノン、ヒドロキノン、キノロン、ヒドロキシキノリンおよびアリザリン(例えば、アリザリンレッドSを含む)からなる群から選択される1つまたは複数のメンバーを含む、項目143に記載のアノード。 (項目145) イオン電池(例えば、アルミニウムイオン電池または水系アルミニウムイオン電池、例えば、項目1から27のいずれか一項に記載の電池)のための電極(例えば、カソードまたはアノード、例えば、項目28から89のいずれか一項に記載のカソードまたは項目102から144のいずれか一項に記載のアノード)であって、電気活材料(例えば、酸化マンガン、アルミノシリケートおよびアルミニウム受容性ポリマーのうちの1つまたは複数を含む粒子またはフィルムとして配設されている)、ポリマーバインダー、ならびに伝導性炭素(例えば、炭素粒子または炭素リボンを含む)を含む、電極。 (項目146) 前記ポリマーバインダーが、前記電極中、全固体の0.5重量%~50重量%である、項目145に記載の電極。 (項目147) 前記ポリマーバインダーが、セルロース(例えば、カルボキシメチルセルロースまたは酢酸セルロース)、スチレンブタジエンゴム、ポリスルホン、アルギネート(例えば、アルギン酸、アルギン酸カルシウム、アルギン酸ナトリウム、アルギン酸アルミニウム、アルギン酸亜鉛またはアルギン酸マグネシウム)、アリザリン、キノン、ヒドロキノン、キノロン、ヒドロキノリンおよびポリビニルアルコール(PVA)からなる群から選択される1つまたは複数のメンバーを含む、項目145または項目146に記載の電極。 (項目148) 電流コレクタをさらに含み、前記ポリマーバインダーが、電流コレクタ上の薄層フィルム(例えば、1nm~10マイクロメートルの範囲の厚さを有する)として配設され、そうすることにより、前記ポリマーバインダーの前記薄層フィルムが、前記電気活材料と前記電流コレクタとの間に配設される[例えば、ここで、前記ポリマーバインダーの前記薄層フィルムは、以下の範囲(例えば、±20%またはそれより良好な許容度で):(i)1nm以上;(ii)1nm~10nm;(iii)5nm~20nm;(iv)20nm~50nm;(v)50nm~250nm;(vi)100nm~500nm;(vii)500nm~1マイクロメートル;および(viii)1マイクロメートル~10マイクロメートルのうちの(少なくとも)1つの範囲内の厚さを有する]、項目145から147のいずれか一項に記載の電極。 (項目149) 伝導層(例えば、1nm~10マイクロメートルの範囲の厚さを有する)をさらに含み、前記伝導層が、前記電気活材料および前記バインダーと電気的および/または物理的に接触して、前記電気活材料と前記バインダーとの間に配設されている、項目145に記載の電極。 (項目150) 前記伝導層が、炭素、スズ、酸化スズ、酸化インジウムスズ、チタン、クロム、ニッケル、金、銀および白金からなる群から選択されるメンバーを含む、項目149に記載の電極。 (項目151) 電流コレクタ、前記ポリマーバインダーの第1の薄層フィルム、第1の伝導層、前記電気活材料の第1の層、前記ポリマーバインダーの第2の薄層フィルム、第2の伝導層および前記電気活材料の第2の層を含む(例えば、ここで列挙した順序の位置で配列されている)、多層構造を含む、項目145から150のいずれか一項に記載の電極。 (項目152) 電流コレクタ、前記ポリマーバインダーの第1の薄層フィルム、前記電気活材料の第1の層、前記ポリマーバインダーの第2の薄層フィルム、および前記電気活材料の第2の層を含む(例えば、かつここで列挙した順序の位置で配列されている)、項目145から150のいずれか一項に記載の電極。 (項目153) イオン電池(例えば、水系アルミニウムイオン電池、例えば、項目1から27のいずれか一項に記載の電池)のための水性電解質であって、水(例えば、脱イオン水)およびアルミニウム塩(例えば、アルミニウムの硫酸塩、リン酸塩、硝酸塩およびハロゲン化物塩からなる群から選択される1つまたは複数のメンバー)を含む[ここで、前記水は溶媒として働き、前記アルミニウム塩は、主要添加剤である(例えば、前記電解質は、0.01M~5M、例えば0.05M~1Mの範囲の全アルミニウム塩濃度を有する)(例えば、前記アルミニウム塩は前記水に溶解している)]、水性電解質。 (項目154) ナトリウム、リチウム、カリウムまたはカルシウムの塩(例えば、ナトリウム、リチウム、カリウムまたはカルシウムの、硫酸塩、リン酸塩、硝酸塩およびハロゲン化物塩からなる群から選択される1つまたは複数のメンバー)を含む添加剤をさらに含む(例えば、前記電解質は、合計で0.01M~5M、例えば1M~3Mの範囲のナトリウム、リチウム、カリウムまたはカルシウムの塩の濃度を有する)(例えば、前記ナトリウム、リチウム、カリウムまたはカルシウムの塩は、前記水に溶解している)、項目153に記載の水性電解質。 (項目155) ポリマー(例えば、前記ポリマーは、アルギネート、キノン、キノロン、ヒドロキシキノン、アリザリンおよびヒドロキシキノリンからなる群から選択される1つまたは複数のメンバーを含む)をさらに含む(例えば、前記電解質は、0.01~50重量%、例えば0.5~10重量%の範囲の全ポリマー重量%を有する)、項目153または154に記載の水性電解質。 (項目156) 前記カソードの湿潤性を増大させる湿潤剤(例えば、前記湿潤剤は、ケトン、アルコール、アルデヒド、エーテル、エステルおよびシクロヘキサンからなる群から選択される1つまたは複数のメンバーを含む)をさらに含む(例えば、前記電解質は、0.01~50重量%、例えば0.5~10重量%の範囲の全湿潤剤重量%を有する)、項目153から155のいずれか一項に記載の水性電解質。 (項目157) マンガン塩(例えば、マンガンの硫酸塩、リン酸塩、酢酸塩、硝酸塩およびハロゲン化物塩からなる群から選択される1つまたは複数のメンバー)を含む(例えば、前記電解質は、0.01M~5M、例えば0.05M~1Mの範囲の全マンガン塩濃度を有する)(例えば、前記マンガン塩が、前記水に溶解している)、項目153から156のいずれか一項に記載の水性電解質。 (項目158) アルミニウム、アルミニウム合金およびアルミニウムコンポジットからなる群から選択される1つまたは複数のメンバーを含むアノード(例えば、項目102から144のいずれか一項に記載のアノード)、 水性電解質(例えば、項目153から157のいずれか一項に記載の電解質)、および 酸化マンガン、アルミノシリケートおよびポリマーからなる群から選択される1つまたは複数のメンバーを含むカソード(例えば、項目28から89のいずれか一項に記載のカソード) を備える、アルミニウム電池-キャパシタハイブリッドであって、 前記アルミニウム電池-キャパシタハイブリッドの1つまたは複数の構成要素(例えば、前記アノードおよび/または前記カソード)が、疑似キャパシタ添加剤および誘電性添加剤からなる群から選択される1種または複数種の添加剤を含み、 前記疑似キャパシタ添加剤が、グラフェン、酸化グラフェン、カーボンナノチューブ、フラーレン、炭素エアロゲル、酸化バナジウム、酸化チタン、酸化モリブデン、酸化ルテニウム、ポリピロールおよびポリ(3,4-エチレンジオキシチオフェン)からなる群から選択される1つまたは複数のメンバーを含み、 前記誘電性添加剤が、酸化チタン、酸化ケイ素、酸化ジルコニウム、パリレンまたは他の共役ポリマー、ポリスチレンおよびポリプロピレンからなる群から選択される1つまたは複数のメンバーを含む、 アルミニウム電池-キャパシタハイブリッド。 (項目159) 前記1種または複数種の添加剤が、疑似キャパシタ添加剤を含み、前記疑似キャパシタ添加剤が、前記アノードおよびカソードの合わせた正味重量の約0.1重量%~約90重量%を構成する、項目158に記載のアルミニウム電池-キャパシタハイブリッド。 (項目160) 前記1種または複数種の添加剤が、疑似キャパシタ添加剤を含み、前記疑似キャパシタ添加剤が、薄層フィルム、ナノ構造、マイクロ構造、粒子またはそれらの組合せの形態である、項目158または159に記載のアルミニウム電池-キャパシタハイブリッド。 (項目161) 前記1種または複数種の添加剤が、誘電性添加剤を含み、前記誘電性添加剤が、前記アノードおよびカソードの合わせた正味重量の約0.1重量%~約90重量%を構成する、項目158から160のいずれか一項に記載のアルミニウム電池-キャパシタハイブリッド。 (項目162) 前記1種または複数種の添加剤が、誘電性添加剤を含み、前記誘電性添加剤が、薄層フィルム、ナノ構造、マイクロ構造、粒子またはそれらの組合せの形態である、項目158から161のいずれか一項に記載のアルミニウム電池-キャパシタハイブリッド。 (項目163) 前記アノードが、 アルミニウム、アルミニウム合金またはアルミニウムコンポジットからなる群から選択される1つまたは複数のメンバーを含む第1のアルミニウム層、 誘電性添加剤を含む誘電性層、 アルミニウム、アルミニウム合金またはアルミニウムコンポジットからなる群から選択される1つまたは複数のメンバーを含む第2のアルミニウム層、および 保護性酸化物層 を含む、項目158から162のいずれか一項に記載のアルミニウム電池-キャパシタハイブリッド。 (項目164) 前記第1のアルミニウム層がアルミニウムホイルを含む、項目163に記載のアルミニウム電池-キャパシタハイブリッド。 (項目165) 前記誘電性層が金属酸化物を含む、項目163または164に記載のアルミニウム電池-キャパシタハイブリッド。 (項目166) 前記金属酸化物が酸化ジルコニウムである、項目165に記載のアルミニウム電池-キャパシタハイブリッド。 (項目167) 前記酸化ジルコニウムが、薄層フィルムの形態である、項目166に記載のアルミニウム電池-キャパシタハイブリッド。 (項目168) 前記第2のアルミニウム層が、アルミニウムホイルの薄層フィルムを含む、項目163から167のいずれか一項に記載のアルミニウム電池-キャパシタハイブリッド。 (項目169) 前記誘電性添加剤が酸化アルミニウムである、項目163から168のいずれか一項に記載のアルミニウム電池-キャパシタハイブリッド。 (項目170) 前記酸化アルミニウムが薄層フィルムの形態である、項目169に記載のアルミニウム電池-キャパシタハイブリッド。 (項目171) 前記カソードが、 ステンレス鋼基材、 アルミニウム、アルミニウム合金またはアルミニウムコンポジットからなる群から選択される1つまたは複数のメンバーを含むアルミニウム層、 誘電性添加剤を含む誘電性層、および 酸化マンガン層 を含む、項目158から170のいずれか一項に記載のアルミニウム電池-キャパシタハイブリッド。 (項目172) 前記誘電性添加剤が金属酸化物を含む、項目171に記載のアルミニウム電池-キャパシタハイブリッド。 (項目173) 前記金属酸化物が酸化ジルコニウムである、項目172に記載のアルミニウム電池-キャパシタハイブリッド。 (項目174) 前記アノードおよびカソードが、前記アノードの前記第2のアルミニウム層から前記カソードへのアルミニウムイオンの輸送を促進するよう配列されている、項目163から173のいずれか一項に記載のアルミニウム電池-キャパシタハイブリッド。 (項目175) 前記アノードおよびカソードが、充電中、前記カソードの前記酸化マンガン層から前記アノードの前記第2のアルミニウム層へのアルミニウムイオンの輸送を促進するよう配列されている、項目171から173のいずれか一項に記載のアルミニウム電池-キャパシタハイブリッド。 (項目176) 前記1つまたは複数の構造が、形状およびサイズの1つまたは複数に関して、粒子(例えば、酸化マンガン粒子)の多峰性(例えば、二峰性)分布を含む、項目28から34のいずれか一項に記載のカソード。 (項目177) 前記カソードの前記粒子の少なくとも80%が、以下の範囲(例えば、各峰性について、±20%またはそれより良好な許容度で): (i) 50nm以上、 (ii) 100nm~250nm、 (iii) 500nm~5マイクロメートル、 (iv) 1マイクロメートル~10マイクロメートル、および (v) 5マイクロメートル~30マイクロメートル のうちの少なくとも2つの範囲内の寸法(例えば、直径)を有する[例えば、カソードは、粒子(例えば、酸化マンガン粒子)が約20マイクロメートル(±20%)の粒子サイズを有する粒子の第1の部分および約0.5マイクロメートル(±20%)の粒子サイズを有する粒子の第2の部分を有する二峰性分布を有し、前記第1の部分および第2の部分は、前記カソードの前記粒子の少なくとも80%を構成する]、項目176に記載のカソード。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641307000003
    Figure 0007641307000003
  • Figure 0007641307000004
    Figure 0007641307000004
  • Figure 0007641307000005
    Figure 0007641307000005
Patent Text Reader

Abstract

To provide an aqueous aluminum-ion battery featuring an aluminum or aluminum alloy / composite anode, an aqueous electrolyte, and a manganese oxide, aluminosilicate, or polymer-based cathode. The batteries operate via an electrochemical reaction that requires the actual transport of aluminum ions between the anode and cathode. The compositions and structures described herein enable the aqueous aluminum-ion batteries described herein to achieve: (1) improved charge storage capacity; (2) improved gravimetric and / or volumetric energy density; (3) increased rate capability and power density (the ability to charge and discharge in shorter times); (4) improved cycle life; (5) improved electrode mechanical strength; (6) improved electrode electrochemical stability; (7) improved electrode conductivity; and (8) improved ion diffusion kinetics in the electrodes and electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Priority Application This application claims the benefit of U.S. Provisional Patent Application No. 62 / 815,770, filed March 8, 2019, the entirety of which is incorporated herein by reference. [Background technology]

[0002] The present disclosure relates generally to aqueous aluminum ion batteries, battery-capacitor hybrids, cathode compositions, anode compositions, binder compositions, and methods of making and using the same. Summary of the Invention [Means for solving the problem]

[0003] The present disclosure includes aqueous aluminum ion batteries, battery-capacitor hybrids, cathode compositions, anode compositions, binder compositions, and methods of making and using the same.

[0004] For example, anodes of aluminum or aluminum alloys / composites, aqueous electrolytes, and manganese oxide-based [e.g., MnO or MnO2 or Mn x O yDescribed herein are aqueous aluminum-ion batteries featuring aluminium-ion (e.g., Mn(II), Mn(II-x), Mn(III), Mn(III-x), Mn(IV), Mn(IV-x), Mn(V), Mn(Vx), Mn(VI), Mn(VI-x), Mn(VII) and Mn(VII-x), where x is between 0 and 1) cathodes, aluminosilicate-based (e.g., Al2SiO5) cathodes or polymer-based cathodes. The batteries operate via an electrochemical reaction that requires the actual transport of aluminum ions between the anode and cathode. In certain embodiments, the compositions and structures described herein enable the aqueous aluminum ion batteries described herein to achieve: (1) improved charge storage capacity; (2) improved gravimetric and / or volumetric energy density; (3) increased rate capability and power density (ability to charge and discharge in shorter times); (4) improved cycle life; (5) improved mechanical strength of the electrodes; (6) improved electrochemical stability of the electrodes; (7) improved conductivity of the electrodes; and (8) improved diffusion kinetics of ions in the electrodes and electrolyte.

[0005] In one aspect, the present invention provides an anode comprising one or more members selected from the group consisting of aluminum, an aluminum alloy, and an aluminum composite; an aqueous electrolyte; and a manganese oxide [e.g., MnO or MnO2 or Mn x O y(e.g., Mn(II), Mn(II-x), Mn(III), Mn(III-x), Mn(IV), Mn(IV-x), Mn(V), Mn(Vx), Mn(VI), Mn(VI-x), Mn(VII) and Mn(VII-x), x is between 0 and 1), aluminosilicates (e.g., Al2SiO5), and polymers. In certain embodiments, the cathode comprises one or more manganese oxides selected from the group consisting of MnO [manganese(II) oxide], Mn3O4 [manganese(II,III) oxide], Mn2O3 [manganese(III) oxide], MnO2 [manganese dioxide, also known as manganese(IV) oxide], MnO3 [manganese(VI) oxide], and Mn2O7 [manganese(VII) oxide].

[0006] In certain embodiments, the anode, the aqueous electrolyte, and the cathode are configured to provide anode / cathode ion exchange (e.g., Al 3+ ) are arranged to facilitate transport.

[0007] In certain embodiments, the battery has a charge storage capacity in the range of 25 mAh / g to 500 mAh / g (units: milliamp-hours per gram of active material in the battery).

[0008] In certain embodiments, the battery delivers charge at rates ranging from 1C to 0.01C (a rate of nC is defined as charge or discharge in 1 / n hours).

[0009] In certain embodiments, it provides stable cycling performance (e.g., where stable cycling performance means having a repeatable voltage profile with no or substantially no noise that may contribute to pulverization, delamination, corrosion or other side reactions) over at least 100 (e.g., at least 150) charge-discharge steps (e.g., where one cycle is equal to one charge and one discharge) (e.g., where the aluminum ion battery has a minimum cycle life of 50 cycles, 100 cycles, 150 cycles or 200 cycles).

[0010] In certain embodiments, upon application of an external load, aluminum ions (Al +3 ) is released from the electrode (e.g., the cathode or anode) into the aqueous electrolyte. In some embodiments, the released Al +3 The ions migrate through the aqueous electrolyte, the membrane separator, and to the opposing electrode (e.g., the anode or cathode, respectively) (e.g., where the electrodes are 0.001-100% aluminum by weight). For example, the anode can contain up to 100% aluminum by weight in a fully charged battery (the cathode contains negligible aluminum at this point). In the discharged state, the concentration of aluminum in the anode and cathode depends on the depth of discharge.

[0011] In certain embodiments, the released Al is present in or on the counter electrode. +3The ions intercalate and / or otherwise react with one or more members selected from the group consisting of: (i) oxygen-containing moieties, such as (a) oxides, (b) hydroxides, (c) nitrates, (d) sulfates, (e) acetates, (f) phosphates, (g) chlorates, (h) bromates, or (i) iodates; (ii) halogen-containing moieties, such as (a) chlorides, (b) fluorides, (c) bromides, (d) iodides; and (iii) metal moieties, such as (a) manganese, (b) sodium, (c) lithium, (d) aluminum, (e) potassium, (f) calcium, or (g) magnesium, thereby forming a stable aluminum phase within or on the counter electrode structure. In certain embodiments, one or more transition metals in the counter electrode change oxidation states, thereby stabilizing the electrode structure.

[0012] In one particular embodiment, the released Al +3 The ions migrate through the aqueous electrolyte, the membrane separator, to the opposing electrode and are stored (eg, as a dielectric charge) on the surface of the opposing electrode.

[0013] In certain embodiments, upon application of an external load, aluminum ions (Al +3 ) is released from the electrode (e.g., the cathode or anode) into the aqueous electrolyte, and the released Al +3The ions react with ions present in the aqueous electrolyte to form a transport phase (e.g., a stable transport phase) for transporting ions (e.g., charge carriers) through the aqueous electrolyte (e.g., through the membrane separator) to the opposite electrode (e.g., the anode or cathode, respectively) (e.g., where the electrode is 0.001-100% aluminum by weight). For example, the anode can contain up to 100% aluminum by weight in a fully charged battery (the cathode contains negligible aluminum at this point). In the discharged state, the concentration of aluminum in the anode and cathode depends on the depth of discharge. In certain embodiments, in the fully charged state, the preferred range of aluminum in the anode is between 70-100% by weight, while the preferred range of aluminum in the cathode is between 0-20% by weight. In certain embodiments, the released Al +3 The ions are OH, which are present in aqueous electrolytes. -1 It reacts with ions to form Al(OH)4 -1 Forming charge carriers (e.g., Al(OH)4 -1 The charge carriers are Al +3(prevent or reduce the ability of the ions to further react in the aqueous electrolyte). In certain embodiments, at least a portion of the charge carriers undergo one or both of the following after transport to the counter electrode: (i) dissociation to form individual anions and cations; and (ii) remaining in a stable charge carrier phase. In certain embodiments, at least a portion of the charge carriers undergo one or both of the following after transport to the counter electrode: (i) dissociation to form individual anions and cations; and the individual anions and / or cations (i) at the counter electrode: (I) oxygen-containing moieties, such as (a) oxides, (b) hydroxides, (c) nitrates, (d) sulfates, (e) acetates, (f) phosphates, (g) chlorates, (h) bromates, or (i) iodates; (II) halogen-containing moieties, such as (a) chlorides, (b) fluorides, (c) bromides, (d) iodides; and (III) undergoing one or more processes selected from the group consisting of intercalating and / or reacting with a metal moiety (e.g., thereby forming a stable phase within or on the surface of the counter electrode structure), such as one or more members selected from the group consisting of (a) manganese, (b) sodium, (c) lithium, (d) aluminum, (e) potassium, (f) calcium, or (g) magnesium, and (ii) being stored as a dielectric charge on the surface of the counter electrode.

[0014] In certain embodiments, at least a portion of the charge carriers remain in a stable charge carrier phase after transport to the counter electrode, where the charge carriers undergo one or both of: (i) intercalation within the structure of the counter electrode; and (ii) a transition to a non-ionic stable phase comprising aluminum and one or more members selected from the group consisting of oxides, hydroxides, chlorides, nitrates, sulfates, phosphates, lithium, sodium, potassium, and magnesium, and a reaction of the intercalation and / or non-ionic stable phase within the counter electrode structure.

[0015] In certain embodiments, the following mechanisms (A), (B) and (C) are used: (A) When an external load is applied, aluminum ions (Al+3 ) is released from the electrode (e.g., the cathode or anode) into the aqueous electrolyte, and the released Al +3 The ions migrate through the aqueous electrolyte, the membrane separator, and to the counter electrode (e.g., the anode or cathode, respectively) (e.g., where the electrodes are 0.001 to 100 wt. % aluminum) and form ions in or on the counter electrode, such as Al +3 The ions intercalate with and / or otherwise react with one or more members selected from the group consisting of: (i) oxygen-containing moieties, e.g., (a) oxides, (b) hydroxides, (c) nitrates, (d) sulfates, (e) acetates, (f) phosphates, (g) chlorates, (h) bromates, or (i) iodates; (ii) halogen-containing moieties, e.g., (a) chlorides, (b) fluorides, (c) bromides, (d) iodides; and (iii) metal moieties, e.g., (a) manganese, (b) sodium, (c) lithium, (d) aluminum, (e) potassium, (f) calcium, or (g) magnesium, thereby forming a stable aluminum phase within or on the structure of the counter electrode; (B) aluminum ions (Al +3 ) is released from the electrode (e.g., the cathode or anode) into the aqueous electrolyte upon application of an external load, where the released Al +3 The ions migrate through the aqueous electrolyte, the membrane separator, to the opposing electrode (e.g., the anode or cathode, respectively) (e.g., where the electrode is 0.001-100 wt. % aluminum) and are stored (e.g., as a dielectric charge) on the surface of the opposing electrode; and (C) upon application of an external load, aluminum ions (Al +3 ) is released from the electrode (e.g., the cathode or anode) into the aqueous electrolyte, and the released Al +3The ions react with ions present in the aqueous electrolyte to form a transport phase (e.g., a stable transport phase) for transporting ions (e.g., charge carriers) through the aqueous electrolyte (e.g., through the electrolyte and through the membrane separator) to the opposite electrode (e.g., the anode or cathode, respectively) (e.g., where the electrode is 0.001-100% aluminum by weight). For example, the anode can contain up to 100% aluminum by weight in a fully charged battery (the cathode contains negligible aluminum at this point). In the discharged state, the concentration of aluminum in the anode and cathode depends on the depth of discharge. In certain embodiments, in the fully charged state, the preferred range of aluminum in the anode is between 70-100% by weight, while the preferred range of aluminum in the cathode is between 0-20% by weight.

[0016] In certain embodiments, the anode comprises an aluminum alloy containing one or more non-aluminum members selected from the group consisting of sodium, lithium, calcium, potassium, magnesium, zirconium, lead, bismuth, titanium, vanadium, tin, copper, silver, gold, platinum, mercury, scandium, sulfur, silicon, iron, silicon, nickel, manganese, chromium, cerium, germanium, gallium, thallium, hafnium, indium, rhodium, ruthenium, molybdenum, palladium, strontium, yttrium, barium, cadmium, iridium, tantalum, cobalt, tellurium, antimony, arsenic, tungsten, and selenium.

[0017] In certain embodiments, the aqueous electrolyte includes one or more non-aluminum members selected from the group consisting of sodium, lithium, calcium, potassium, nickel, cobalt, iron, manganese, vanadium, titanium, tin, zinc, copper, and magnesium.

[0018] In certain embodiments, the cathode is a manganese oxide (e.g., MnO or MnO2 or Mn x Oy ), aluminosilicates (e.g., Al2SiO5), and polymers. In certain embodiments, the manganese oxide is a member selected from the group consisting of MnO [manganese oxide (II)], Mn3O4 [manganese oxide (II,III)], Mn2O3 [manganese oxide (III)], MnO2 [manganese dioxide, also known as manganese oxide (IV)], MnO3 [manganese oxide (VI)], and Mn2O7 [manganese oxide (VII)]. In certain embodiments, the cathode comprises a sheet (e.g., a sheet of manganese oxide (e.g., MnO or MnO2 or Mn x O y ) and / or aluminosilicates (e.g., Al2SiO5) and / or polymers), the guest ions and / or molecules comprising one or more members selected from the group consisting of sodium, lithium, calcium, potassium, rubidium, cesium, beryllium, strontium, barium, magnesium, nickel, zinc, bismuth, cobalt, copper, and protons. In certain embodiments, the manganese oxide is a member selected from the group consisting of MnO [manganese(II) oxide], Mn3O4 [manganese(II,III) oxide], Mn2O3 [manganese(III) oxide], MnO2 [manganese dioxide, also known as manganese(IV) oxide], MnO3 [manganese(VI) oxide], and Mn2O7 [manganese(VII) oxide].

[0019] In certain embodiments, at least one of the cathode, anode, and aqueous electrolyte contains non-aluminum ions that participate in an electrochemical reaction upon application of an external load (e.g., charging or discharging) and / or by an ion exchange process between the cathode and electrolyte and / or between the anode and electrolyte and / or between the cathode and anode.

[0020] In certain embodiments, at least one of the cathode, anode, and aqueous electrolyte (eg, at least one, at least two, or all three of the cathode, anode, and aqueous electrolyte) does not contain cobalt.

[0021] In certain embodiments, at least one of the cathode, anode, and aqueous electrolyte (eg, at least one, at least two, or all three of the cathode, anode, and aqueous electrolyte) is non-toxic.

[0022] In certain embodiments, at least one of the cathode, anode, and aqueous electrolyte (eg, at least one, at least two, or all three of the cathode, anode, and aqueous electrolyte) is non-flammable.

[0023] In certain embodiments, at least one of the cathode, anode, and aqueous electrolyte (e.g., at least one, at least two, or all three of the cathode, anode, and aqueous electrolyte) does not contain any heavy metals (e.g., does not contain any of antimony, cerium, dysprosium, erbium, europium, gadolinium, gallium, germanium, holmium, indium, lanthanum, lutetium, neodymium, niobium, praseodymium, samarium, tantalum, terbium, thulium, tungsten, uranium, ytterbium, iridium, osmium, palladium, platinum, rhodium, ruthenium, chromium, cobalt, copper, iron, lead, molybdenum, nickel, tin, and zinc).

[0024] In another aspect, the present invention provides a current collector (e.g., a conductive substrate), each of which is made of manganese oxide (e.g., MnO or MnO2 or Mn x O y), aluminosilicates (e.g., Al2SiO5) (e.g., layered aluminosilicates) and aluminium-accepting polymers, wherein the one or more structures are disposed on (e.g., directly on) a current collector and in electrical contact with the current collector (e.g., wherein a thickness of the cathode is between 10 nm and 1 mm, e.g., between 10 μm and 100 μm, e.g., between 1 μm and 10 μm, e.g., between 1 μm and 5 μm, e.g., with a tolerance of ±20% or better).

[0025] In certain embodiments, the one or more structures are each a manganese oxide (e.g., MnO or MnO2 or Mn x O y In certain embodiments, the manganese oxide is a member selected from the group consisting of MnO [manganese(II) oxide], Mn3O4 [manganese(II,III) oxide], Mn2O3 [manganese(III) oxide], MnO2 [manganese dioxide, also known as manganese(IV) oxide], MnO3 [manganese(VI) oxide], and Mn2O7 [manganese(VII) oxide].

[0026] In certain embodiments, the one or more structures comprise at least 20% by weight (e.g., 20% to 40% by weight, e.g., 40% to 60% by weight, e.g., 60% to 80% by weight, e.g., at least 80% by weight) of manganese oxide (e.g., MnO or MnO2 or MnO3) with an inter-sheet (e.g., inter-layer) separation distance (e.g., d-layer spacing of adjacent

[0001] manganese oxide sheets) of 1 Angstrom or more (e.g., 5 Angstroms or more) (e.g., 10 Angstroms or more) (e.g., and up to 100 Angstroms). x O y), in certain embodiments, there is a contribution from guest ions and molecules (e.g., in some cases, there is as much as 15% by weight of water molecules trapped within the manganese oxide crystals). Additionally, in certain embodiments, a polymer binder (2-20% by weight) and a conductive carbon additive (2-20% by weight) are added in preparing the cathode slurry.

[0027] In certain embodiments, the one or more structures include a spinel structure, a tunnel structure, a sandwich structure, an encapsulation structure, or a trapping structure.

[0028] In certain embodiments, the one or more structures comprise a turbostratic structure.

[0029] In certain embodiments, the one or more structures include one or a combination of lithiophorite structures (e.g., comprising alternating sheets of manganese oxide and aluminum hydroxide) (e.g., where the one or more structures include manganese oxide sheets having dimensions in the range of 10 nm to 500 micrometers), phyllomanganate structures (e.g., comprising metal oxides that are hydrated), and tectomanganate structures, one or more of which may be pristine or disordered and may include vacancies.

[0030] In certain embodiments, the one or more structures include (e.g., are) particles, and at least 80% of the particles of the cathode have a dimension (e.g., diameter) within (at least) one of the following ranges (e.g., with a tolerance of ±20% or better): (i) 50 nm or more (e.g., at least 80% of the particles have a dimension of 40-60 nm or more), (ii) 100 nm to 250 nm (e.g., at least 80% of the particles have a dimension between 80-120 nm and 200-300 nm), (iii) 500 nm to 5 micrometers (e.g., at least 80% of the particles have a dimension between 400-600 nm and 4-6 micrometers), (iv) 1 micrometer to 10 micrometers, and (v) 5 micrometers to 30 micrometers.

[0031] In certain embodiments, the one or more structures include a multimodal (e.g., bimodal) distribution of particles (e.g., manganese oxide particles) with respect to one or more of shape and size. In certain embodiments, at least 80% of the particles of the cathode have a dimension (e.g., diameter) within at least two of the following ranges (e.g., with a tolerance of ±20% or better for each modality): (i) 50 nm or more, (ii) 100 nm to 250 nm, (iii) 500 nm to 5 micrometers, (iv) 1 micrometer to 10 micrometers, and (v) 5 micrometer to 30 micrometers (e.g., the cathode has a bimodal distribution of particles (e.g., manganese oxide particles) having a first portion of particles having a particle size of about 20 micrometers (±20%) and a second portion of particles having a particle size of about 0.5 micrometers (±20%), the first portion and the second portion making up at least 80% of the particles of the cathode). The anode and / or cathode may also include a bimodal or multimodal distribution of particle shapes in addition to a bimodal or multimodal distribution of particle sizes. For example, the anode and / or cathode may consist of about 20% by weight of a distribution of spherical particles and about 80% by weight of a distribution of sheets.

[0032] In certain embodiments, the one or more structures include sheets (e.g., are sheet elements), and at least 80% of the sheets of the cathode have a dimension (e.g., a thickness) within (at least) one of the following ranges (e.g., with a tolerance of ±20% or better): (i) 50 nm or more (e.g., at least 80% of the sheets have a dimension of 40-60 nm or more), (ii) 100 nm to 250 nm (e.g., at least 80% of the sheets have a dimension between 80-120 nm and 200-300 nm), (iii) 500 nm to 5 micrometers (e.g., at least 80% of the sheets have a dimension between 400-600 nm and 4-6 micrometers), (iv) 1 micrometer to 10 micrometers, and (v) 5 micrometers to 30 micrometers.

[0033] In certain embodiments, the cathode includes one or more non-aluminum guest ions stored between manganese oxide sheets.

[0034] In certain embodiments, the cathode includes one or more non-aluminum guest ions disposed within sites (eg, interstitial sites) and / or vacancies of the manganese oxide crystal lattice.

[0035] In certain embodiments, the guest ion comprises one or more members selected from the group consisting of proton, sodium, lithium, calcium, potassium, zinc, bismuth, copper, lead, cobalt, nickel, magnesium, hydrogen, hydronium, hydroxide, oxide-hydroxide, sulfate, sulfide, nitride, nitrate, phosphide, phosphate, acetate, polyoxometalates (POMs), and pillar-forming agents (e.g., aliphatic and / or aromatic compounds).

[0036]

[0037] In some embodiments, the cathode includes one or more non-aluminum guest molecules stored between manganese oxide sheets.

[0038] In certain embodiments, the cathode includes one or more non-aluminum guest ions disposed at sites (eg, interstitial sites) and / or vacancies of the manganese oxide crystal lattice.

[0039] In certain embodiments, the guest molecule comprises one or more members selected from the group consisting of oxides, hydroxides, oxide-hydroxides, sulfides, sulfates, nitrides, nitrates, chlorides, chlorates, phosphates, and phosphides.

[0040] In certain embodiments, the guest molecule comprises one or more phosphates, hi certain embodiments, the one or more phosphates are members selected from the group consisting of sodium phosphates, lithium phosphates, potassium phosphates, calcium phosphates, magnesium phosphates, and manganese phosphates.

[0041] In certain embodiments, the cathode includes phosphates of aluminum stored between manganese oxide sheets or disposed in sites (eg, interstitial sites) and / or vacancies of the manganese oxide crystal lattice.

[0042] In certain embodiments, the cathode comprises one or more pillar-forming agents stored between the manganese oxide sheets, hi certain embodiments, the one or more pillar-forming agents comprise one or more members selected from the group consisting of polyoxometalates (POMs), amphiphilic molecules, polar organic molecules, and non-polar organic molecules.

[0043] In certain embodiments, each of the one or more structures comprises an aluminum-receptive polymer. In certain embodiments, the aluminum-receptive polymer comprises a member selected from the group consisting of alizarin, alginate, amidinate, quinone, quinolone, hydroxyquinone and hydroxyquinoline. In certain embodiments, the aluminum-receptive polymer exists as a complex with one or more members selected from the group consisting of lithium, sodium, potassium, calcium, magnesium, manganese, iron, cobalt, titanium, tin, vanadium and tungsten (e.g., where the complex participates in an electrochemical reaction with aluminum ions from the electrolyte and / or aluminum source electrode (e.g., anode) by an ion exchange process in a battery during charging / discharging).

[0044] In certain embodiments, the one or more structures are particles (e.g., manganese oxide (e.g., MnO or MnO2 or Mn x O y ) (e.g., the particles are nanoparticles, microparticles, or a combination of nanoparticles and microparticles) (e.g., the particles are spheres having diameters ranging from 10 nm to 500 micrometers). In certain embodiments, the cathode comprises a plurality of conductive posts projecting from a current collector, the particles being disposed on the plurality of conductive posts.

[0045] In certain embodiments, the one or more structures include a thin film (e.g., a patterned thin film). In certain embodiments, the cathode comprises a plurality of conductive posts protruding from a current collector, and the thin film is disposed on the plurality of conductive posts (e.g., and the thin film is patterned to correspond to the distribution of the posts on the current collector).

[0046] In certain embodiments, the current collector is porous (e.g., a mesh, a foam, interconnected fibers, tubes and sheets, nanotubes, or graphene-like structures). In certain embodiments, one or more structures are disposed (e.g., coated) within or on the pores of the current collector.

[0047] In certain embodiments, the one or more structures are coated onto the one or more porous carbon structures. In certain embodiments, the one or more porous carbon structures comprise one or more members selected from the group consisting of carbon fibers, nanofibers, carbon nanotubes (CNTs), fullerenes, graphene, partially reduced graphene oxide, aerogels, xerogels, and interpenetrating multiphase materials.

[0048] In certain embodiments, the cathode further comprises a binder (e.g., a polymeric binder) that physically maintains (e.g., adheres) one or more structures in contact with the current collector. In certain embodiments, the binder is selected from the group consisting of carboxymethyl cellulose, styrene butadiene rubber, polyvinyl alcohol, alginate, polypropylene, and polytetrafluoroethylene (PTFE).

[0049] In some embodiments, the binder is selected from the group consisting of alginate, PVDF, PTFE, polyaniline, epoxy, carboxymethyl cellulose, rubber, styrene butadiene rubber, polyacrylic acid, polyvinyl alcohol, and polyvinyl propylene.

[0050] In some embodiments, the binder is pre-treated with one or more species of multivalent ions.

[0051] In some embodiments, the one or more species of multivalent ions include one or more ions of manganese, magnesium, calcium, zinc, barium, and aluminum.

[0052] In some embodiments, the binder is pretreated with one or more species of monovalent ions.

[0053] In some embodiments, the one or more species of monovalent ions include one or more ions of lithium, sodium, and potassium.

[0054] In some embodiments, the binder comprises ions of one or more members selected from the group consisting of sodium, potassium, magnesium, manganese, aluminum, calcium, barium, strontium, and zinc.

[0055] In some embodiments, the binder is deposited from a solution comprising one or more of water, n-methylpyrrolidone, ketones, glycols, dimethylsulfoxide (DMSO) and esters, and optionally a co-solvent selected from the group consisting of water, n-methylpyrrolidone, ketones, glycols, DMSO and esters.

[0056] In some embodiments, the cathode is binder-free (e.g., where one or more structures are formed on a current collector using one or more of chemical vapor deposition, physical vapor deposition, atomic layer deposition, spin-coating, and electrochemical deposition).

[0057] In certain embodiments, the cathode further includes a conductive additive (eg, a carbon-containing additive) in electrical contact with the current collector and one or more structures.

[0058] In certain embodiments, the current collector comprises one or more members selected from the group consisting of stainless steel, copper, carbon, silver, gold, platinum, tin, vanadium, zinc, tin oxide, indium, indium tin oxide (ITO), aluminum, nickel, tungsten, chromium, and titanium.

[0059] In certain embodiments, the current collector includes a coating of an adhesion promoter, a conductivity promoter, or both an adhesion promoter and a conductivity promoter.

[0060] In some embodiments, the cathode comprises manganese oxide in one or more phases, the one or more phases being selected from the group consisting of an alpha phase, a beta phase, a lambda phase, a ramsdellite phase, an amorphous phase, a gamma phase, a delta phase, and an epsilon phase.

[0061] In some embodiments, the one or more phases is two or more phases (eg, three or more phases).

[0062] In some embodiments, a predominant one of the two or more phases is at least 40% by weight of the cathode and all remaining two or more phases are 50% by weight or less of the cathode.

[0063] In some embodiments, the manganese oxide is arranged to undergo at least one phase change during charging and discharging (eg, ion insertion and removal) of the cathode.

[0064] In some embodiments, the cathode comprises a manganese oxide having a layered structure (eg, phyllomanganate), a tunnel structure (eg, tectomanganate), a spinel structure, a ramsdellite structure, or an amorphous structure.

[0065] In some embodiments, the cathode comprises a manganese oxide, wherein the manganese in the manganese oxide has one or more oxidation states selected from the group consisting of Mn(II), Mn(II-x), Mn(III), Mn(III-x), Mn(IV), Mn(IV-x), Mn(V), Mn(Vx), Mn(VI), Mn(VI-x), Mn(VII), and Mn(VII-x), where x is between 0 and 1.

[0066] In some embodiments, the one or more structures include manganese oxide, where the manganese oxide is predominantly (e.g., at least 70% by weight, at least 80% by weight, or at least 90% by weight) delta phase manganese oxide.

[0067] In certain embodiments, the current collector comprises one or more coatings of carbon, metal (e.g., tin, zinc, aluminum, chromium, copper, nickel, iron, zirconium, silver, gold, platinum), metal oxide (e.g., indium tin oxide, tin oxide, titanium oxide, vanadium oxide, zirconium oxide) or polymer (e.g., PEDOT, PAN, parylene), where the coating acts as one or more of an adhesion promoter, an electronic conductivity promoter and an ionic conductivity inhibitor.

[0068] In another aspect, the invention is a cathode for an ion battery (e.g., an aluminum ion battery or an aqueous aluminum ion battery), the cathode being made by a method comprising depositing a quantity of a solution onto a current collector, the solution being a manganese oxide (e.g., MnO or MnO2 or Mn x O y ), layered aluminosilicates (e.g., Al2SiO5), and aluminum-accepting polymers, and one or more solvents (e.g., selected from the group consisting of water, N-methylpyrrolidone, and ethanol). In certain embodiments, the one or more members include manganese oxides selected from the group consisting of MnO [manganese oxide (II)], Mn3O4 [manganese oxide (II,III)], Mn2O3 [manganese oxide (III)], MnO2 [manganese dioxide, also known as manganese oxide (IV)], MnO3 [manganese oxide (VI)], and Mn2O7 [manganese oxide (VII)].

[0069] In certain embodiments, one or more members may comprise reacting one or more manganese oxide precursors with a base in the presence of an oxygen source (e.g., and optionally an oxidant chemical catalyst), and, optionally, producing a manganese oxide (e.g., MnO or MnO2 or MnO3) after the reacting step. x O y (v) a manganese oxide produced by a method comprising hydrothermally treating a manganese oxide precursor comprising: (i) a manganese salt; (ii) a manganese salt; (iii) a manganese salt; (iv) a manganese salt; and (vi) a manganese salt.

[0070] In certain embodiments, the base comprises lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium hydroxide.

[0071] In certain embodiments, the oxygen source is dissolved oxygen gas or a peroxide (eg, hydrogen peroxide).

[0072] In certain embodiments, the solution further comprises one or more of a binder (e.g., a polymeric binder, e.g., a polymeric binder permeable by an electrolyte solution comprising one or more aluminum salts) and a conductive additive (e.g., a carbon-containing additive).

[0073] In certain embodiments, the depositing step includes doctor blading, spin coating, comma coating, or slot-die coating.

[0074] In certain embodiments, the method further comprises the step of calendering the deposited solution and the current collector.

[0075] In some embodiments, the solution comprises one or more members selected from the group consisting of water, n-methylpyrrolidone, ketones, glycols, dimethylsulfoxide (DMSO), and esters, and optionally a co-solvent selected from the group consisting of water, n-methylpyrrolidone, ketones, glycols, DMSO, and esters.

[0076] In some embodiments, the solution comprises (i) a binder selected from the group consisting of alginate, PVDF, PTFE, polyaniline, epoxy, carboxymethyl cellulose, rubber, styrene butadiene rubber, polyacrylic acid, polyvinyl alcohol, and polyvinyl propylene, and (ii) an ionic species selected from the group consisting of sodium, lithium, potassium, magnesium, manganese, aluminum, calcium, barium, strontium, and zinc.

[0077] In another aspect, the present invention provides a cathode for an aluminum ion battery (e.g., an aluminum ion battery or an aqueous aluminum ion battery), comprising a manganese oxide (e.g., MnO or MnO2 or Mn x O y and one or more sacrificial materials, and removing the one or more sacrificial materials. In certain embodiments, the manganese oxide is a member selected from the group consisting of MnO [manganese oxide (II)], Mn3O4 [manganese oxide (II,III)], Mn2O3 [manganese oxide (III)], MnO2 [manganese dioxide, also known as manganese oxide (IV)], MnO3 [manganese oxide (VI)], and Mn2O7 [manganese oxide (VII)].

[0078] In certain embodiments, the one or more sacrificial materials comprise one or more members selected from the group consisting of alizarin, amidinates, quinones, alginates, zeolites, quinolones, hydroxyquinones, hydroxyquinolines, silicon, copper, cobalt, chromium, nickel, iron, oxides, hydroxides, sulfates, nitrates, and phosphates (e.g., of silicon, copper, cobalt, chromium, nickel, or iron).

[0079] In certain embodiments, the co-depositing step includes co-thermal evaporation, co-sputtering, co-extrusion, or co-coating (eg, spin-coating, doctor blading, or slot-die coating).

[0080] In another aspect, the present invention provides a method for manufacturing a cathode for an aluminum-ion battery (e.g., an aluminum-ion battery or an aqueous aluminum-ion battery), comprising depositing a quantity of a solution onto a current collector, wherein the solution is a manganese oxide (e.g., MnO or MnO2 or Mn x O y ), layered aluminosilicates (e.g., Al2SiO5) and aluminum-accepting polymers, and one or more solvents (e.g., selected from the group consisting of water, N-methylpyrrolidone and ethanol). In certain embodiments, the one or more members comprise a manganese oxide selected from the group consisting of MnO [manganese oxide (II)], Mn3O4 [manganese oxide (II,III)], Mn2O3 [manganese oxide (III)], MnO2 [manganese dioxide, also known as manganese oxide (IV)], MnO3 [manganese oxide (VI)] and Mn2O7 [manganese oxide (VII)].

[0081] In certain embodiments, manganese oxide (e.g., MnO or MnO2 or MnO3) can be produced by reacting one or more manganese oxide precursors with a base in the presence of an oxygen source (e.g., and optionally an oxidant chemical catalyst), and optionally hydrothermally treating the manganese oxide after the reacting step. x O y The method further comprises the step of preparing a precursor solution comprising: (a) a manganese salt, a lithium salt, a sodium salt, a magnesium salt, nickel, zinc, aluminum, an inorganic acid, and a permanganate, wherein the manganese salt comprises one or more of sulfate, (i) nitrate, (ii) chloride, (iii) acetate, (iv) phosphate, (v) perchlorate, (vi) fluoride, and (vii) bromide, and the permanganate comprises one or more of (i) sodium, and (ii) potassium. In certain embodiments, the base comprises one or more of lithium hydroxide, sodium hydroxide, potassium hydroxide, and calcium hydroxide. In certain embodiments, the oxygen source is dissolved oxygen gas or a peroxide (e.g., hydrogen peroxide).

[0082] In certain embodiments, the solution further comprises one or more of a binder (e.g., a polymeric binder, e.g., a polymeric binder permeable by an electrolyte solution comprising one or more aluminum salts) and a conductive additive (e.g., a carbon-containing additive).

[0083] In certain embodiments, the depositing step includes doctor blading, spin coating, or slot-die coating.

[0084] In certain embodiments, the method further comprises the step of calendering the deposited solution and the current collector.

[0085] In another aspect, the present invention provides a method for manufacturing a cathode for an aluminum-ion battery (e.g., an aluminum-ion battery or an aqueous aluminum-ion battery), comprising depositing manganese oxide (e.g., MnO or MnO2 or MnO3) on a current collector. x O y and one or more sacrificial materials, and removing the one or more sacrificial materials. In certain embodiments, the one or more sacrificial materials include one or more members selected from the group consisting of alizarin, amidinates, quinones, alginates, zeolites, quinolones, hydroxyquinones, hydroxyquinolines, silicon, copper, cobalt, chromium, nickel, iron, oxides, hydroxides, sulfates, nitrates, and phosphates (e.g., of silicon, copper, cobalt, chromium, nickel, or iron). In certain embodiments, the manganese oxide is a member selected from the group consisting of MnO [manganese oxide (II)], Mn3O4 [manganese oxide (II,III)], Mn2O3 [manganese oxide (III)], MnO2 [manganese dioxide, also known as manganese oxide (IV)], MnO3 [manganese oxide (VI)], and Mn2O7 [manganese oxide (VII)].

[0086] In certain embodiments, the co-depositing step comprises one or more members selected from the group consisting of co-thermal evaporation, co-sputtering, co-extrusion or co-coating (e.g., spin-coating, doctor blading or slot-die coating).

[0087] In another aspect, the invention provides an anode for an ion battery (e.g., an aluminum ion battery or an aqueous aluminum ion battery) comprising one or more structures (e.g., one or more foils, thin films, or particles), each of which comprises one or more aluminum-containing members selected from the group consisting of aluminum, aluminum alloys, and aluminum composites, wherein the anode is between 0.001% and 100% aluminum by weight (e.g., between 70% and 100% aluminum by weight, such as at least 95% aluminum by weight) (e.g., where the anode is at least 95% aluminum by weight). % by weight of aluminum and up to 5% by weight of non-aluminum species, e.g., the non-aluminum species include one or more alloying metals and / or oxides intentionally incorporated into the anode) (e.g., where the purity of the aluminum is at least 99.9 atomic %, e.g., at least 99.99 atomic %, e.g., 99.99 atomic % to 99.99999 atomic %, e.g., where impurities are present in the range of 0.01 atomic % to 0.00001 atomic %, e.g., the impurities include iron and / or sodium and / or magnesium and / or silica, e.g., impurities commonly found in metal foils) for an anode. In some embodiments, the anode comprises a surface layer comprising (e.g., consisting of) one or more of aluminum, oxygen, hydrogen, nitrogen, lithium manganese, and carbon.

[0088] In certain embodiments, each of the one or more structures comprises an aluminum alloy or mixture that includes one or more non-aluminum members selected from the group consisting of sodium, lithium, calcium, potassium, magnesium, zirconium, lead, bismuth, titanium, vanadium, tin, copper, silver, gold, platinum, mercury, scandium, sulfur, silicon, iron, silicon, nickel, manganese, chromium, cerium, germanium, gallium, thallium, hafnium, indium, rhodium, ruthenium, molybdenum, palladium, strontium, yttrium, barium, cadmium, iridium, tantalum, cobalt, tellurium, antimony, arsenic, tungsten, and selenium.

[0089] In certain embodiments, the anode comprises a film including one or more structures, each of which is a particle (e.g., where the particle has a diameter in the range of 10 nm to 100 micrometers) (e.g., where the film has a thickness in the range of 10 nm to 1 mm). In certain embodiments, at least 80% of the particles of the anode are within the following ranges (e.g., with a tolerance of ±20% or better): (i) 50 nm or more (e.g., at least 80% of the particles have dimensions of 40-60 nm or more), (ii) 100 nm to 500 nm (e.g., at least 80% of the particles have dimensions between 80-120 nm and 400-600 nm), (iii) 250 nm to 1 micrometer (e.g., at least 80% of the particles have dimensions between 200-300 nm and 0.8-1.2 micrometers). (iv) 500 nm to 5 micrometers (e.g., at least 80% of the particles have a dimension between 400-600 nm and 4-6 micrometers), (v) 1 micrometer to 10 micrometers, (vi) 5 micrometer to 25 micrometers, (vii) 10 micrometer to 50 micrometers, and (viii) 50 micrometer to 100 micrometers.

[0090] In certain embodiments, the film further comprises a polymeric binder in physical contact with the plurality of particles, the polymeric binder being selected from the group consisting of carboxymethyl cellulose, styrene butadiene rubber, polyvinyl alcohol, polypropylene, and polytetrafluoroethylene.

[0091] In certain embodiments, the film further comprises one or more conductive carbon additives. In certain embodiments, the one or more structures include a thin film having a thickness in the range of 1 nm to 1 mm. In certain embodiments, the thin film has a thickness within (at least) one of the following ranges (e.g., with a tolerance of ±20% or better): (i) 50 nm or more (e.g., a thickness of 40 to 60 nm or more), (ii) 100 nm to 500 nm (e.g., a thickness between 80 to 120 nm and 400 to 600 nm), (iii) 250 nm to 1 micrometer (e.g., a thickness between 200 to 300 nm and 0.8 to 1.2 micrometers), (iv) 500 nm to 5 micrometers (e.g., a thickness between 400 to 600 nm and 4 to 6 micrometers), (v) 1 micrometer to 10 micrometers, (vi) 5 micrometers to 25 micrometers, (vii) 10 micrometers to 50 micrometers, and (viii) 50 micrometers to 100 micrometers.

[0092] In certain embodiments, the thin film is coated on a current collector (e.g., a conductive substrate) (e.g., where the conductive substrate comprises one or more members selected from the group consisting of carbon, steel, nickel, iron, zinc, aluminum, titanium, tungsten, copper, silver, tin, indium, and chromium). In some embodiments, the thin film is coated on a current collector (e.g., a conductive substrate) that further comprises one or more coatings of carbon, metal (e.g., tin, zinc, aluminum, chromium, copper, nickel, iron, zirconium, silver, gold, platinum), metal oxide (e.g., indium tin oxide, tin oxide, titanium oxide, vanadium oxide, zirconium oxide), or polymer (e.g., PEDOT, PAN, parylene), where the coating acts as one or more of an adhesion promoter, an electronic conductivity promoter, and an ionic conductivity inhibitor.

[0093]

[0094] In certain embodiments, the thickness is sufficient to provide an anode with a capacity that matches that of a cathode in a battery that includes the anode and cathode.

[0095] In certain embodiments, the one or more structures include a foil having a polished surface (e.g., mechanically or electrochemically polished). In certain embodiments, the foil includes polished aluminum having a native oxide layer having a thickness of 10 nanometers and less. In certain embodiments, the polished aluminum has a mirror finish (a qualitative characteristic).

[0096] In certain embodiments, the one or more structures comprise a porous structure (eg, the porous structure comprises pores having a circular or rectangular cross-section).

[0097] In certain embodiments, the one or more structures comprise a plurality of posts projecting from a current collector (e.g., a conductive substrate) (e.g., where the conductive substrate comprises one or more members selected from the group consisting of carbon, stainless steel, nickel, titanium, tungsten, copper and chromium).

[0098] In certain embodiments, the anode further comprises a non-native transitional aluminum oxide layer (e.g., having a thickness in the range of 0.1 nm to 10 micrometers) (e.g., formed by atomic layer deposition, chemical vapor deposition, thermal reaction, hydrothermal reaction, etching, electrochemical reaction, oxygen plasma reaction, or hydroxide treatment). In certain embodiments, the non-native transitional aluminum oxide layer has a thickness within (at least) one of the following ranges (e.g., with a tolerance of ±20% or better): (i) 1 nm or more, (ii) 1 nm to 10 nm, (iii) 5 nm to 20 nm, (iv) 20 nm to 50 nm, (v) 50 nm to 250 nm, (vi) 100 nm to 500 nm, (vii) 500 nm to 1 micrometer, and (viii) 1 micrometer to 10 micrometer. In certain embodiments, the non-native transitional aluminum oxide layer is disposed on one or more structures (e.g., including a thin film or foil).

[0099] In certain embodiments, the anode further comprises an oxide film disposed on the one or more structures (e.g., having a thickness in the range of 0.1 nm to 100 micrometers) [e.g., where the oxide film is patterned (e.g., where the oxide film is patterned to correspond to the distribution of pillars on a current collector)]. In certain embodiments, the oxide film has a thickness within (at least) one of the following ranges (e.g., with a tolerance of ±20% or better): (i) 1 nm or more, (ii) 1 nm to 10 nm, (iii) 5 nm to 20 nm, (iv) 20 nm to 50 nm, (v) 50 nm to 250 nm, (vi) 100 nm to 500 nm, (vii) 500 nm to 1 micrometer, and (viii) 1 micrometer to 10 micrometers.

[0100] In one particular embodiment, the oxide film is a thin film.

[0101] In certain embodiments, the oxide film is a coating that includes a plurality of oxide particles. In certain embodiments, the plurality of oxide particles includes nanoparticles, microparticles, or both nanoparticles and microparticles. In certain embodiments, at least 80% of the oxide particles have a dimension (e.g., diameter) within (at least) one of the following ranges (e.g., with a tolerance of ±20% or better): (i) 1 nanometer to 500 micrometers, and (ii) 10 nanometers to 20 micrometers.

[0102] In certain embodiments, the oxide film further comprises a polymer binder selected from the group consisting of carboxymethyl cellulose, styrene butadiene, polyvinyl alcohol, polypropylene, and polytetrafluoroethylene.

[0103] In certain embodiments, the oxide film further comprises one or more conductive carbon additives.

[0104] In certain embodiments, the anode comprises a plurality of oxide films, each of the plurality of oxide films comprising a different oxide.

[0105] In certain embodiments, the anode includes multiple oxide layers of the same or different types, optionally with one or more aluminum layers between the oxide layers (e.g., the anode includes at least one example of the following order of layers: Al / Al2O3 / ZrO2 / Al2O3) (e.g., the anode includes at least one example of the following order of layers: Al / Al2O3 / Al / Al2O3).

[0106] In certain embodiments, the one or more structures include a thin film or foil, and each of the plurality of oxide films is in contact with the one or more structures (e.g., arranged in rows (e.g., ordered rows) on the thin film or foil).

[0107] In certain embodiments, multiple oxide films are disposed as layers on one or more structures.

[0108] In certain embodiments, the one or more structures include a plurality of thin films or foils, one or more of which are disposed between two or more oxide films.

[0109] In certain embodiments, the anode includes a plurality of oxide pillars protruding from one or more structures. In certain embodiments, the plurality of oxide pillars is porous. In certain embodiments, the plurality of oxide pillars includes one or more of fibers, nanotubes, and nanocolumns. In certain embodiments, the plurality of oxide pillars is formed by physical vapor deposition, chemical vapor deposition, atomic layer deposition, hydrothermal reaction, electrochemical reaction, electrochemical deposition, or thermal reaction. In certain embodiments, the plurality of oxide pillars is formed by depositing a film and etching the film, the etching comprising plasma etching, wet chemical etching, reactive ion etching, or buffered oxide etching.

[0110] In certain embodiments, the anode further comprises a non-oxide film disposed on one or more structures (e.g., directly on one or more structures or with one or more oxide films disposed between the non-oxide film and the one or more structures). In certain embodiments, the non-oxide film comprises one or more non-oxide members selected from the group consisting of elemental sulfides, elemental sulfates, elemental nitrides, elemental nitrates, elemental phosphides, elemental phosphates, and elemental halides, where the elements are selected from the group consisting of zirconium, tungsten, indium, chromium, cobalt, magnesium, iron, nickel, vanadium, titanium, zinc, manganese, iron, tin, silicon, sulfur, copper, hafnium, and cobalt. In certain embodiments, the non-oxide film is a thin film. In certain embodiments, the non-oxide film is a coating comprising a plurality of non-oxide particles (e.g., comprising one or more non-oxide members). In certain embodiments, the plurality of non-oxide particles comprises nanoparticles, microparticles, or both nanoparticles and microparticles.

[0111] In certain embodiments, the anode includes a polymer layer disposed on one or more structures (e.g., where the surface coverage of the one or more structures by the polymer layer is 1% to 100%, e.g., at least 50% of the surface of the one or more structures is covered by the polymer layer) (e.g., where the polymer layer has a thickness in the range of 0.1 nm to 100 micrometers) (e.g., where the polymer layer has a thickness within (at least) one of the following ranges (e.g., with a tolerance of ±20% or better): (i) 1 nm or more; (ii) 1 nm to 10 nm; (iii) 5 nm to 20 nm; (iv) 20 nm to 50 nm; (v) 50 nm to 250 nm; (vi) 100 nm to 500 nm; (vii) 500 nm to 1 micrometer; and (viii) 1 micrometer to 10 micrometers). In certain embodiments, the polymer layer comprises one or more members selected from the group consisting of parylene, polyvinyl alcohol, alginic acid, PTFE, polyethylene oxide, cellulose (and derivatives thereof), polysulfone (PES), polymers of one or more acrylates, alginates (e.g., containing sodium, calcium, aluminum, potassium, magnesium, or zinc), quinones, hydroquinones, quinolones, hydroxyquinolines, and alizarins (e.g., containing Alizarin Red S).

[0112] In another aspect, the present invention provides an electrode (e.g., a cathode or anode) for an ion battery (e.g., an aluminum ion battery or an aqueous aluminum ion battery), comprising an electroactive material (e.g., a manganese oxide (e.g., MnO or MnO2 or Mn x O y), an aluminosilicate, and an aluminum-receptive polymer (arranged as particles or a film comprising the aluminosilicate, the aluminosilicate, and the aluminum-receptive polymer), a polymer binder, and conductive carbon (e.g., comprising carbon particles or carbon ribbons). In certain embodiments, the manganese oxide is a member selected from the group consisting of MnO [manganese oxide (II)], Mn3O4 [manganese oxide (II,III)], Mn2O3 [manganese oxide (III)], MnO2 [manganese dioxide, also known as manganese oxide (IV)], MnO3 [manganese oxide (VI)], and Mn2O7 [manganese oxide (VII)].

[0113] In certain embodiments, the polymer binder is 0.5% to 50% by weight of the total solids in the electrode.

[0114] In certain embodiments, the polymeric binder comprises one or more members selected from the group consisting of cellulose (e.g., carboxymethyl cellulose or cellulose acetate), styrene butadiene rubber, polysulfone, alginate (e.g., alginic acid, calcium alginate, sodium alginate, aluminum alginate, zinc alginate, or magnesium alginate), alizarin, quinone, hydroquinone, quinolone, hydroquinoline, and polyvinyl alcohol (PVA).

[0115] In certain embodiments, the electrode further comprises a current collector, and the polymer binder is disposed as a thin film (e.g., having a thickness in the range of 1 nm to 10 micrometers) on the current collector, such that the thin film of the polymer binder is disposed between the electroactive material and the current collector (e.g., where the thin film of the polymer binder has a thickness within (at least) one of the following ranges (e.g., with a tolerance of ±20% or better): (i) 1 nm or more; (ii) 1 nm to 10 nm; (iii) 5 nm to 20 nm; (iv) 20 nm to 50 nm; (v) 50 nm to 250 nm; (vi) 100 nm to 500 nm; (vii) 500 nm to 1 micrometer; and (viii) 1 micrometer to 10 micrometers). In certain embodiments, the electrode further comprises a conductive layer (e.g., having a thickness in the range of 1 nm to 10 micrometers), the conductive layer being in electrical and / or physical contact with and disposed between the electroactive material and the binder. In certain embodiments, the conductive layer comprises a member selected from the group consisting of carbon, tin, tin oxide, indium tin oxide, titanium, chromium, nickel, gold, silver, and platinum.

[0116] In certain embodiments, the electrode comprises a multi-layer structure including a current collector, a first thin film of a polymer binder, a first conductive layer, a first layer of electroactive material, a second thin film of a polymer binder, a second conductive layer, and a second layer of electroactive material (e.g., arranged in the order of positions recited herein).

[0117] In certain embodiments, an electrode includes a current collector, a first thin film of a polymer binder, a first layer of an electroactive material, a second thin film of a polymer binder, and a second layer of an electroactive material (e.g., arranged in the order of positions recited herein).

[0118] In another aspect, the present invention is directed to an aqueous electrolyte for an ion battery (e.g., an aqueous aluminum ion battery) comprising water (e.g., deionized water) and an aluminum salt (e.g., one or more members selected from the group consisting of sulfate, phosphate, nitrate, and halide salts of aluminum) where water serves as the solvent and the aluminum salt is the primary additive (e.g., the electrolyte has a total aluminum salt concentration in the range of 0.01 M to 5 M, e.g., 0.05 M to 1 M) (e.g., the aluminum salt is dissolved in the water).

[0119] In certain embodiments, the aqueous electrolyte further comprises an additive comprising a salt of sodium, lithium, potassium, or calcium (e.g., one or more members selected from the group consisting of sulfate, phosphate, nitrate, and halide salts of sodium, lithium, potassium, or calcium) (e.g., the electrolyte has a total concentration of the sodium, lithium, potassium, or calcium salt in the range of 0.01 M to 5 M, e.g., 1 M to 3 M) (e.g., the sodium, lithium, potassium, or calcium salt is dissolved in the water).

[0120] In certain embodiments, the aqueous electrolyte further comprises a polymer (e.g., the polymer comprises one or more members selected from the group consisting of alginate, quinone, quinolone, hydroxyquinone, alizarin, and hydroxyquinoline) (e.g., the electrolyte has a total polymer weight percent in the range of 0.01 to 50 wt %, e.g., 0.5 to 10 wt %).

[0121] In certain embodiments, the aqueous electrolyte further comprises a wetting agent (e.g., the wetting agent comprises one or more members selected from the group consisting of ketones, alcohols, aldehydes, ethers, esters, and cyclohexanes) that increases the wettability of the cathode (e.g., the electrolyte has a total wetting agent weight % in the range of 0.01 to 50 wt %, e.g., 0.5 to 10 wt %).

[0122] In certain embodiments, the aqueous electrolyte includes a manganese salt (e.g., one or more members selected from the group consisting of sulfate, phosphate, acetate, nitrate, and halide salts of manganese) (e.g., the electrolyte has a total manganese salt concentration in the range of 0.01 M to 5 M, e.g., 0.05 M to 1 M) (e.g., the manganese salt is dissolved in water).

[0123] In another aspect, the present invention provides a cathode comprising an anode comprising one or more members selected from the group consisting of aluminum, an aluminum alloy, and an aluminum composite, an aqueous electrolyte, and a manganese oxide (e.g., MnO or MnO2 or Mn x O y and a cathode comprising one or more members selected from the group consisting of aluminosilicates, aluminosilicates and polymers, wherein one or more components (e.g., the anode and / or cathode) of the aluminum battery-capacitor hybrid comprise one or more additives selected from the group consisting of pseudocapacitor additives and dielectric additives, wherein the pseudocapacitor additive comprises one or more members selected from the group consisting of graphene, graphene oxide, carbon nanotubes, fullerenes, carbon aerogels, vanadium oxide, titanium oxide, molybdenum oxide, ruthenium oxide, polypyrrole and poly(3,4-ethylenedioxythiophene), and the dielectric additive comprises one or more members selected from the group consisting of titanium oxide, silicon oxide, zirconium oxide, parylene or other conjugated polymers, polystyrene and polypropylene. In certain embodiments, the manganese oxide is a member selected from the group consisting of MnO [manganese oxide (II)], Mn3O4 [manganese oxide (II,III)], Mn2O3 [manganese oxide (III)], MnO2 [manganese dioxide, also known as manganese oxide (IV)], MnO3 [manganese oxide (VI)], and Mn2O7 [manganese oxide (VII)].

[0124] In certain embodiments, the one or more additives include a pseudocapacitor additive, and the pseudocapacitor additive comprises about 0.1 wt % to about 90 wt % of the combined net weight of the anode and cathode.

[0125] In certain embodiments, the one or more additives include a pseudocapacitor additive, wherein the pseudocapacitor additive is in the form of a thin film, nanostructures, microstructures, particles, or a combination thereof.

[0126] In certain embodiments, the one or more additives include a dielectric additive, the dielectric additive comprising about 0.1% to about 90% by weight of the combined net weight of the anode and cathode. In certain embodiments, the concentration of the additive is determined based on the end use application. For example, a high energy density battery-capacitor hybrid may have a dielectric additive concentration of less than 30% by weight. Meanwhile, a high power battery-capacitor hybrid may have a dielectric additive concentration of more than 50% by weight.

[0127] In certain embodiments, the one or more additives include a dielectric additive, wherein the dielectric additive is in the form of a thin film, nanostructures, microstructures, particles, or a combination thereof.

[0128] In certain embodiments, the anode comprises a first aluminum layer comprising one or more members selected from the group consisting of aluminum, an aluminum alloy, or an aluminum composite, a dielectric layer comprising a dielectric additive, a second aluminum layer comprising one or more members selected from the group consisting of aluminum, an aluminum alloy, or an aluminum composite, and a protective oxide layer.

[0129] In one particular embodiment, the first aluminum layer comprises aluminum foil.

[0130] In certain embodiments, the dielectric layer comprises a metal oxide. In certain embodiments, the metal oxide is zirconium oxide. In certain embodiments, the zirconium oxide is in the form of a thin film.

[0131] In one particular embodiment, the second aluminum layer comprises a thin film of aluminum foil.

[0132] In certain embodiments, the dielectric additive is aluminum oxide, hi certain embodiments, the aluminum oxide is in the form of a thin film.

[0133] In certain embodiments, the cathode comprises a stainless steel substrate, an aluminum layer comprising one or more members selected from the group consisting of aluminum, an aluminum alloy, or an aluminum composite, a dielectric layer comprising a dielectric additive, and a manganese oxide layer. In certain embodiments, the dielectric additive comprises a metal oxide. In certain embodiments, the metal oxide is zirconium oxide.

[0134] In certain embodiments, the anode and cathode are arranged to facilitate transport of aluminum ions from the second aluminum layer of the anode to the cathode.

[0135] In certain embodiments, the anode and cathode are arranged to promote transport of aluminum ions from the manganese oxide layer of the cathode to the second aluminum layer of the anode during charging.

[0136] The drawings are presented herein for purposes of illustration and not for purposes of limitation. The above and other objects, aspects, features and advantages of the present disclosure will become more apparent and may be better understood by referring to the following description in connection with the accompanying drawings, in which: In an embodiment of the present invention, for example, the following items are provided: (Item 1) an anode comprising one or more members selected from the group consisting of aluminum, aluminum alloys and aluminum composites (e.g., the anode described in any one of items 102 to 144); an aqueous electrolyte (e.g. an electrolyte according to any one of items 153 to 157), and A cathode comprising one or more members selected from the group consisting of manganese oxide, aluminosilicate, and polymer (e.g., the cathode described in any one of items 28 to 89). An aluminum ion battery comprising: (Item 2) The anode, the aqueous electrolyte, and the cathode are connected to each other to form a cathode. 3+ Item 2. The aluminum ion battery of item 1, wherein the aluminum ion battery is arranged to promote transport of (Item 3) 3. The aluminum ion battery according to item 1 or 2, wherein the battery has a charge storage capacity in the range of 25 mAh / g to 500 mAh / g (units are milliamp-hours per gram of active material in the battery). (Item 4) Item 2. The aluminum ion battery of any one of the preceding items, wherein the battery draws charge at a rate ranging from 1C to 0.01C (a rate of nC is defined as charge or discharge in 1 / n hours). (Item 5) The aluminum ion battery of any one of the preceding items, which provides stable cycling performance (e.g., where stable cycling performance means having a repeatable voltage profile with no or substantially no noise that may contribute to pulverization, delamination, corrosion or other side reactions) over at least 100 (e.g., at least 150) charge-discharge steps (e.g., where one cycle is equal to one charge and one discharge) (e.g., where the aluminum ion battery has a minimum cycle life of 50 cycles, 100 cycles, 150 cycles or 200 cycles). (Item 6) When an external load is applied, aluminum ions (Al +3 ) is released from an electrode (e.g., the cathode or the anode) into the aqueous electrolyte. (Item 7) The released Al +3 7. The aluminum ion battery of claim 6, wherein ions migrate through the aqueous electrolyte, a membrane separator, and to an opposing electrode (e.g., the anode or the cathode, respectively) (e.g., where the electrode is 0.001 to 100% aluminum by weight). (Item 8) The released Al in or on the opposite electrode. +3 8. The aluminum ion battery of claim 7, wherein the ions intercalate and / or otherwise react with one or more members selected from the group consisting of: (i) oxygen-containing moieties, such as (a) oxides, (b) hydroxides, (c) nitrates, (d) sulfates, (e) acetates, (f) phosphates, (g) chlorates, (h) bromates, or (i) iodates; (ii) halogen-containing moieties, such as (a) chlorides, (b) fluorides, (c) bromides, (d) iodides; and (iii) metal moieties, such as (a) manganese, (b) sodium, (c) lithium, (d) aluminum, (e) potassium, (f) calcium, or (g) magnesium, thereby forming a stable aluminum phase within or on the surface of the counter electrode structure. (Item 9) Item 9. The aluminum ion battery of item 8, wherein one or more transition metals in the counter electrode change oxidation state, thereby stabilizing the structure of the electrode. (Item 10) The released Al +3 Ions are added to the aqueous electrolyte (e.g., the Al +3 Charge carriers containing ions, e.g. Al(OH)4 - 8. The aluminum ion battery according to item 7, wherein the aluminum ion battery passes through the membrane separator, migrates to the opposite electrode, and is stored on the surface of the opposite electrode. (Item 11) The released Al 3+ Item 11. The aluminum ion battery of item 10, wherein ions are stored on the surface as dielectric charges. (Item 12) When an external load is applied, aluminum ions (Al +3 ) is released from an electrode (e.g., the cathode or the anode) into the aqueous electrolyte, and the released Al +3 The released Al ions react with ions present in the aqueous electrolyte and pass through the aqueous electrolyte (e.g., through a membrane separator) to a counter electrode (e.g., the anode or the cathode, respectively) (e.g., where the electrode is 0.001 to 100 wt % aluminum). 3+ 6. The aluminum ion battery according to any one of the preceding claims, wherein the aluminum ion battery forms a transport phase (e.g., a stable transport phase) for transporting charge carriers (including (Item 13) The released Al +3 OH ions are present in the aqueous electrolyte -1 It reacts with ions to form Al(OH)4 -1 Forming charge carriers (e.g., where Al(OH) -1 The charge carriers are Al +3 13. The aluminum ion battery of claim 12, wherein said first and second electrodes are connected to said first and second electrodes, and said first and second electrodes are connected to said first and second electrodes. (Item 14) Item 14. The aluminum ion battery of item 13, wherein at least a portion of the charge carriers undergo one or both of the following after transport to the counter electrode: (i) dissociation to form individual anions and cations; and (ii) remaining in a stable charge carrier phase. (Item 15) At least a portion of the charge carriers dissociate after transport to the counter electrode to form individual anions and cations, and the individual anions and / or cations are converted to (i) at the counter electrode: (I) oxygen-containing moieties, such as (a) oxides, (b) hydroxides, (c) nitrates, (d) sulfates, (e) acetates, (f) phosphates, (g) chlorates, (h) bromates, or (i) iodates; (II) halogen-containing moieties, such as (a) chlorides, (b) fluorides, (c) bromides, (d) iodides; and (III) metal moieties, such as Item 15. The aluminum ion battery of item 14, wherein the aluminum ion undergoes one or more processes selected from the group consisting of: (a) manganese, (b) sodium, (c) lithium, (d) aluminum, (e) potassium, (f) calcium, or (g) magnesium, intercalating and / or reacting with (e.g., forming a stable phase within or on the structure of the counter electrode), and (ii) being stored on the surface of the counter electrode (e.g., as a dielectric charge). (Item 16) Item 15. The aluminum ion battery of item 14, wherein at least a portion of the charge carriers remain in a stable charge carrier phase after transport to the counter electrode, and the charge carriers undergo one or both of the following at the counter electrode: (i) intercalation within the structure of the counter electrode; and (ii) a transition to a non-ionic stable phase comprising aluminum and one or more members selected from the group consisting of oxide, hydroxide, chloride, nitrate, sulfate, phosphate, lithium, sodium, potassium, and magnesium, and intercalation within the counter electrode structure and / or reaction of the non-ionic stable phase. (Item 17) The following mechanisms (A) and (B): (A) When an external load is applied, aluminum ions (Al +3 ) is released from an electrode (e.g., the cathode or the anode) into the aqueous electrolyte, and the released Al +3 The ions are added to the aqueous electrolyte [e.g., charge carriers (e.g., Al(OH)4 -) through a membrane separator to a counter electrode (e.g., the anode or the cathode, respectively) (e.g., where the electrode is 0.001 to 100 wt. % aluminum) and oxidizes the Al +3 the ions intercalate and / or otherwise react with one or more members selected from the group consisting of: (i) oxygen-containing moieties, e.g., (a) oxides, (b) hydroxides, (c) nitrates, (d) sulfates, (e) acetates, (f) phosphates, (g) chlorates, (h) bromates, or (i) iodates; (ii) halogen-containing moieties, e.g., (a) chlorides, (b) fluorides, (c) bromides, (d) iodides; and (iii) metal moieties, e.g., (a) manganese, (b) sodium, (c) lithium, (d) aluminum, (e) potassium, (f) calcium, or (g) magnesium, thereby forming a stable aluminum phase within or on said counter electrode structure; And (C) When an external load is applied, aluminum ions (Al +3 ) is released from an electrode (e.g., the cathode or the anode) into the aqueous electrolyte, and the released Al +3 ions react with ions present in the aqueous electrolyte to form a transport phase (e.g., a stable transport phase) for transporting ions (e.g., charge carriers) through the aqueous electrolyte (e.g., and through a membrane separator) to an opposing electrode (e.g., the anode or the cathode, respectively) (e.g., where the electrode is 0.001 to 100 wt % aluminum); 6. The aluminum ion battery according to any one of items 1 to 5, wherein either or both of the following occurs: (Item 18) When an external load is applied, aluminum ions (Al +3 ) is released from an electrode (e.g., the cathode or the anode) into the aqueous electrolyte, and the released Al +3 The ions are added to the aqueous electrolyte [e.g., charge carriers (e.g., Al(OH)4 -6. The aluminum ion battery according to items 1 to 5, wherein the charged electrolyte is 0.001 to 100% by weight aluminum, passes through a membrane separator, migrates to the counter electrode (e.g., the anode or the cathode, respectively) (e.g., where the electrode is 0.001 to 100% by weight aluminum), and is stored on the surface of the counter electrode (e.g., as a dielectric charge). (Item 19) The aluminum-ion battery of any one of the preceding items, wherein the anode comprises an aluminum alloy containing one or more non-aluminum members selected from the group consisting of sodium, lithium, calcium, potassium, magnesium, zirconium, lead, bismuth, titanium, vanadium, tin, copper, silver, gold, platinum, mercury, scandium, sulfur, silicon, iron, silicon, nickel, manganese, chromium, cerium, germanium, gallium, thallium, hafnium, indium, rhodium, ruthenium, molybdenum, palladium, strontium, yttrium, barium, cadmium, iridium, tantalum, cobalt, tellurium, antimony, arsenic, tungsten, and selenium. (Item 20) 2. The aluminum-ion battery of any one of the preceding items, wherein the aqueous electrolyte comprises one or more non-aluminum members selected from the group consisting of sodium, lithium, calcium, potassium, nickel, cobalt, iron, manganese, vanadium, titanium, tin, zinc, copper, and magnesium. (Item 21) 2. The aluminum-ion battery of any one of the preceding items, wherein the cathode comprises a sheet of one or more members selected from the group consisting of manganese oxides, aluminosilicates, and polymers. (Item 22) 22. The aluminum-ion battery of claim 21, wherein the cathode comprises non-aluminum guest ions and / or molecules stored between the sheets (e.g., the sheets comprise manganese oxide and / or aluminosilicate and / or polymer), and the guest ions and / or molecules comprise one or more members selected from the group consisting of sodium, lithium, calcium, potassium, rubidium, cesium, beryllium, strontium, barium, magnesium, nickel, zinc, bismuth, cobalt, copper, and protons. (Item 23) The aluminum-ion battery of any one of the preceding items, wherein at least one of the cathode, the anode and the aqueous electrolyte comprises non-aluminum ions that participate in an electrochemical reaction upon application of an external load (e.g., charging or discharging) and / or by an ion exchange process between the cathode and the electrolyte and / or between the anode and the electrolyte and / or between the cathode and the anode. (Item 24) 2. The aluminum-ion battery of any one of the preceding items, wherein at least one of the cathode, the anode, and the aqueous electrolyte (e.g., at least one, at least two, or all three of the cathode, the anode, and the aqueous electrolyte) does not contain cobalt. (Item 25) The aluminum ion battery of any one of the preceding items, wherein at least one of the cathode, the anode, and the aqueous electrolyte (e.g., at least one, at least two, or all three of the cathode, the anode, and the aqueous electrolyte) is non-toxic. (Item 26) The aluminum ion battery of any one of the preceding items, wherein at least one of the cathode, the anode, and the aqueous electrolyte (e.g., at least one, at least two, or all three of the cathode, the anode, and the aqueous electrolyte) is non-flammable. (Item 27) The aluminum-ion battery of any one of the preceding items, wherein at least one of the cathode, the anode, and the aqueous electrolyte (e.g., at least one, at least two, or all three of the cathode, the anode, and the aqueous electrolyte) does not contain any heavy metals (e.g., does not contain any of antimony, cerium, dysprosium, erbium, europium, gadolinium, gallium, germanium, holmium, indium, lanthanum, lutetium, neodymium, niobium, praseodymium, samarium, tantalum, terbium, thulium, tungsten, uranium, ytterbium, iridium, osmium, palladium, platinum, rhodium, ruthenium, chromium, cobalt, copper, iron, lead, molybdenum, nickel, tin, and zinc). (Item 28) a current collector (e.g., a conductive substrate); and One or more structures (e.g., one or more thin films or particles), each comprising one or more members selected from the group consisting of manganese oxide, aluminosilicates (e.g., layered aluminosilicates), and aluminum-receptive polymers. 28. A cathode for an ion battery (e.g. an aluminum ion battery or an aqueous aluminum ion battery, e.g. a battery according to any one of items 1 to 27), comprising: the one or more structures are disposed on (e.g. directly on) the current collector and are in electrical contact with the current collector (e.g. where the thickness of the cathode is from 10 nm to 1 mm, e.g. from 10 μm to 100 μm, e.g. from 1 μm to 10 μm, e.g. from 1 μm to 5 μm, e.g. with a tolerance of ±20% or better); Cathode. (Item 29) Item 29. The cathode of item 28, wherein the one or more structures each comprise manganese oxide. (Item 30) 30. The cathode of claim 28 or 29, wherein the one or more structures comprise a plurality of sheets comprising (e.g., consisting of, consisting essentially of, or including) at least 20% by weight (e.g., 20% to 40% by weight, such as 40% to 60% by weight, such as 60% to 80% by weight, such as at least 80% by weight), with an inter-sheet (e.g., inter-layer) separation distance (e.g., d-layer spacing of adjacent

[0001] manganese oxide sheets) of 1 Angstrom or more (e.g., 5 Angstroms or more) (e.g., 10 Angstroms or more) (e.g., and up to 100 Angstroms). (Item 31) 31. The cathode of any one of items 28 to 30, wherein the one or more structures include a spinel structure, a tunnel structure, a sandwich structure, an encapsulation structure, a capture structure, or a combination thereof. (Item 32) 32. The cathode of any one of claims 28 to 31, wherein the one or more structures include a turbostratic structure. (Item 33) 33. The cathode of any one of items 28 to 32, wherein the one or more structures include one or a combination of lithiophorite structures (e.g., comprising alternating sheets of manganese oxide and aluminum hydroxide) (e.g., where the one or more structures include manganese oxide sheets having dimensions in the range of 10 nm to 500 micrometers), phyllomanganate structures (e.g., comprising metal oxides that are hydrated), and tectomanganate structures, one or more of which structures may be pristine or disordered and may include vacancies. (Item 34) The one or more structures include (e.g., are) particles, and at least 80% of the particles of the cathode have a molecular weight within the following range (e.g., with a tolerance of ±20% or better): (i) 50 nm or greater (e.g., at least 80% of the particles have dimensions between 40 and 60 nm or greater); (ii) 100 nm to 250 nm (e.g., at least 80% of the particles have a dimension between 80-120 nm and 200-300 nm); (iii) 500 nm to 5 micrometers (e.g., at least 80% of the particles have a dimension between 400-600 nm and 4-6 micrometers); (iv) 1 micrometer to 10 micrometers; (v) 5 micrometers to 30 micrometers having a dimension (e.g., diameter) within (at least) one of the ranges 34. The cathode according to any one of items 28 to 33. (Item 35) The one or more structures include sheets (e.g., are sheet materials), and at least 80% of the sheets of the cathode have a thickness within the following range (e.g., with a tolerance of ±20% or better): (i) 50 nm or more (e.g., at least 80% of the sheet has dimensions of 40-60 nm or more); (ii) 100 nm to 250 nm (e.g., at least 80% of the sheet has a dimension between 80 to 120 nm and 200 to 300 nm); (iii) 500 nm to 5 micrometers (e.g., at least 80% of the sheet has a dimension between 400-600 nm and 4-6 micrometers); (iv) 1 micrometer to 10 micrometers; (v) 5 micrometers to 30 micrometers having a dimension (e.g., thickness) within (at least) one of the ranges; 35. The cathode according to any one of items 28 to 34. (Item 36) 36. The cathode of any one of claims 29 to 35, comprising one or more non-aluminum guest ions stored between the manganese oxide sheets. (Item 37) 37. The cathode of any one of items 29 to 36, comprising one or more non-aluminum guest ions disposed at sites (e.g., interstitial sites) and / or vacancies of the manganese oxide crystal lattice. (Item 38) Item 38. The cathode of item 36 or item 37, wherein the guest ion comprises one or more members selected from the group consisting of protons, sodium, lithium, potassium, zinc, bismuth, copper, lead, cobalt, nickel, calcium, potassium, magnesium, hydrogen, hydronium, hydroxide, oxide-hydroxide, sulfate, sulfide, nitride, nitrate, phosphide, phosphate, acetate, polyoxometalates (POMs) and pillar-forming agents (e.g., aliphatic and / or aromatic compounds). (Item 39) 39. The cathode of any one of items 28 to 38, comprising one or more aluminum guest ions stored between the manganese oxide sheets. (Item 40) 40. The cathode of any one of claims 29 to 39, comprising one or more non-aluminum guest molecules stored between the manganese oxide sheets. (Item 41) 41. The cathode of any one of items 29 to 40, comprising one or more non-aluminum guest ions disposed at sites (e.g., interstitial sites) and / or vacancies of the manganese oxide crystal lattice. (Item 42) 42. The cathode of claim 40 or 41, wherein the guest molecules comprise one or more members selected from the group consisting of oxides, hydroxides, oxide-hydroxides, sulfides, sulfates, nitrides, nitrates, chlorides, chlorates, phosphates, and phosphides. (Item 43) 43. The cathode of any one of claims 40 to 42, wherein the guest molecules comprise one or more phosphates. (Item 44) Item 44. The cathode of item 43, wherein the one or more phosphates are members selected from the group consisting of sodium phosphates, lithium phosphates, potassium phosphates, calcium phosphates, magnesium phosphates and manganese phosphates. (Item 45) 45. The cathode of any one of claims 29 to 44, comprising phosphates of aluminum stored between manganese oxide sheets or disposed in sites (e.g., interstitial sites) and / or vacancies of the manganese oxide crystal lattice. (Item 46) 46. ​​The cathode of any one of claims 29 to 45, comprising one or more columnar forming agents stored between the manganese oxide sheets. (Item 47) Item 47. The cathode of item 46, wherein the one or more pillar-forming agents comprise one or more members selected from the group consisting of polyoxometalates (POMs), amphiphilic molecules, polar organic molecules, and non-polar organic molecules. (Item 48) 48. The cathode of any one of claims 28 to 47, wherein the one or more structures each comprise an aluminum-receptive polymer. (Item 49) Item 49. The cathode of item 48, wherein the aluminum-receptive polymer comprises a member selected from the group consisting of alizarins, alginates, amidinates, quinones, quinolones, hydroxyquinones, crown ethers, and hydroxyquinolines. (Item 50) 50. The cathode of claim 48 or 49, wherein the aluminum-receptive polymer is present as a complex with one or more members selected from the group consisting of lithium, sodium, lead, chromium, copper, bismuth, cobalt, zinc, potassium, calcium, magnesium, manganese, iron, cobalt, titanium, tin, vanadium and tungsten, e.g., wherein the complex participates in an electrochemical reaction by an ion exchange process with aluminum ions from the electrolyte and / or aluminum source electrode (e.g., anode) in a battery during charging / discharging. (Item 51) 51. The cathode of any one of items 28 to 50, wherein the one or more structures comprise particles (e.g., comprising manganese oxide) (e.g., the particles are nanoparticles, microparticles, or a combination of nanoparticles and microparticles) (e.g., the particles are spheres having a diameter in the range of 10 nm to 500 micrometers). (Item 52) 52. The cathode of claim 51 comprising a plurality of conductive posts protruding from the current collector, the particles being disposed on the plurality of conductive posts. (Item 53) 51. The cathode of any one of items 28 to 50, wherein the one or more structures comprise a thin film (e.g., a patterned thin film). (Item 54) Item 54. The cathode according to item 53, comprising a plurality of conductive pillars protruding from the current collector, and the thin film is disposed on the plurality of conductive pillars (e.g., and the thin film is patterned to correspond to the distribution of the pillars on the current collector). (Item 55) 51. The cathode of any one of items 28 to 50, wherein the current collector is porous (e.g., a mesh, a foam, a plurality of interconnected fibers, a plurality of tubes and sheets, a plurality of nanotubes, or a graphene-like structure). (Item 56) Item 56. The cathode of item 55, wherein the one or more structures are disposed (e.g., coated) within or on a pore surface of the current collector. (Item 57) 55. The cathode according to any one of items 28 to 54, wherein the one or more structures are coated on one or more porous carbon structures. (Item 58) Item 58. The cathode of item 57, wherein the one or more porous carbon structures comprise one or more members selected from the group consisting of carbon fibers, nanofibers, carbon nanotubes (CNTs), fullerenes, graphene, partially reduced graphene oxide, aerogels, xerogels, and interpenetrating multiphase materials. (Item 59) 59. The cathode of any one of items 28 to 58, further comprising a binder (e.g., a polymeric binder) in contact with the current collector to physically maintain (e.g., adhere) the one or more structures together. (Item 60) Item 60. The cathode of item 59, wherein the binder is selected from the group consisting of carboxymethyl cellulose, styrene butadiene rubber, polyvinyl alcohol, alginate, polypropylene, polytetrafluoroethylene, polyvinylidene difluoride, polyaniline, epoxy, rubber, polyacrylic acid, and polyvinyl propylene. (Item 61) 60. The cathode of claim 59, wherein the binder is selected from the group consisting of alginate, PVDF, PTFE, polyaniline, epoxy, carboxymethyl cellulose, rubber, styrene butadiene rubber, polyacrylic acid, polyvinyl alcohol and polyvinyl propylene. (Item 62) 62. The cathode of any one of claims 59 to 61, wherein the binder is pretreated with one or more species of multivalent ions. (Item 63) Item 63. The cathode of item 62, wherein the one or more species of multivalent ions comprise one or more ions of manganese, magnesium, calcium, zinc, barium, and aluminum. (Item 64) 64. The cathode of any one of claims 59 to 63, wherein the binder is pretreated with one or more species of univalent ions. (Item 65) Item 65. The cathode of item 64, wherein the one or more species of monovalent ions comprise one or more ions of lithium, sodium, and potassium. (Item 66) 66. The cathode of any one of items 59 to 65, wherein the binder comprises ions of one or more members selected from the group consisting of sodium, potassium, magnesium, manganese, aluminum, calcium, barium, strontium, and zinc. (Item 67) 67. The cathode of any one of items 59 to 66, wherein the binder is deposited from a solution comprising one or more of water, n-methylpyrrolidone, ketones, glycols, dimethylsulfoxide (DMSO) and esters, and optionally a co-solvent selected from the group consisting of water, n-methylpyrrolidone, ketones, glycols, DMSO and esters. (Item 68) 55. The cathode of any one of claims 28 to 54, wherein the cathode is binder-free (e.g., wherein the one or more structures are formed on the current collector using one or more of chemical vapor deposition, physical vapor deposition, atomic layer deposition, spin-coating, and electrochemical deposition). (Item 69) 69. The cathode of any one of items 28 to 68, further comprising a conductive additive (e.g., a carbon-containing additive) in electrical contact with the current collector and the one or more structures. (Item 70) 70. The cathode of any one of items 28 to 69, wherein the current collector comprises one or more members selected from the group consisting of stainless steel, copper, carbon, silver, gold, platinum, tin, vanadium, zinc, tin oxide, indium, indium tin oxide (ITO), aluminum, nickel, tungsten, chromium and titanium. (Item 71) 71. The cathode of any one of items 28 to 70, wherein the current collector comprises a coating of an adhesion promoter, a conductivity promoter, or both an adhesion promoter and a conductivity promoter. (Item 72) 72. The cathode of any one of items 28 to 71, wherein the current collector comprises one or more coatings of carbon, metal (e.g., tin, zinc, aluminum, chromium, copper, nickel, iron, zirconium, silver, gold, platinum), metal oxide (e.g., indium tin oxide, tin oxide, titanium oxide, vanadium oxide, zirconium oxide) or polymer (e.g., PEDOT, PAN, parylene), wherein the coating acts as one or more of an adhesion promoter, an electronic conductivity promoter and an ionic conductivity inhibitor. (Item 73) 24. A cathode for an aluminum-ion battery (e.g. an aluminum-ion battery or an aqueous aluminum-ion battery, e.g. a battery according to any one of items 1 to 23), comprising The cathode is made by a method comprising depositing a quantity of a solution onto a current collector, the solution comprising: one or more members selected from the group consisting of manganese oxide, layered aluminosilicates, and aluminum-receptive polymers; and One or more solvents (e.g., selected from the group consisting of water, N-methylpyrrolidone, and ethanol) a cathode. (Item 74) The one or more members are reacting one or more manganese oxide precursors with a base in the presence of an oxygen source (e.g., and optionally an oxidant chemical catalyst); and Optionally, hydrothermally treating the manganese oxide after the reaction step. and a manganese oxide produced by a process comprising: the one or more precursors are each selected from the group consisting of manganese salts, lithium salts, sodium salts, magnesium salts, nickel, zinc, aluminum, inorganic acids, and permanganates; wherein the manganese salt comprises one or more of sulfate, (i) nitrate, (ii) chloride, (iii) acetate, (iv) phosphate, (v) perchlorate, (vi) fluoride, and (vii) bromide; the permanganate salt comprises one or more of: (i) sodium; and (ii) potassium; 74. The cathode according to item 73. (Item 75) Item 75. The cathode of item 74, wherein the base comprises lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium hydroxide. (Item 76) 76. The cathode of claim 74 or 75, wherein the oxygen source is dissolved oxygen gas or a peroxide (e.g., hydrogen peroxide). (Item 77) 77. The cathode of any one of items 73 to 76, wherein the solution further comprises one or more of a binder (e.g., a polymeric binder, e.g., a polymeric binder permeable by an electrolyte solution comprising one or more aluminum salts) and a conductive additive (e.g., a carbon-containing additive). (Item 78) 78. The cathode of any one of claims 73 to 77, wherein the depositing step comprises doctor blading, spin coating, comma coating or slot-die coating. (Item 79) 80. The cathode of any one of claims 73 to 78, wherein the method further comprises the step of calendering the deposited solution and the current collector. (Item 80) 80. The cathode of any one of claims 28 to 79, wherein the cathode comprises manganese oxide in one or more phases, the one or more phases being selected from the group consisting of alpha phase, beta phase, lambda phase, ramsdellite phase, amorphous phase, gamma phase, delta phase and epsilon phase. (Item 81) Item 81. The cathode of item 80, wherein the one or more phases are two or more phases (e.g., three or more phases). (Item 82) Item 82. The cathode of item 81, wherein a predominant one of the two or more phases is at least 40% by weight of the cathode and all remaining of the two or more phases are 50% by weight or less of the cathode. (Item 83) 83. The cathode of any one of items 80 to 82, wherein the manganese oxide is configured to undergo at least one phase change during charging and discharging (e.g., ion insertion and removal) of the cathode. (Item 84) 84. The cathode according to any one of items 28 to 83, wherein the cathode comprises a manganese oxide having a layered structure (e.g., a phyllomanganate), a tunnel structure (e.g., a tectomanganate), a spinel structure, a ramsdellite structure or an amorphous structure. (Item 85) 85. The cathode according to any one of items 28 to 84, wherein the cathode comprises a manganese oxide, wherein the manganese in the manganese oxide has one or more oxidation states selected from the group consisting of Mn(II), Mn(II-x), Mn(III), Mn(III-x), Mn(IV), Mn(IV-x), Mn(V), Mn(Vx), Mn(VI), Mn(VI-x), Mn(VII) and Mn(VII-x), where x is between 0 and 1. (Item 86) 86. The cathode of any one of items 28 to 85, wherein the one or more structures comprise manganese oxide, and the manganese oxide is predominantly (e.g., at least 70% by weight, at least 80% by weight, or at least 90% by weight) delta phase manganese oxide. (Item 87) 28. A cathode for an aluminum-ion battery (e.g. an aluminum-ion battery or an aqueous aluminum-ion battery, e.g. a battery according to any one of items 1 to 27), co-depositing manganese oxide and one or more sacrificial materials on a current collector; and Removing the one or more sacrificial materials. A cathode made by a method comprising: (Item 88) Item 88. The cathode of item 87, wherein the one or more sacrificial materials comprise one or more members selected from the group consisting of alizarin, amidinates, quinones, alginates, zeolites, quinolones, hydroxyquinones, hydroxyquinolines, silicon, copper, cobalt, chromium, nickel, iron, oxides, hydroxides, sulfates, nitrates, and phosphates (e.g., of silicon, copper, cobalt, chromium, nickel, or iron). (Item 89) Item 89. The cathode of item 87 or item 88, wherein the simultaneously depositing steps include simultaneously thermal evaporation, simultaneously sputtering, coextrusion or simultaneously coating (e.g., spin-coating, doctor blading or slot-die coating). (Item 90) 28. A method for producing a cathode for an aluminum-ion battery (e.g. an aluminum-ion battery or an aqueous aluminum-ion battery, e.g. a battery according to any one of items 1 to 27), comprising: depositing a quantity of a solution onto a current collector, wherein the solution comprises: one or more members selected from the group consisting of manganese oxide, layered aluminosilicates, and aluminum-receptive polymers; and One or more solvents (e.g., selected from the group consisting of water, N-methylpyrrolidone, and ethanol) A method comprising: (Item 91) reacting one or more manganese oxide precursors with a base in the presence of an oxygen source (e.g., and optionally an oxidant chemical catalyst); and Optionally, hydrothermally treating the manganese oxide after the reaction step. producing manganese oxide by the one or more precursors are each selected from the group consisting of manganese salts, lithium salts, sodium salts, magnesium salts, nickel, zinc, aluminum, inorganic acids, and permanganates; wherein the manganese salt comprises one or more of sulfate, (i) nitrate, (ii) chloride, (iii) acetate, (iv) phosphate, (v) perchlorate, (vi) fluoride, and (vii) bromide; the permanganate salt comprises one or more of: (i) sodium; and (ii) potassium; Item 91. The method according to item 90. (Item 92) 92. The method of claim 91, wherein the base comprises one or more of lithium hydroxide, sodium hydroxide, potassium hydroxide, and calcium hydroxide. (Item 93) 93. The method of claim 91 or 92, wherein the oxygen source is dissolved oxygen gas or a peroxide (e.g., hydrogen peroxide). (Item 94) 94. The method of any one of items 90 to 93, wherein the solution further comprises one or more of a binder (e.g., a polymeric binder, e.g., a polymeric binder permeable by an electrolyte solution comprising one or more aluminum salts) and a conductive additive (e.g., a carbon-containing additive). (Item 95) 96. The method of any one of items 90 to 95, wherein the depositing step comprises doctor blading, spin coating, comma coating or slot-die coating. (Item 96) 96. The method of any one of claims 90 to 95, further comprising the step of calendering the deposited solution and the current collector. (Item 97) 97. The method of any one of items 90 to 96, wherein the solution comprises one or more members selected from the group consisting of water, n-methylpyrrolidone, ketones, glycols, dimethylsulfoxide (DMSO) and esters, and optionally a co-solvent selected from the group consisting of water, n-methylpyrrolidone, ketones, glycols, DMSO and esters. (Item 98) 98. The method of any one of items 90 to 97, wherein the solution comprises (i) a binder selected from the group consisting of alginate, PVDF, PTFE, polyaniline, epoxy, carboxymethyl cellulose, rubber, styrene butadiene rubber, polyacrylic acid, polyvinyl alcohol, and polyvinyl propylene, and (ii) an ionic species selected from the group consisting of sodium, lithium, potassium, magnesium, manganese, aluminum, calcium, barium, strontium, and zinc. (Item 99) 28. A method for producing a cathode for an aluminum-ion battery (e.g. an aluminum-ion battery or an aqueous aluminum-ion battery, e.g. a battery according to any one of items 1 to 27), comprising the steps of: co-depositing manganese oxide and one or more sacrificial materials on a current collector; and Removing the one or more sacrificial materials. A method comprising: (Item 100) 99. The method of claim 99, wherein the one or more sacrificial materials comprise one or more members selected from the group consisting of alizarin, amidinates, quinones, alginates, zeolites, quinolones, hydroxyquinones, hydroxyquinolines, silicon, copper, cobalt, chromium, nickel, iron, oxides, hydroxides, sulfates, nitrates, and phosphates (e.g., of silicon, copper, cobalt, chromium, nickel, or iron). (Item 101) Item 99. The method of item 100, wherein the simultaneously depositing step comprises one or more members selected from the group consisting of simultaneous thermal evaporation, simultaneous sputtering, coextrusion or simultaneous coating (e.g., spin-coating, doctor blading or slot-die coating). (Item 102) 28. An anode for an ion battery (e.g. an aluminum ion battery or an aqueous aluminum ion battery, e.g. a battery according to any one of items 1 to 27) comprising one or more structures (e.g. one or more foils, thin films or particles), an anode, wherein the one or more structures each comprise one or more aluminum-containing members selected from the group consisting of aluminum, aluminum alloys and aluminum composites, and the anode is 0.001% to 100% by weight aluminum (e.g., 70% to 100% by weight aluminum, e.g., at least 95% by weight aluminum) (e.g., where the anode comprises at least 95% by weight aluminum and up to 5% by weight non-aluminum species, e.g., the non-aluminum species comprising one or more alloying metals and / or oxides intentionally incorporated into the anode) (e.g., where the purity of the aluminum is at least 99.9 atomic %, such as at least 99.99 atomic %, e.g., 99.99 atomic % to 99.99999 atomic %, e.g., where impurities are present in the range of 0.01 atomic % to 0.00001 atomic %, e.g., where the impurities comprise iron and / or sodium and / or magnesium and / or silica, e.g., impurities commonly found in metal foils). (Item 103) Item 103. The anode of item 102, wherein the anode comprises a surface layer comprising (e.g. consisting of) one or more of aluminum, oxygen, hydrogen, nitrogen, lithium manganese and carbon. (Item 104) 104. The anode of claim 102 or 103, wherein each of the one or more structures comprises an aluminum alloy or mixture containing one or more non-aluminum members selected from the group consisting of sodium, lithium, calcium, potassium, magnesium, zirconium, lead, bismuth, titanium, vanadium, tin, copper, silver, gold, platinum, mercury, scandium, sulfur, silicon, iron, silicon, nickel, manganese, chromium, cerium, germanium, gallium, thallium, hafnium, indium, rhodium, ruthenium, molybdenum, palladium, strontium, yttrium, barium, cadmium, iridium, tantalum, cobalt, tellurium, antimony, arsenic, tungsten and selenium. (Item 105) 105. The anode of any one of items 102 to 104, comprising a film comprising the one or more structures, each of the one or more structures being a particle (e.g., where the particle has a diameter in the range of 10 nm to 100 micrometers) (e.g., where the film has a thickness in the range of 10 nm to 1 mm). (Item 106) At least 80% of the particles of the anode have a particle size within the following range (e.g., with a tolerance of ±20% or better): (i) 50 nm or greater (e.g., at least 80% of the particles have dimensions between 40 and 60 nm or greater); (ii) 100 nm to 500 nm (e.g., at least 80% of the particles have a dimension between 80-120 nm and 400-600 nm); (iii) 250 nm to 1 micrometer (e.g., at least 80% of the particles have a dimension between 200-300 nm and 0.8-1.2 micrometers); (iv) 500 nm to 5 micrometers (e.g., at least 80% of the particles have a dimension between 400-600 nm and 4-6 micrometers); (v) 1 micrometer to 10 micrometers; (vi) 5 micrometers to 25 micrometers (vii) 10 micrometers to 50 micrometers, and (viii) 50 micrometers to 100 micrometers having a dimension (e.g., diameter) within (at least) one of the ranges Item 106. The anode according to item 105. (Item 107) 107. The anode of claim 105 or 106, wherein the film further comprises a polymer binder in physical contact with the plurality of particles, the polymer binder being selected from the group consisting of carboxymethyl cellulose, styrene butadiene rubber, polyvinyl alcohol, polypropylene, and polytetrafluoroethylene. (Item 108) 108. The anode of any one of claims 105 to 107, wherein the film further comprises one or more conductive carbon additives. (Item 109) 109. The anode of any one of claims 102 to 108, wherein the one or more structures comprise a thin film having a thickness in the range of 1 nm to 1 mm. (Item 110) Thin films may be formed within the following ranges (e.g., with tolerances of ±20% or better): (i) 50 nm or more (e.g., a thickness of 40 to 60 nm or more); (ii) 100 nm to 500 nm (e.g., a thickness between 80 to 120 nm and 400 to 600 nm); (iii) 250 nm to 1 micrometer (e.g., a thickness between 200-300 nm and 0.8-1.2 micrometers); (iv) 500 nm to 5 micrometers (e.g., a thickness between 400-600 nm and 4-6 micrometers); (v) 1 micrometer to 10 micrometers; (vi) 5 micrometers to 25 micrometers (vii) 10 micrometers to 50 micrometers, and (viii) 50 micrometers to 100 micrometers having a thickness within (at least) one of the ranges Item 109. The anode according to item 109. (Item 111) 111. The anode of claim 109 or 110, wherein the thin film is coated on a current collector (e.g., a conductive substrate) (e.g., wherein the conductive substrate comprises one or more members selected from the group consisting of carbon, steel, nickel, iron, zinc, aluminum, titanium, tungsten, copper, silver, tin, indium and chromium). (Item 112) Item 111. The anode according to item 109 or 110, wherein the thin film is coated on a current collector (e.g., a conductive substrate) further comprising one or more coatings of carbon, metal (e.g., tin, zinc, aluminum, chromium, copper, nickel, iron, zirconium, silver, gold, platinum), metal oxide (e.g., indium tin oxide, tin oxide, titanium oxide, vanadium oxide, zirconium oxide) or polymer (e.g., PEDOT, PAN, parylene), wherein the coating acts as one or more of an adhesion promoter, an electronic conductivity promoter, and an ionic conductivity inhibitor. (Item 113) 112. The anode of any one of claims 109 to 111, wherein the thickness is sufficient to provide the anode with a capacity matching that of the cathode in a battery comprising the anode and cathode. (Item 114) 105. The anode of any one of claims 102 to 104, wherein the one or more structures comprise a foil having a polished surface (e.g., mechanically or electrochemically polished). (Item 115) 115. The anode of any one of items 102 to 114, wherein the one or more structures comprise a porous structure (e.g., the porous structure comprises pores having a circular or rectangular cross-section). (Item 116) 115. The anode of any one of items 102 to 114, wherein the one or more structures comprise a plurality of posts protruding from a current collector (e.g., a conductive substrate) (e.g., wherein the conductive substrate comprises one or more members selected from the group consisting of carbon, stainless steel, nickel, titanium, tungsten, copper and chromium). (Item 117) 117. The anode of any one of items 102 to 116, further comprising a non-native transitional aluminum oxide layer (e.g., having a thickness in the range of 0.1 nm to 10 micrometers) (e.g., formed by atomic layer deposition, chemical vapor deposition, thermal reaction, hydrothermal reaction, etching, electrochemical reaction, oxygen plasma reaction or hydroxide treatment). (Item 118) The non-native transitional aluminum oxide layer has a thickness within the following ranges (e.g., with a tolerance of ±20% or better): (i) 1 nm or more, (ii) 1 nm to 10 nm; (iii) 5 nm to 20 nm, (iv) 20 nm to 50 nm, (v) 50 nm to 250 nm, (vi) 100 nm to 500 nm, (vii) 500 nm to 1 micrometer, and (viii) 1 micrometer to 10 micrometers Item 118. The anode according to item 117, having a thickness within (at least) one of the ranges. (Item 119) Item 119. The anode of item 118, wherein the non-native transitional aluminum oxide layer is disposed on the one or more structures (e.g., including a thin film or foil). (Item 120) 120. The anode of any one of claims 102 to 119, further comprising an oxide film disposed on the one or more structures (e.g., having a thickness in the range of 0.1 nm to 100 micrometers), for example, where the oxide film is patterned (e.g., where the oxide film is patterned to correspond to a distribution of pillars on the current collector). (Item 121) The oxide film has a thickness within the following range (e.g., with a tolerance of ±20% or better): (i) 1 nm or more, (ii) 1 nm to 10 nm; (iii) 5 nm to 20 nm, (iv) 20 nm to 50 nm, (v) 50 nm to 250 nm, (vi) 100 nm to 500 nm, (vii) 500 nm to 1 micrometer, and (viii) 1 micrometer to 10 micrometers 121. The anode according to item 120, having a thickness within (at least) one of the ranges. (Item 122) 122. The anode according to claim 120 or 121, wherein the oxide film is a thin film. (Item 123) 122. The anode of claim 120 or 121, wherein the oxide film is a coating comprising a plurality of oxide particles. (Item 124) Item 124. The anode of item 123, wherein the plurality of oxide particles comprises nanoparticles, microparticles, or both nanoparticles and microparticles. (Item 125) At least 80% of the oxide particles have a particle size within the following range (e.g., with a tolerance of ±20% or better): (i) 1 nanometer to 500 micrometers, and (ii) 10 nanometers to 20 micrometers 125. The anode of item 124, having a dimension (e.g., diameter) within (at least) one of the ranges. (Item 126) 126. The anode of any one of claims 123 to 125, wherein the oxide film further comprises a polymer binder selected from the group consisting of carboxymethyl cellulose, styrene butadiene, polyvinyl alcohol, polypropylene and polytetrafluoroethylene. (Item 127) 127. The anode of any one of claims 123 to 126, wherein the oxide film further comprises one or more conductive carbon additives. (Item 128) 128. The anode of any one of claims 102 to 127, comprising a plurality of oxide films, each of said plurality of oxide films comprising a different oxide. (Item 129) 129. The anode according to any one of items 102 to 128, comprising multiple oxide layers of the same or different type, optionally with one or more aluminum layers between said oxide layers (e.g. the anode comprises at least one example of the following order of layers: Al / Al2O3 / ZrO2 / Al2O3) (e.g. the anode comprises at least one example of the following order of layers: Al / Al2O3 / Al / Al2O3). (Item 130) Item 130. The anode of item 128 or 129, wherein the one or more structures include a thin film or foil, and each of the plurality of oxide films is in contact with the one or more structures (e.g., arranged in rows (e.g., regular rows) on the thin film or foil). (Item 131) 130. The anode of claim 128 or 129, wherein the plurality of oxide films are disposed as a layer on the one or more structures. (Item 132) 130. The anode of claim 128 or 129, wherein the one or more structures include a plurality of thin films or foils, one or more of the plurality of thin films or foils being disposed between two or more of the oxide films. (Item 133) 117. The anode of any one of claims 102 to 116, comprising a plurality of oxide pillars protruding from the one or more structures. (Item 134) Item 134. The anode of item 133, wherein the plurality of oxide pillars are porous. (Item 135) Item 135. The anode of item 133 or item 134, wherein the plurality of oxide pillars comprises one or more of fibers, nanotubes, and nanocolumns. (Item 136) 136. The anode of any one of claims 133 to 135, wherein the plurality of oxide pillars are formed by physical vapor deposition, chemical vapor deposition, atomic layer deposition, hydrothermal reaction, electrochemical reaction, electrochemical deposition, or thermal reaction. (Item 137) 137. The anode of any one of claims 133 to 136, wherein the plurality of oxide pillars are formed by depositing a film and etching the film, the etching comprising plasma etching, wet chemical etching, reactive ion etching or buffered oxide etching. (Item 138) 138. The anode of any one of items 102 to 137, further comprising a non-oxide film disposed on the one or more structures (e.g., directly on the one or more structures or with one or more oxide films disposed between the non-oxide film and the one or more structures). (Item 139) the non-oxide film comprises one or more non-oxide members selected from the group consisting of a sulfide of the element, a sulfate of the element, a nitride of the element, a nitrate of the element, a phosphide of the element, a phosphate of the element, and a halide of the element; Item 139. The anode according to item 138, wherein the element is selected from the group consisting of zirconium, tungsten, indium, chromium, cobalt, magnesium, iron, nickel, vanadium, titanium, zinc, manganese, iron, tin, silicon, sulfur, copper, hafnium and cobalt. (Item 140) Item 140. The anode according to item 138 or item 139, wherein the non-oxide film is a thin film. (Item 141) Item 140. The anode of item 138 or item 139, wherein the non-oxide film is a coating comprising a plurality of non-oxide particles (e.g., comprising the one or more non-oxide members). (Item 142) Item 142. The anode of item 141, wherein the plurality of non-oxide particles comprises nanoparticles, microparticles, or both nanoparticles and microparticles. (Item 143) 143. The anode of any one of items 102 to 142, comprising a polymer layer disposed on the one or more structures (e.g., where surface coverage of the one or more structures by the polymer layer is 1% to 100%, e.g., at least 50% of the surface of the one or more structures is covered by the polymer layer) (e.g., where the polymer layer has a thickness in the range of 0.1 nm to 100 micrometers) (e.g., where the polymer layer has a thickness within (at least) one of the following ranges (e.g., with a tolerance of ±20% or better): (i) 1 nm or more; (ii) 1 nm to 10 nm; (iii) 5 nm to 20 nm; (iv) 20 nm to 50 nm; (v) 50 nm to 250 nm; (vi) 100 nm to 500 nm; (vii) 500 nm to 1 micrometer; and (viii) 1 micrometer to 10 micrometers). (Item 144) Item 144. The anode of item 143, wherein the polymer layer comprises one or more members selected from the group consisting of parylene, polyvinyl alcohol, alginic acid, PTFE, polyethylene oxide, cellulose (and derivatives thereof), polysulfone (PES), polymers of one or more acrylates, alginates (e.g., containing sodium, calcium, aluminum, potassium, magnesium, or zinc), quinones, hydroquinones, quinolones, hydroxyquinolines, and alizarins (e.g., containing Alizarin Red S). (Item 145) 1. An electrode (e.g., a cathode or anode, e.g., a cathode according to any one of items 28 to 89 or an anode according to any one of items 102 to 144) for an ion battery (e.g., an aluminum ion battery or an aqueous aluminum ion battery, e.g., a battery according to any one of items 1 to 27), comprising an electroactive material (e.g., arranged as particles or a film comprising one or more of manganese oxide, aluminosilicate and an aluminum-receptive polymer), a polymer binder, and conductive carbon (e.g., comprising carbon particles or carbon ribbons). (Item 146) Item 146. The electrode of item 145, wherein the polymer binder is 0.5% to 50% by weight of total solids in the electrode. (Item 147) Item 147. The electrode of item 145 or item 146, wherein the polymer binder comprises one or more members selected from the group consisting of cellulose (e.g., carboxymethyl cellulose or cellulose acetate), styrene butadiene rubber, polysulfone, alginate (e.g., alginic acid, calcium alginate, sodium alginate, aluminum alginate, zinc alginate or magnesium alginate), alizarin, quinone, hydroquinone, quinolone, hydroquinoline and polyvinyl alcohol (PVA). (Item 148) 148. The electrode according to any one of items 145 to 147, further comprising a current collector, wherein the polymer binder is disposed as a thin film (e.g., having a thickness in the range of 1 nm to 10 micrometers) on the current collector, such that the thin film of the polymer binder is disposed between the electroactive material and the current collector (e.g., wherein the thin film of the polymer binder has a thickness in (at least) one of the following ranges (e.g., with a tolerance of ±20% or better): (i) 1 nm or more; (ii) 1 nm to 10 nm; (iii) 5 nm to 20 nm; (iv) 20 nm to 50 nm; (v) 50 nm to 250 nm; (vi) 100 nm to 500 nm; (vii) 500 nm to 1 micrometer; and (viii) 1 micrometer to 10 micrometers). (Item 149) Item 146. The electrode of item 145, further comprising a conductive layer (e.g., having a thickness in the range of 1 nm to 10 micrometers), the conductive layer being in electrical and / or physical contact with and disposed between the electroactive material and the binder. (Item 150) Item 150. The electrode of item 149, wherein the conductive layer comprises a member selected from the group consisting of carbon, tin, tin oxide, indium tin oxide, titanium, chromium, nickel, gold, silver and platinum. (Item 151) 151. The electrode of any one of items 145 to 150, comprising a multilayer structure comprising a current collector, a first thin film of the polymer binder, a first conductive layer, a first layer of the electroactive material, a second thin film of the polymer binder, a second conductive layer and a second layer of the electroactive material (e.g., arranged in the order positions recited herein). (Item 152) 151. The electrode of any one of items 145 to 150, comprising a current collector, a first thin film of the polymer binder, a first layer of the electroactive material, a second thin film of the polymer binder, and a second layer of the electroactive material (e.g., and arranged in the order positions recited herein). (Item 153) 28. An aqueous electrolyte for an ion battery (e.g., a water-based aluminum ion battery, e.g., the battery according to any one of items 1 to 27), comprising water (e.g., deionized water) and an aluminum salt (e.g., one or more members selected from the group consisting of sulfate, phosphate, nitrate and halide salts of aluminum) wherein the water acts as a solvent and the aluminum salt is the major additive (e.g., the electrolyte has a total aluminum salt concentration in the range of 0.01 M to 5 M, e.g., 0.05 M to 1 M) (e.g., the aluminum salt is dissolved in the water). (Item 154) Item 154. The aqueous electrolyte according to item 153, further comprising an additive comprising a salt of sodium, lithium, potassium or calcium (e.g., one or more members selected from the group consisting of sulfate, phosphate, nitrate and halide salts of sodium, lithium, potassium or calcium) (e.g., the electrolyte has a concentration of sodium, lithium, potassium or calcium salt in total ranging from 0.01 M to 5 M, e.g., 1 M to 3 M) (e.g., the sodium, lithium, potassium or calcium salt is dissolved in the water). (Item 155) 155. The aqueous electrolyte according to item 153 or 154, further comprising a polymer (e.g., the polymer comprises one or more members selected from the group consisting of alginate, quinone, quinolone, hydroxyquinone, alizarin and hydroxyquinoline) (e.g., the electrolyte has a total polymer weight % in the range of 0.01 to 50 wt.%, e.g., 0.5 to 10 wt.%). (Item 156) 156. The aqueous electrolyte of any one of items 153 to 155, further comprising a wetting agent (e.g., the wetting agent comprises one or more members selected from the group consisting of ketones, alcohols, aldehydes, ethers, esters and cyclohexanes) that increases wettability of the cathode (e.g., the electrolyte has a total wetting agent weight % in the range of 0.01 to 50 wt.%, e.g., 0.5 to 10 wt.%). (Item 157) 157. The aqueous electrolyte of any one of items 153 to 156, comprising a manganese salt (e.g. one or more members selected from the group consisting of sulfate, phosphate, acetate, nitrate and halide salts of manganese) (e.g. the electrolyte has a total manganese salt concentration in the range of 0.01 M to 5 M, such as 0.05 M to 1 M) (e.g. the manganese salt is dissolved in the water). (Item 158) an anode comprising one or more members selected from the group consisting of aluminum, aluminum alloys and aluminum composites (e.g., the anode described in any one of items 102 to 144); an aqueous electrolyte (e.g. an electrolyte according to any one of items 153 to 157), and A cathode comprising one or more members selected from the group consisting of manganese oxide, aluminosilicate, and polymer (e.g., the cathode described in any one of items 28 to 89). An aluminum battery-capacitor hybrid comprising: one or more components of the aluminum battery-capacitor hybrid (e.g., the anode and / or the cathode) comprise one or more additives selected from the group consisting of pseudocapacitor additives and dielectric additives; the pseudocapacitor additive comprises one or more members selected from the group consisting of graphene, graphene oxide, carbon nanotubes, fullerenes, carbon aerogels, vanadium oxide, titanium oxide, molybdenum oxide, ruthenium oxide, polypyrrole, and poly(3,4-ethylenedioxythiophene); The dielectric additive comprises one or more members selected from the group consisting of titanium oxide, silicon oxide, zirconium oxide, parylene or other conjugated polymers, polystyrene, and polypropylene; Aluminum battery-capacitor hybrid. (Item 159) Item 159. The aluminum battery-capacitor hybrid according to item 158, wherein the one or more additives comprise a pseudocapacitor additive, and the pseudocapacitor additive comprises about 0.1 wt.% to about 90 wt.% of the combined net weight of the anode and cathode. (Item 160) 160. The aluminum battery-capacitor hybrid according to item 158 or 159, wherein the one or more additives comprise a pseudocapacitor additive, and the pseudocapacitor additive is in the form of a thin film, a nanostructure, a microstructure, a particle, or a combination thereof. (Item 161) 161. The aluminum battery-capacitor hybrid of any one of items 158 to 160, wherein the one or more additives include a dielectric additive, and the dielectric additive comprises about 0.1 wt.% to about 90 wt.% of the combined net weight of the anode and cathode. (Item 162) 162. The aluminum battery-capacitor hybrid according to any one of items 158 to 161, wherein the one or more additives comprise a dielectric additive, and the dielectric additive is in the form of a thin film, a nanostructure, a microstructure, a particle, or a combination thereof. (Item 163) The anode is a first aluminum layer comprising one or more members selected from the group consisting of aluminum, an aluminum alloy, or an aluminum composite; a dielectric layer including a dielectric additive; a second aluminum layer comprising one or more members selected from the group consisting of aluminum, an aluminum alloy, or an aluminum composite; and protective oxide layer 163. The aluminum battery-capacitor hybrid of any one of items 158 to 162, comprising: (Item 164) Item 164. The aluminum battery-capacitor hybrid according to item 163, wherein the first aluminum layer comprises aluminum foil. (Item 165) 165. The aluminum battery-capacitor hybrid of item 163 or 164, wherein the dielectric layer comprises a metal oxide. (Item 166) Item 166. The aluminum battery-capacitor hybrid according to item 165, wherein the metal oxide is zirconium oxide. (Item 167) Item 167. The aluminum battery-capacitor hybrid according to item 166, wherein the zirconium oxide is in the form of a thin film. (Item 168) 168. The aluminum battery-capacitor hybrid of any one of items 163 to 167, wherein the second aluminum layer comprises a thin film of aluminum foil. (Item 169) 169. The aluminum battery-capacitor hybrid according to any one of items 163 to 168, wherein the dielectric additive is aluminum oxide. (Item 170) Item 170. The aluminum battery-capacitor hybrid according to item 169, wherein the aluminum oxide is in the form of a thin film. (Item 171) The cathode is Stainless steel substrate, an aluminum layer comprising one or more members selected from the group consisting of aluminum, an aluminum alloy, or an aluminum composite; a dielectric layer including a dielectric additive; and Manganese oxide layer 171. The aluminum battery-capacitor hybrid of any one of items 158 to 170, comprising: (Item 172) Item 172. The aluminum battery-capacitor hybrid according to item 171, wherein the dielectric additive comprises a metal oxide. (Item 173) Item 173. The aluminum battery-capacitor hybrid according to item 172, wherein said metal oxide is zirconium oxide. (Item 174) 174. The aluminum battery-capacitor hybrid of any one of claims 163 to 173, wherein the anode and cathode are arranged to facilitate transport of aluminum ions from the second aluminum layer of the anode to the cathode. (Item 175) 174. The aluminum battery-capacitor hybrid of any one of items 171 to 173, wherein the anode and cathode are arranged to promote transport of aluminum ions from the manganese oxide layer of the cathode to the second aluminum layer of the anode during charging. (Item 176) 35. The cathode of any one of items 28 to 34, wherein the one or more structures comprise a multimodal (e.g., bimodal) distribution of particles (e.g., manganese oxide particles) with respect to one or more of shape and size. (Item 177) At least 80% of the particles of the cathode have a particle size within the following range (e.g., with a tolerance of ±20% or better for each modality): (i) 50nm or more, (ii) 100 nm to 250 nm; (iii) 500 nm to 5 micrometers; (iv) 1 micrometer to 10 micrometers, and (v) 5 micrometers to 30 micrometers 20 micrometers (±20%)と30 micrometers (±0.5 micrometers) (e.g., the cathode has a bimodal distribution of particles (e.g., manganese oxide particles) having a first portion of particles having a particle size of about 20 micrometers (±20%) and a second portion of particles having a particle size of about 0.5 micrometers (±20%), said first portion and second portion making up at least 80% of the particles of said cathode). [Brief description of the drawings]

[0137] [Figure 1] FIG. 1 shows examples of individual or interconnected porous aluminum or aluminum-based alloy or hybrid anode structures deposited on a conductive substrate according to exemplary embodiments of the present disclosure.

[0138] [Diagram 2] FIG. 2 illustrates an example of a transitional aluminum oxide region on an underlying aluminum substrate, according to an exemplary embodiment of the present disclosure.

[0139] [Diagram 3]3A and 3B are diagrams illustrating examples of individual layers of oxide films or coatings on aluminum or aluminum-based anodes according to exemplary embodiments of the present disclosure.

[0140] [Figure 4] 4A and 4B are diagrams illustrating multiple oxide films, coatings, or film-oxide combinations on an aluminum or aluminum-based anode according to an exemplary embodiment of the present disclosure.

[0141] [Diagram 5] 5A-5C show a repeat unit comprising an aluminum or aluminum-based underlying anode and a layer of an oxide film or coating according to an exemplary embodiment of the present disclosure.

[0142] [Figure 6] 6A-6B show examples of an underlying aluminum or aluminum-based anode coated with multiple oxides, each of which is present on the same substrate, according to an exemplary embodiment of the present disclosure.

[0143] [Figure 7] FIG. 7 shows an example of a porous oxide columnar-like structure deposited on an underlying aluminum or aluminum-based anode, according to an exemplary embodiment of the present disclosure.

[0144] [Figure 8A] FIG. 8A illustrates an oxide film or coating on a patterned aluminum or aluminum-based anode structure protruding from the underlying aluminum or aluminum-based alloy (or other conductive) substrate, according to an exemplary embodiment of the present disclosure.

[0145] [Figure 8B]FIG. 8B is a diagram illustrating an example of a single oxide film or coating on an aluminum or aluminum-based alloy structure (eg, from FIG. 8A) according to an exemplary embodiment of the present disclosure.

[0146] [Figure 8C] FIG. 8C is a diagram illustrating examples of multiple oxide films or coatings on an aluminum or aluminum-based alloy structure (eg, from FIG. 8A) according to an exemplary embodiment of the present disclosure.

[0147] [Figure 9A] FIG. 9A illustrates manganese oxide particles coated onto a porous conductive matrix comprising a conductive substrate (e.g., a foil or plate) and an array of conductive structures, according to an exemplary embodiment of the present disclosure.

[0148] [Figure 9B] FIG. 9B illustrates a cross-section of manganese oxide particles coated onto a core conductive structure (eg, as in FIG. 9A) according to an exemplary embodiment of the present disclosure.

[0149] [Figure 9C] FIG. 9C illustrates a cross-section of a manganese oxide film coated onto a core conductive structure according to an exemplary embodiment of the present disclosure.

[0150] [Figure 10A] FIG. 10A shows an example of manganese oxide coated on an interconnected porous substrate, where the pores are regular circular pores or irregular circular pores, according to an exemplary embodiment of the present disclosure.

[0151] [Figure 10B]FIG. 10B shows an example of manganese oxide coated on an interconnected porous substrate, where the pores are regular rectangular pores or irregular rectangular (e.g., woven) pores, according to an exemplary embodiment of the present disclosure.

[0152] [Figure 11] FIG. 11 illustrates an example of a manganese oxide film deposited on the exterior or interior surface of a carbon nanotube (CNT), according to an exemplary embodiment of the present disclosure.

[0153] [Figure 12] FIG. 12 is a diagram illustrating binders used in a slurry-based electrode composition according to an exemplary embodiment of the present disclosure.

[0154] [Figure 13] FIG. 13 illustrates a process for fabricating a binder-conductive layer-active cathode composite structure (top) and an example of a 3D configuration of multiple binder-conductive layer-active cathode repeat units (bottom) according to an exemplary embodiment of the present disclosure.

[0155] [Figure 14-1] FIG. 14 shows (A) the structural composition of a possible battery-capacitor hybrid anode, (B) the structural composition of a possible battery-capacitor hybrid cathode, (C) the reaction chemistry during discharge (including transport of aluminum ions from the anode to the cathode), and (D) the reaction chemistry during discharge (including transport of aluminum ions from the cathode to the anode) according to an exemplary embodiment of the present disclosure. [Figure 14-2] FIG. 14 shows (A) the structural composition of a possible battery-capacitor hybrid anode, (B) the structural composition of a possible battery-capacitor hybrid cathode, (C) the reaction chemistry during discharge (including transport of aluminum ions from the anode to the cathode), and (D) the reaction chemistry during discharge (including transport of aluminum ions from the cathode to the anode) according to an exemplary embodiment of the present disclosure.

[0156] [Figure 15] FIG. 15 illustrates the voltage profile of a sodium hydrate intercalated manganese oxide cathode assembled against a polished aluminum anode and cycled at a constant current density of about 20 μA / cm2 according to an exemplary embodiment of the present disclosure.

[0157] [Figure 16] FIG. 16 illustrates (a) X-ray diffraction results showing the presence of sodium chloride residues in the as-synthesized manganese oxide, and (b) evidence of large sheet spacing, according to an exemplary embodiment of the present disclosure.

[0158] [Figure 17] FIG. 17 illustrates thermogravimetric analysis (TGA) results showing evidence of water crystals within the manganese oxide structure, according to an exemplary embodiment of the present disclosure.

[0159] [Figure 18-1] FIG. 18 shows cross-sectional scanning electron microscope (SEM) images (left) and energy dispersive spectroscopy (EDS) mapping of aluminum ions (right) of a cathode after (a) 8 hours of discharge, (b) 20 hours of discharge, (c) 32 hours of discharge, and (d) 40 hours of discharge, according to an exemplary embodiment of the present disclosure. [Figure 18-2] FIG. 18 shows cross-sectional scanning electron microscope (SEM) images (left) and energy dispersive spectroscopy (EDS) mapping of aluminum ions (right) of a cathode after (a) 8 hours of discharge, (b) 20 hours of discharge, (c) 32 hours of discharge, and (d) 40 hours of discharge, according to an exemplary embodiment of the present disclosure.

[0160] [Figure 19] FIG. 19 illustrates a diagram showing capacity as a function of cycle index for an aluminum-manganese alloy anode according to an exemplary embodiment of the present disclosure.

[0161] [Figure 20] FIG. 20 illustrates (a) a top-down SEM image and EDS mapping of manganese oxide with potassium guest atoms from left to right, and (b) a voltage profile for a cell including manganese oxide with potassium guest atoms as the active cathode material, according to an exemplary embodiment of the present disclosure.

[0162] [Figure 21] FIG. 21 shows SEM images of cathodes synthesized with (a) polyvinylpyrrolidone (PVP) binder, (b) PVP and alginate binder, and (c) polyacrylic acid binder according to an exemplary embodiment of the present disclosure, as well as the discharge voltage profile as a function of time with (d) polyacrylic acid binder and (e) PVP / alginate binder.

[0163] [Figure 22] FIG. 22 shows (a), (b) SEM images of a patterned aluminum anode, (c) an SEM image of a polished unpatterned aluminum anode, (d), (e) voltage profile of a cell with a patterned aluminum anode, and (f) voltage profile of a cell with an unpatterned aluminum anode according to an exemplary embodiment of the present disclosure.

[0164] [Diagram 23] FIG. 23 illustrates cyclic voltammetry of a three-electrode system comprising an aluminum / zirconium oxide working electrode, a manganese oxide counter electrode, and an Ag / AgCl reference electrode, according to an exemplary embodiment of the present disclosure.

[0165] [Figure 24] FIG. 24 illustrates the cyclic voltammetry and charge-discharge voltage profile of an aluminum anode that has been spray coated with zirconium oxide according to an exemplary embodiment of the present disclosure.

[0166] [Diagram 25] FIG. 25 is a graph showing capacity as a function of cycle index at 15 hour, 6 hour and 3 hour charge-discharge rates, with charging at a constant voltage of 1.5 V, according to an exemplary embodiment of the present disclosure.

[0167] [Figure 26] FIG. 26 is a graph showing the charge-discharge profile of a manganese oxide cathode coated on a porous conductive substrate at rates of (a) C / 2.5 and (b) C / 0.5 according to an exemplary embodiment of the present disclosure.

[0168] [Figure 27] FIG. 27 is a graph showing discharge capacity as a function of cycle index for manganese oxide cathodes having (a) beta (β) and alpha (α) phases, (b) a majority (e.g., at least 70%) in the delta (δ) phase, and (c) a majority (e.g., at least 70%) in the gamma (γ) phase, in accordance with an exemplary embodiment of the present disclosure.

[0169] [Figure 28] FIG. 28 shows cyclic voltammetry in a three-electrode setup (Pt reference electrode) of a potassium-manganese oxide cathode against an aluminum anode according to an exemplary embodiment of the present disclosure, where only a pair of distinct, repeatable redox peaks are observed (0.7 V vs. Pt and 0.4 V vs. Pt).

[0170] [Figure 29] 29A-29B show elemental analysis confirming the presence of sodium in sodium-manganese oxide cathodes even after loading with aluminum ions, according to an exemplary embodiment of the present disclosure.

[0171] [Figure 30A]FIG. 30A shows EDS mappings showing that aluminum intercalation is independent of guest ion exchange for pyrolytic graphite cathodes, according to an exemplary embodiment of the present disclosure.

[0172] [Figure 30B] FIG. 30B shows EDS mappings showing that aluminum insertion is not dependent on the exchange of guest ions for sodium-manganese oxide cathodes, according to an exemplary embodiment of the present disclosure.

[0173] [Diagram 31] FIG. 31 is a diagram illustrating a bimodal distribution of cathode particle sizes (eg, 20 μm and 0.5 μm) according to an exemplary embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0174] Throughout the description, when compositions and devices are described as having, including, or comprising certain components, or when processes and methods are described as having, including, or comprising certain steps, it is further contemplated that there are compositions and devices that consist essentially of or consist of the recited components, and that there are processes and methods that consist essentially of or consist of the recited process steps. It should be understood that the order of steps or the order for performing certain actions is not important so long as the invention remains operable. Furthermore, two or more steps or actions may be performed simultaneously. Headings are provided for the convenience of the reader and are not intended as limitations on the claimed subject matter. The presence of material in the Background section is not an admission that such material is prior art. Headings are provided for the convenience of the reader and are not intended as limitations on the claimed subject matter.

[0175] In this application, unless otherwise clear from the context or expressly stated otherwise, (i) the term "a" can be understood to mean "at least one"; (ii) the term "or" can be understood to mean "and / or"; (iii) the terms "comprising" and "including" can be understood to encompass the listed components or steps, whether presented by themselves or with one or more additional components or steps; (iv) the terms "about" and "approximately" can be understood to allow for standard deviation as would be understood by one of ordinary skill in the art; and (v) when ranges are presented, the endpoints are included. In certain embodiments, unless otherwise specified, the term "approximately" or "about" refers to a value that falls within 25%, 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1% or less on either side of (greater or less than) the specified reference value, or a range that is otherwise clear from the context (except where such number would exceed 100% of the possible values).

[0176] Disclosed herein are aqueous aluminum ion batteries, battery-capacitor hybrids, cathode compositions, anode compositions, binder compositions, and methods of making and using the same. Aqueous aluminum-ion battery

[0177] Certain preferred embodiments of the aqueous aluminum ion battery described herein feature an aluminum or aluminum alloy / composite anode, an aqueous electrolyte, and a manganese oxide, aluminosilicate, or polymer-based cathode. The electrochemical reaction requires the actual transport of aluminum ions between the anode and the cathode. Various desired compositions and material properties of the anode and cathode are described herein along with their constituent structures. These compositions and structures allow the aqueous aluminum ion battery described herein to achieve: (1) improved charge storage capacity; (2) improved gravimetric and / or volumetric energy density; (3) improved rate capability and power density (ability to charge and discharge in a shorter time); (4) improved cycle life; (5) improved mechanical strength of the electrodes; (6) improved electrochemical stability of the electrodes; (7) improved conductivity of the electrodes; and (8) improved diffusion kinetics of ions in the electrodes and electrolyte.

[0178] The aqueous-based aluminum-ion battery described herein is shown to deliver capacities between 25mAh / g and 300mAh / g at rates ranging from 1C to 0.01C (where a rate of nC is defined as charge or discharge in 1 / n hours). Cycle life analysis indicates that the cell provides stable cycling performance over 150+ charge-discharge steps. All testing was done in a 2032 coin cell form factor and used standard separators such as Celgard (polypropylene) and glass microfiber.

[0179] Without wishing to be bound by any particular theory, certain preferred embodiments of the electrochemical cells described herein are believed to be due to one or more of the following reaction mechanisms (i)-(iv):

[0180] Reaction mechanism (i): When an external load is applied, aluminum ions (Al +3 ) is released. +3The ions pass through the aqueous electrolyte, the membrane separator, and migrate to the counter electrode, where the aluminum ions can intercalate within the electrode structure or otherwise react with one or more of: (i) oxide, (ii) hydroxide, (iii) nitrate, (iv) chloride, (v) sulfate, (vi) acetate, (vii) phosphate, (viii) manganese, (ix) sodium, (x) lithium, (xi) aluminum, and (xii) potassium to form a stable aluminum phase within or on the counter electrode structure. Additionally, one or more transition metals in the counter electrode can change their oxidation state to stabilize the structure.

[0181] Reaction mechanism (ii): When an external load is applied, aluminum ions (Al +3 ) is released. +3 The ions migrate through the aqueous electrolyte, the membrane separator, and to the counter electrode, where the aluminum ions are stored as a dielectric charge on the surface of the counter electrode.

[0182] Reaction mechanism (iii): When an external load is applied, aluminum ions (Al +3 ) is released. +3 The ions pass through the aqueous electrolyte and react with ions present in the electrolyte to form stable transport phases. For example, such phases include Al +3 Ions and OH -1 This is achieved by combining with ions, Al(OH)4 -1 These charge carriers can be formed in the Al +3The charge carriers are prevented from further reacting in the aqueous electrolyte. Once transported to the counter electrode, they may undergo one or both of the following processes: (a) dissociate to form individual anions and cations, and (b) remain in a stable charge carrier phase. If the individual anions and / or cations dissociate, they may further undergo one or more of the following processes: (a) intercalate and / or react with the counter electrode, as described in reaction mechanism (i), and (b) become stored on the surface of the counter electrode as a dielectric charge, as described in reaction mechanism (ii). If the charge carriers remain in their stable phase, they may undergo one or more of the following processes: (a) intercalation within the counter electrode structure, (b) transition to a non-ionic stable phase comprising aluminum and one or more of oxide, hydroxide, chloride, nitrate, sulfate, phosphate, lithium, sodium, potassium and magnesium, and intercalate and / or react within the counter electrode structure as per the mechanisms listed in reaction mechanism (i).

[0183] Reaction mechanism (iv): When an external load is applied, aluminum ions (Al +3 ) migrates to the opposite electrode and interacts there according to one or more of the mechanisms listed in reaction mechanisms (i), (ii), and (iii).

[0184] The exact nature of the electrochemical reaction depends on several factors, including: (a) the pH of the electrolyte, (b) the voltage window, (c) the state of charge, (d) the depth of discharge, and (e) the cell composition (anode, cathode, and electrolyte salts and solvents).

[0185] In some approaches, the electrochemical reaction may involve one or more ions in addition to the interactions mentioned above. The additional ions may include one or more of sodium, lithium, calcium, potassium and magnesium and may originate from the alloy aluminum anode, the salt of the electrolyte, or from guest ions or molecules stored between the sheets of the manganese oxide, aluminosilicate or polymer cathode. The additional ions may participate in the electrochemical reaction upon application of an external load (charging or discharging) or through ion exchange processes between the cathode and electrolyte, the anode and electrolyte, the cathode and anode, or combinations thereof. Transport mechanisms (and charge carrier characteristics) in electrolytes:

[0186] In some embodiments, Al released from the anode or cathode during electrochemical cycling. 3+ The ions can coordinate at the surface of the electrode and / or in the electrolyte to form complexes of various sizes, a specific common example being the polyoxometalate cluster Al 13 and Al 30 Keggin type complexes, but are not limited to this size or order.

[0187] These complexes are x O y H z From aluminum, oxygen and hydrogen alone; or together with other metals, such as X n Al x O y H zwhere X can be any metal or combination of metals from the group including sodium, lithium, calcium, potassium, magnesium, zirconium, lead, bismuth, titanium, vanadium, tin, copper, silver, gold, platinum, mercury, scandium, sulfur, silicon, iron, silicon, nickel, manganese, chromium, cerium, germanium, gallium, thallium, hafnium, indium, rhodium, ruthenium, molybdenum, palladium, strontium, yttrium, barium, cadmium, iridium, tantalum, cobalt, tellurium, antimony, arsenic, tungsten and selenium.

[0188] In electrolytes, these complexes exist in the following states: Al 3+ The fully dissociated state in which ions are present, the complex molecular state, or the form X n Al x O y H z These complexes may maintain their structure throughout the charge transport process or may undergo conversion between the anode and cathode inside and outside the separator layer. Aluminum insertion, accumulation and transport in the cathode and / or anode:

[0189] In some embodiments, Al that diffuses into the anode or cathode 3+ The ions can be coordinated to form complexes of various sizes in the electrolyte and / or at the surface of the anode and / or cathode and / or within the anode / cathode structure, a specific common example being the polyoxometalate cluster Al 13 and Al 30 Keggin type complexes, but are not limited to this size or order.

[0190] These complexes are x O y H z From aluminum, oxygen and hydrogen alone; or together with other metals, such as X n Alx O y H z where X can be any metal or combination of metals from the group including sodium, lithium, calcium, potassium, magnesium, zirconium, lead, bismuth, titanium, vanadium, tin, copper, silver, gold, platinum, mercury, scandium, sulfur, silicon, iron, silicon, nickel, manganese, chromium, cerium, germanium, gallium, thallium, hafnium, indium, rhodium, ruthenium, molybdenum, palladium, strontium, yttrium, barium, cadmium, iridium, tantalum, cobalt, tellurium, antimony, arsenic, tungsten and selenium.

[0191] In the cathode, these complexes can form a surface layer that is of varying composition during charging, discharging, and rest. This layer can be of various densities and crystalline orders, ranging from highly ordered layers and clusters to completely amorphous. Cathode components, including polymer binders, conductive carbon additives, and active metal oxide materials, can interact with this surface layer, providing electrons and various aluminum ions (e.g., Al) as charge carriers. + , Al 2+ , Al 3+ , Al(OH)4 1- Other metal ions may also be present and may diffuse through such layers on the cathode surface, including, but not limited to, the group including sodium, lithium, calcium, potassium, magnesium, zirconium, lead, bismuth, titanium, vanadium, tin, copper, silver, gold, platinum, mercury, scandium, sulfur, silicon, iron, silicon, nickel, manganese, chromium, cerium, germanium, gallium, thallium, hafnium, indium, rhodium, ruthenium, molybdenum, palladium, strontium, yttrium, barium, cadmium, iridium, tantalum, cobalt, tellurium, antimony, arsenic, tungsten, and selenium.

[0192] These complexes can be present within or on the surface or edges of the crystal lattice of the cathode active material. These complexes can transport and / or stabilize aluminum charge carriers within the cathode active material. These complexes can remain intact or partially intact within or on the surface or edges of the crystal lattice of the cathode active material throughout charging, discharging and / or resting conditions. anode

[0193] In certain preferred embodiments, the anode consists essentially of aluminum, aluminum composites and / or aluminum alloys in the form of foils, films, structures or particles. Aluminum composite or alloy anodes in the form of foils, films, structures or particles are referred to herein as aluminum-based anodes. The anodes may be free-standing in nature (as in foils) or coated on a conductive substrate.

[0194] In certain embodiments, the aluminum anode comprises an aluminum foil containing 0.00001% to 99.99999 or more by weight aluminum, with a purity ranging between 50% to 99.99999% or more. Additionally, the foil may further comprise an alloy or mixture of one or more of carbon, manganese, magnesium, cobalt, nickel, tin, iron, silicon, sodium, potassium, lithium, calcium, phosphorus, sulfur, zinc, copper, titanium, vanadium, and chromium. In certain embodiments, the thickness of the aluminum foil, including the alloy or mixture, if present, may range from 10 nm to 100 micrometers.

[0195] In some embodiments, the aluminum anode comprises a film of aluminum nanoparticles and / or microparticles. The aluminum particles can have diameters ranging between 10 nm and 50 micrometers. The aluminum particles may further comprise an alloy or mixed composition of one or more of carbon, manganese, magnesium, cobalt, nickel, tin, iron, silicon, sodium, potassium, lithium, calcium, phosphorus, sulfur, zinc, copper, titanium, vanadium, and chromium. The film may further comprise a polymer binder, including but not limited to carboxymethyl cellulose, styrene butadiene rubber, polyvinyl alcohol, polypropylene, poly-tetrafluoroethylene, and conductive carbon additives. Such films may be coated by a variety of techniques, including but not limited to doctor blade, slot die, electrochemical deposition, coextrusion, and spin coating. The films may be coated on conductive substrates, including but not limited to carbon, stainless steel, nickel, titanium, tungsten, copper, chromium, and aluminum. The thickness of the aluminum film of nanoparticles / microparticles, including alloys or mixtures, if present, may range from 10 nm to 1 mm.

[0196] In some embodiments, the aluminum anode may be deposited as a thin film. The film may further comprise one or more of carbon, manganese, magnesium, cobalt, nickel, tin, iron, silicon, sodium, potassium, lithium, calcium, zirconium, phosphorus, sulfur, zinc, copper, titanium, vanadium, and chromium. Such films may be coated by various techniques, including but not limited to physical vapor deposition, chemical vapor deposition, atomic layer deposition, and thermal evaporation. The films may be coated on conductive substrates, including but not limited to carbon, stainless steel, nickel, titanium, tungsten, copper, chromium, and aluminum. The thickness of the aluminum film, including alloys or mixtures, if present, may range from 1 nm to 1 mm. The thickness range of the aluminum determines the capacity that can be matched between the aluminum anode and the manganese oxide cathode. The aluminum or aluminum-based alloys or mixtures may be further patterned or deposited in the form of nanostructures. For example, a porous structural template (as shown in FIG. 1) can be obtained by a variety of techniques, including but not limited to photolithography, reactive ion etching, plasma etching, and oblique deposition. Some techniques include depositing aluminum and aluminum-based alloys and mixtures directly onto a porous substrate, including but not limited to nanotubes, fibers, foams, and meshes. Such porous substrates include one or more conductive compositions, including but not limited to carbon, nickel, stainless steel, titanium, tungsten, copper, chromium, and aluminum.

[0197] The aluminum or aluminum-based anodes described above may further include a transitional aluminum oxide layer ranging in thickness from 0.1 nm to 10 micrometers, for example as shown in FIG. 2. Such a transitional oxide may be in the form of a uniform thin film or may be patterned and closely resemble the structure of the underlying aluminum. Such a transitional aluminum oxide layer may be formed organically or otherwise by one or a combination of techniques including, but not limited to, chemical vapor deposition, thermal reaction, hydrothermal reaction, etching, electrochemical reaction, or other chemical reactions such as those involving oxygen plasma and hydroxide treatment, among others.

[0198] Optional secondary anode composition: The secondary anode composition can include a discrete layer of one or more oxides, including, for example, zirconium oxide, aluminum oxide, tungsten oxide, vanadium oxide, titanium oxide, zinc oxide, manganese oxide, iron oxide, tin oxide, silicon oxide, copper oxide, and / or cobalt oxide. The thickness of these oxide layers can range from 0.1 nm to 100 microns, and the layers can be created by techniques such as physical vapor deposition, chemical vapor deposition, atomic layer deposition, electrochemical deposition, and chemical reactions.

[0199] The oxide may be deposited in the form of a thin film (e.g., as shown in FIG. 3A), or a coating of nanoparticles, microparticles, or a combination of nanoparticles and microparticles (e.g., as shown in FIG. 3B). Thin films of oxide may be deposited by techniques including, but not limited to, physical vapor deposition, chemical vapor deposition, atomic layer deposition, and thermal evaporation. Meanwhile, coatings of nanoparticles and / or microparticles may be deposited by techniques including, but not limited to, doctor blade, slot die, electrochemical deposition, coextrusion, and spin coating. Additionally, the coating may further include a polymer binder, such as carboxymethyl cellulose, styrene butadiene rubber, polyvinyl alcohol, polypropylene, poly-tetrafluoroethylene, and / or a conductive carbon additive.

[0200] In some embodiments, the underlying aluminum or aluminum-based anode may be coated with multiple oxide layers, including a film (e.g., as shown in FIG. 4A), a coating (e.g., as shown in FIG. 4B), or a combination of both.

[0201] In some embodiments, aluminum or aluminum-based anodes (where aluminum-based refers to one or more of aluminum alloys, aluminum and a passivation layer or layers, aluminum and an oxide layer or layers, aluminum with a native oxide layer, aluminum with a transitional oxide layer, and other such combinations) and oxide films or coatings may be used as repeating units. Each unit may have the same or different compositions and the same or different thicknesses. Examples are shown in Figures 5A-5C, where Figure 5A shows two identical units, Figure 5B shows two different units (with films of different compositions), and Figure 5C shows two different units (one with an oxide coating and one with an oxide film). Some such approaches aid in scale-up and improve the mechanical, chemical, and electrochemical stability of the anode composition, allowing for efficient utilization and improved rate capabilities of the anode.

[0202] In some embodiments, the underlying surface of an aluminum or aluminum-based anode may be coated with multiple oxide films, oxide particles, or a combination of the two, with each oxide sharing the same underlying substrate, for example as shown in Figures 6A-6B. Such coatings can be efficiently achieved by techniques including, but not limited to, photolithography and the use of masks during deposition of the individual oxides.

[0203] In addition to films and coatings that include oxide particles, coatings can also include porous oxide structures, such as fibers, nanotubes, and nanocolumns, for example, as shown in Figure 7. Such oxide structures can be deposited by techniques including, but not limited to, oblique angle deposition, physical vapor deposition, chemical vapor deposition, atomic layer deposition, lithography, photolithography, e-beam lithography, die-stamping, baking, hot pressing, electrochemical deposition, and hydrothermal reactions.

[0204] In some embodiments, oxides may also be coated and / or deposited directly onto the porous aluminum or aluminum-based anode, for example, as shown in Figures 8A-8B. Such deposition methods may include one or more techniques, including, but not limited to, physical vapor deposition, chemical vapor deposition, atomic layer deposition, hydrothermal reactions, electrochemical reactions, electrochemical deposition, thermal reactions, and / or other similar chemical reactions. In some approaches, an oxide layer may be coated onto the underlying aluminum or aluminum-based anode in the form of a film or layer of nanoparticles, microparticles, or a combination of both, and then subjected to some form of etching, including, but not limited to, plasma etching, reactive ion etching, and / or buffered oxide etching. Furthermore, multiple oxide layers may be coated onto the core aluminum or aluminum-based anode structure, for example, as shown in Figure 8C. In some approaches, oxide layers may be organically grown as transitional oxides on the porous aluminum substrate. Such oxide layers may primarily comprise aluminum oxide, with or without oxides of other alloy materials present with the underlying aluminum anode. Such transitional aluminum oxide layers may be formed organically or otherwise by one or a combination of techniques including, for example, chemical vapor deposition, thermal reactions, lithography, die-stamping, hot pressing, hydrothermal reactions, etching, electrochemical reactions, and / or other chemical reactions such as those involving oxygen plasma and hydroxide treatments, among others.

[0205] Beyond oxides, other layers of films or particles that may be desirable in the proposed aqueous aluminum ionic systems include, for example, sulfides, sulfates, nitrides, nitrates, phosphides, phosphates and halides of elements including, but not limited to, zirconium, tungsten, vanadium, titanium, zinc, manganese, iron, tin, silicon, copper and cobalt. Additionally, the underlying aluminum or aluminum-based anode may be coated with a layer comprising one or a combination of sulfides, sulfates, nitrides, nitrates, phosphides, phosphates and halides of elements including, but not limited to, zirconium, tungsten, vanadium, titanium, zinc, manganese, iron, tin, silicon, copper and cobalt.

[0206] Additionally, the underlying aluminum or aluminum-based anode may be coated with one or more layers of polymers, including but not limited to monomers, oligomers and polymers or copolymers of parylene, polyvinyl alcohol, alginic acid, alginates (sodium, calcium, aluminum, potassium, magnesium, zinc), quinone, hydroquinone, quinoline, hydroxyquinoline, alizarin, and / or alizarin red S; and / or corresponding derivatives. These monomers, oligomers and / or polymers can be deposited on the surface of the aluminum film with a polymer layer thickness ranging from 0.1 nm to 100 micrometers. The polymer layer can have a surface coverage of between 1% and 100% of the area of ​​the underlying aluminum film. Techniques used to deposit these polymers include chemical vapor deposition, spin-coating, doctor blade, co-extrusion and slot-die, among others.

[0207] Additionally, the underlying aluminum or aluminum-based anode may be coated with one or more layers including monomers, oligomers and polymers or copolymers of oxides, sulfides, sulfates, nitrides, nitrates, phosphides, phosphates, halides, parylene, polyvinyl alcohol, alginic acid, alginates (sodium, calcium, aluminum, potassium, magnesium, zinc), quinone, hydroquinone, quinoline, hydroxyquinoline, alizarin, and / or alizarin red S; and / or corresponding derivatives. Surface SEI layer of aluminum anode:

[0208] The aluminum, aluminum alloy, or aluminum compound anode may include a surface layer comprising (e.g., consisting of) one or more of oxygen, hydrogen, nitrogen, sulfur, phosphorus, halogens (fluorine, chlorine, bromine, iodine), carbon, or combinations thereof, and one or more metals (including but not limited to one or more of sodium, potassium, lithium, calcium, magnesium, manganese, zinc, titanium, indium, tin, copper, vanadium, silicon, cobalt, chromium). In certain embodiments, the surface layer comprises (e.g., consists of) a complex of aluminum, oxygen, and / or hydrogen. In some embodiments, the surface layer comprises (e.g., consists of) a complex of aluminum, metal, oxygen, and hydrogen, where the metal can comprise one or more of sodium, lithium, calcium, potassium, magnesium, zirconium, lead, bismuth, titanium, vanadium, tin, copper, silver, gold, platinum, mercury, scandium, sulfur, silicon, iron, silicon, nickel, manganese, chromium, cerium, germanium, gallium, thallium, hafnium, indium, rhodium, ruthenium, molybdenum, palladium, strontium, yttrium, barium, cadmium, iridium, tantalum, cobalt, tellurium, antimony, arsenic, tungsten, and selenium. In certain embodiments, the surface layer can change structure and composition during electrochemical cycling, including charging, discharging, and resting.

[0209] In one particular embodiment, Al released from the anode surface 3+ The ions can coordinate in the electrolyte to form complexes of various sizes, e.g., polyoxometalate clusters Al 13 and Al 30 Keggin type complexes, but are not limited to this size or order. These complexes are x O y H z Aluminum, oxygen and hydrogen; or together with other metals such as X n Al x O y H z where X can be any metal or combination of metals from the group including sodium, lithium, calcium, potassium, magnesium, zirconium, lead, bismuth, titanium, vanadium, tin, copper, silver, gold, platinum, mercury, scandium, sulfur, silicon, iron, silicon, nickel, manganese, chromium, cerium, germanium, gallium, thallium, hafnium, indium, rhodium, ruthenium, molybdenum, palladium, strontium, yttrium, barium, cadmium, iridium, tantalum, cobalt, tellurium, antimony, arsenic, tungsten, and selenium.

[0210] At the cathode, these complexes can form a surface layer that is of varying composition during charging, discharging, and rest. This layer can be of various densities and crystalline orders, ranging from highly ordered layers and clusters to completely amorphous. Metallic aluminum accumulated within the anode can interact with this surface layer, providing electrons and various aluminum ions (e.g., Al) as charge carriers. + , Al 2+ , Al 3+ , Al(OH)4 1- ) movement is possible.

[0211] It should be noted that, in general, these complexes can be present on, within, or any combination of the anode, cathode, separator, or anywhere in the electrolyte. These clusters and / or networks can exist during charging, discharging, and / or rest, or any combination thereof. Current collector substrate for anode:

[0212] In certain embodiments, solutions containing aluminum and alloy particles, aluminum or aluminum alloy films, or aluminum-based compounds may be deposited directly onto the current collector, for example, by doctor-blade, slot-die, comma, spray, or spin coating techniques. Aluminum, aluminum alloys, or aluminum-based compounds may also be deposited onto the current collector by physical or chemical vapor deposition techniques, or by atomic layer deposition.

[0213] The current collector substrate can be carbon or other conductive metal or metal oxide substrates, including but not limited to tin, tin oxide, indium, indium tin oxide, tungsten, vanadium, stainless steel, nickel, zinc, aluminum, copper, chromium, titanium, bismuth, silver, gold, platinum, iron, iron oxide, and molybdenum. In certain embodiments, the current collector substrate is further coated with one or more films, which are made of carbon, metals and / or their corresponding metal oxides, including but not limited to tin, tin oxide, indium, indium tin oxide, tungsten, vanadium, stainless steel, nickel, zinc, aluminum, copper, chromium, titanium, bismuth, silver, gold, platinum, iron, iron oxide, and molybdenum, and polymers, including but not limited to PTFE, PVDF, parylene, poly(3,4-ethylenedioxythiophene) (PEDOT), polyaniline, polypropylene, and cellulose. In certain embodiments, the film improves adhesion. In certain embodiments, the film improves electronic conductivity. In certain embodiments, the film is impermeable to one or more ions, including but not limited to metal ions such as calcium, potassium, aluminum, lithium, sodium, magnesium, manganese, cobalt, chromium, nickel, zinc, and iron. In some embodiments, the film is impermeable to ionic complexes, including one or more of oxygen complexes, hydrogen complexes (including hydroxides and oxide-hydroxides), nitrogen complexes (including nitrides, nitrates), phosphorus complexes (including phosphides, phosphates), sulfur complexes (including sulfides, sulfates), and halides complexes, or combinations thereof. Cathode

[0214] In certain preferred embodiments, the cathode is primarily comprised of manganese oxide structures, layered aluminosilicates or aluminum-accepting polymers, along with a conductive additive to improve charge distribution and contact with the current collector, and a polymer binder to adhere the electrode to the current collector and maintain physical interconnection of the electrode and conductive additive particles (while allowing electrolyte permeation). The cathode, binder and conductive additive are typically mixed in a solvent such as water, N-methylpyrrolidone, ethanol, among others, and coated onto the current collector substrate by means including, but not limited to, doctor blades and slot-dies. The as-coated cathode may or may not be dried and calendered to improve mechanical strength and density. The thickness of the cathode may range between 10 nm and 1 mm. Manganese oxides include MnO, MnO2, Mn x O y and manganese having the state Mn(II), Mn(II-x), Mn(III), Mn(III-x), Mn(IV), Mn(IV-x), Mn(V), Mn(Vx), Mn(VI), Mn(VI-x), Mn(VII) or Mn(VII-x), where x is between 0 and 1.

[0215] Manganese oxides are synthesized by the reaction between two or more of the following precursors: salts of manganese where the anion is sulfate, nitrate, chloride, acetate, phosphate, perchlorate, fluoride or bromide. These precursors may also be sodium or potassium permanganates. These precursors are reacted with an appropriate mixture of bases such as, but not limited to, lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium hydroxide, along with an oxygen source such as dissolved oxygen gas, hydrogen peroxide, or other peroxides and oxygen-rich molecules. The presence of an external oxidizing chemical catalyst may or may not be included. Following this redox chemical reaction, the as-obtained product may or may not be subjected to a hydrothermal treatment.

[0216] In some embodiments, the binder-free cathode is deposited on the current collector substrate using methods including, but not limited to, chemical vapor deposition, physical vapor deposition, atomic layer deposition, spin-coating, atomic layer deposition, and / or electrochemical deposition. The thickness of such cathodes can range between 1 nm and 1 mm. Manganese oxide material properties:

[0217] Manganese oxides can have turbostratic structures or highly oriented layouts that include several manganese oxide sheets. The particles can consist of sheets ranging in size from 10 nm to 500 micrometers. These sheet layers can be transformed into various spinel, tunnel, sandwich or encapsulation and trapping structures that may or may not contain guest ions or molecules or combinations of guest ions and molecules. Possible guest ions include, but are not limited to, one or more of sodium, lithium, potassium, calcium, zinc, bismuth, copper, lead, cobalt, nickel, magnesium, aluminum, hydrogen, hydronium ions, hydroxide ions, oxide-hydroxide ions, sulfate ions, sulfide ions, nitride ions, nitrate ions, phosphide ions, phosphate ions and acetate ions. Possible guest molecules include, but are not limited to, one or more of the following: water, oxides, hydroxides, oxide-hydroxides, sulfides, sulfates, nitrides, nitrates, phosphides and / or phosphates of sodium, lithium, potassium, calcium, magnesium, aluminum, manganese.

[0218] Furthermore, these sheets can be subjected to a spheronization process to obtain a spherical structural geometry. The particles can consist of spheres with diameters ranging from 10 nm to 500 micrometers. It is also possible to have a mixture of spherical and sheet-like geometries of manganese oxide. The material can be either a structured material that accepts guest ions, guest molecules, or a combination of both, or an ordered crystalline material that contains sites / vacancies that accept guest ions, guest molecules, or a combination of both.

[0219] The interlayer distance (d-layer spacing

[0001] ) of manganese oxide ranges between 1 Å and 50 Å. Exfoliation of the interlayer distance is achieved by an ion exchange process, including but not limited to one, more or a combination of the following ions: lithium, calcium, aluminum, sodium, magnesium and potassium. A wide range of pillaring agents can be used, including but not limited to polyoxometalates (POMs), amphiphilic molecules, and both polar and non-polar organic molecules. The aforementioned ions and / or molecules are intercalated between the manganese oxide sheets, which increases the d-layer spacing between the layers to accommodate the ions, which in turn increases the surface area of ​​the material. These ions / atoms / molecules can be present in their ionic form through weak physical or chemical bonds with the manganese oxide, or react with one, more or a combination of groups formed during the synthesis process, including but not limited to manganese hydroxide, manganese oxide hydroxide, manganese chloride, manganese sulfate, manganese acetate, manganese phosphate and manganese nitrate, further increasing the d-layer spacing between the layers. These ions or respective stable compounds can remain between the manganese oxide sheets or they may be removed by several washing cycles. These guest ions, pillar formers and molecules can reside at the edges, in three corner-sharing vacancies or similar vacancies, or anywhere on the normal crystal faces of the manganese oxide. Cathode structural structure:

[0220] Manganese oxide may be deposited on a conductive substrate as a thin film or coating consisting of nanoparticles, microparticles, or a combination of nanoparticles and microparticles. Manganese oxide thin films may be deposited by techniques including, but not limited to, physical vapor deposition, chemical vapor deposition, atomic layer deposition, and thermal evaporation. Meanwhile, nanoparticle and / or microparticle coatings may be deposited by techniques including, but not limited to, doctor blade, slot die, electrochemical deposition, comma coating, and spin coating, or other similar manufacturing methods. Additionally, the coating may further include a polymeric binder, including, but not limited to, carboxymethylcellulose, styrene butadiene rubber, polyvinyl alcohol, alginate, polypropylene, poly-tetrafluoroethylene, and / or conductive carbon additives.

[0221] Conductive substrates on which the cathode may be deposited (or coated) include, but are not limited to, stainless steel, copper, carbon, silver, gold, platinum, tin, vanadium, zinc, tin oxide, indium, indium tin oxide, aluminum, nickel, tungsten, chromium and titanium foils and plates. Additionally, the foils and plates may be coated with a thin film of an adhesion promoter, a conductivity promoter, or a combination of an adhesion promoter and a conductivity promoter.

[0222] In certain embodiments, the conductive substrate is a porous structure, such as a mesh, foam, fiber, or nanostructure and / or microstructure of one or more of stainless steel, carbon, silver, gold, platinum, tin, vanadium, zinc, tin oxide, indium, indium tin oxide, copper, aluminum, nickel, tungsten, chromium, and titanium. Figures 9A-9C show examples of such cathodes. In Figure 9A, a conductive core fiber or nanostructure and / or microstructure matrix is ​​coated with manganese oxide particles (or films). Details of a single structure derived from such a matrix are shown in Figures 9B-9C. Figures 10A-10B also show examples of coated porous structures.

[0223] In some embodiments, the cathode may be coated on a high surface area porous carbon, including but not limited to one or more of carbon nanotubes (CNTs), fullerenes, graphene, and / or partially reduced graphene oxide. The high surface area porous carbon can act as a free-standing film and current collector, and may be grown directly on a conductive substrate or added to a slurry that is coated onto a current collector substrate. Manganese oxide may be coated onto such conductive carbon additives by a slurry-based approach or thin film deposition technique, for example, in the form shown in FIG. 11.

[0224] In some approaches, pores may be achieved in the cathode through the use of sacrificial materials such as one or more polymers, including, but not limited to, alizarin, amidinates, quinones, alginates, zeolites, quinolines, hydroxyquinones, crown ethers and hydroxyquinoline monomers, oligomers and polymers or copolymers, or other similar chelating or coordinating complexes, silicon, copper, cobalt, chromium, nickel, iron, and oxides, hydroxides, sulfates, nitrates and phosphates of silicon, copper, cobalt, chromium nickel and iron. The sacrificial material may be co-deposited with manganese oxide (such as by co-thermal evaporation, co-sputtering and co-extrusion) or mixed with manganese oxide, conductive carbon and polymer binder in a slurry, which is then coated onto a conductive current collector. The sacrificial material may be removed ex situ by processes including, but not limited to, etching, plasma, heat treatment, ion exchange and chemical reaction, where the sacrificial polymer forms an insoluble precipitate that can be removed by washing. In some approaches, the sacrificial material may be removed in situ during storage or operation of the electrochemical cell by processes such as ion-exchange.

[0225] Aluminum-accepting polymers: Apart from manganese oxides or aluminosilicates, certain polymers are also found herein to be viable candidates for electrochemical cells. Such polymers can include, but are not limited to, alizarin, alginate, amidinate, quinone, quinoline, hydroxyquinone, crown ether and hydroxyquinoline monomers, oligomers and polymers or copolymers, as well as coordination or chelating complexes. These polymers can further exist in the form of a complex with one or more ions, including, but not limited to, lithium, sodium, lead, chromium, copper, bismuth, cobalt, zinc, potassium, aluminum, calcium, magnesium, manganese, iron, cobalt, titanium, tin, vanadium and tungsten. Furthermore, ion-forming monomer, oligomeric, polymer and copolymer complexes can also participate in electrochemical reactions by ion exchange processes with aluminum ions derived from the electrolyte and / or derived from the aluminum source electrode during charging and conversely during discharging. Cathode material phase:

[0226] In certain embodiments, the cathode comprises one or more phases of manganese oxide, the one or more phases including, but not limited to, one or more of alpha, beta, lambda (λ), ramsdellite, amorphous, gamma, delta, and epsilon (ε). In some embodiments, the cathode comprises a primary phase of manganese oxide, and one or more of secondary and tertiary phases of (e.g., the) manganese oxide. In some cases, the cathode may comprise four or more phases of manganese oxide. The concentration of each phase present can be 100% by weight for single-phased compositions, or can range from 0.1% to 99.9% by weight for multi-phase compositions, for example. For example, in certain embodiments, the primary phase comprises at least 40% by weight of the cathode. In some embodiments, the other phases present (e.g., secondary, and optionally tertiary) comprise less than 50% by weight of the cathode. In certain embodiments, the one or more phases undergo a transition to one or more other phases during charging and / or discharging of the electrochemical cell. In some embodiments, the cathode includes one or more structures (e.g., particles) that include manganese oxide, where the manganese oxide is a majority (e.g., at least 70%, at least 80%, or at least 90% by weight) of delta phase manganese oxide. In some embodiments, cathodes that use delta phase manganese oxide or higher proportions of delta phase manganese oxide perform better than cathodes that use manganese oxide in other phases, including those in which another phase of manganese oxide (e.g., gamma phase) reversibly transitions between phases during charging cycles (e.g., between gamma and delta phases).

[0227] In addition to the phase, manganese oxides can also be defined, at least in part, by their structure, which may include one or a combination of layered structures (e.g., phyllomanganates), tunnel structures (e.g., tectomanganates), spinels, ramsdellites, and amorphous. In some embodiments, the cathode comprises a manganese oxide in which manganese is octahedrally coordinated to six oxygen atoms, where none of the oxygens can be replaced by hydroxides or Reutschi vacancies (e.g., protonated Mn vacancies), or any or all of the oxygens can be replaced by hydroxides or Reutschi vacancies.

[0228] In some embodiments, the manganese oxide in the cathode can be comprised of manganese in one or more oxidation states selected from the group consisting of Mn(II), Mn(II-x), Mn(III), Mn(III-x), Mn(IV), Mn(IV-x), Mn(V), Mn(Vx), Mn(VI), Mn(VI-x), Mn(VII) and Mn(VII-x), where x is between 0 and 1. Current collector substrate for cathode:

[0229] In some embodiments, the current collector substrate is carbon or other conductive metal or metal oxide substrate, including but not limited to tin, tin oxide, indium, indium tin oxide, tungsten, vanadium, stainless steel, nickel, zinc, aluminum, copper, chromium, titanium, bismuth, silver, gold, platinum, iron, iron oxide, and molybdenum. In certain embodiments, the current collector substrate is further coated with one or more films, which are made of carbon, metals and / or their corresponding metal oxides, including but not limited to tin, tin oxide, indium, indium tin oxide, tungsten, vanadium, stainless steel, nickel, zinc, aluminum, copper, chromium, titanium, bismuth, silver, gold, platinum, iron, iron oxide, and molybdenum, and polymers, including but not limited to PTFE, PVDF, parylene, PEDOT, polyaniline, polypropylene, and cellulose. In certain embodiments, the film improves adhesion. In certain embodiments, the film improves electronic conductivity. In certain embodiments, the film is impermeable to one or more ions, including metal ions such as, but not limited to, calcium, potassium, aluminum, lithium, sodium, magnesium, manganese, cobalt, chromium, nickel, zinc, and iron, In other embodiments, the film is impermeable to ionic complexes, including one or more of complexes with oxygen, complexes with hydrogen (including hydroxides and oxide-hydroxides), complexes with nitrogen (including nitrides, nitrates), complexes with phosphorus (including phosphides, phosphates), complexes with sulfur (including sulfides, sulfates), and complexes with halides, or combinations thereof. Binder Composition

[0230] In some embodiments, the polymer binder is selected to ensure both cohesion between the active electrode particles and adhesion to the conductive carbon particles, and between the electrode structure and the current collector substrate, as shown, for example, in Figure 12. The proportion of polymer binder will typically be between 0.5 and 50% by weight of the total electrode solids.

[0231] Polymeric binders that can be used include, but are not limited to, one or more of cellulose and its derivatives, such as carboxymethylcellulose and cellulose acetate, styrene, styrene butadiene rubber and other similar butadiene rubbers, polysulfones, alginates (alginic acid, calcium alginate, sodium alginate, aluminum alginate, zinc alginate, magnesium alginate, and similar multivalent ion crosslinked derivatives and combinations thereof), alizarin and its derivatives, such as alizarin red S, quinones, hydroquinones, quinolines, hydroquinolines, and polyvinyl alcohols. These monomeric, oligomeric, and polymeric and coploymer binders may further comprise ionic complexes with one or more ions, including, but not limited to, lithium, sodium, potassium, aluminum, calcium, magnesium, manganese, iron, cobalt, titanium, tin, vanadium, and tungsten. The ionic complexes may further be formed by an in situ or ex situ ion exchange step. In situ ion exchange involves the exchange of ions originating from one or more of the electrolyte, aluminum source electrode and aluminum host electrode either prior to cycling or during the formation cycle of the battery chemistry by osmotic pressure, electrophoretic force or similar driving force. Ex situ ion exchange involves the exchange of ions originating from the solution during the slurry formulation process, whereby the aqueous slurry contains relevant salts that enable the ion exchange process. The purpose of the ion exchange process is to ensure improved mechanical robustness of the binder and therefore the electrode structure.

[0232] In some approaches, the binder may be coated on a conductive substrate as a thin film, with thicknesses ranging between 1 nm and 10 micrometers. A conductive layer, such as carbon, tin, titanium, chromium, nickel, gold, silver, platinum, and other similar materials, is then coated on top of the binder film, with thicknesses ranging between 1 nm and 10 micrometers. This composition is then subjected to pressure by processes including, but not limited to, compressive force, tensile force, shear force, hot pressing, sintering, and calendaring. Following this, the active cathode material (manganese oxide, aluminosilicate, polymer) is coated directly on top of the carbon film. Such configurations can also be used as repeat units to achieve scalability, improve electrode utilization, and increase rate capability, for example, as shown in FIG. 13 (showing how to make multiple repeat units (bottom) (top)).

[0233] If the adhesion between the active cathode material and the underlying conductive substrate is not ideal, a second layer of binder may be used to coat the conductive layer, then the active cathode material, and finally the multi-layer structure is subjected to the pressing process described above.

[0234] It may be possible to eliminate the use of a conductive layer from the above approach and coat the active cathode material directly onto a thin film of binder and then subject this construction to the above-described pressing forces. Alginate Binder:

[0235] In some embodiments, the cathode includes a binder. In some embodiments, the cathode includes an alginate binder. The alginate binder may be combined with another binder, such as PVP. In some embodiments, when alginate is present (e.g., in the cathode), multivalent ions are included. Multivalent ions that can be used include, but are not limited to, manganese, magnesium, calcium, zinc, barium, and aluminum ions. In some embodiments, monovalent ions are included. For example, the binder may include alginate and one or more ions of lithium, sodium, and potassium. Ions that can be used for ionic pretreatment of the cathode, including binders such as PVP-alginate, include sodium, potassium, magnesium, manganese, aluminum, calcium, barium, strontium, and zinc ions. Inclusion of ions (e.g., multivalent or monovalent ions) with the binder can induce mechanical enhancement and / or electrochemical stability.

[0236] Other polymer binders may be used with monovalent and / or polyvalent ions. Some examples include, but are not limited to, polyvinylidene difluoride (PVDF), PTFE, polyaniline, epoxy, carboxymethyl cellulose, rubber, styrene butadiene rubber, polyacrylic acid, polyvinyl alcohol, and polyvinyl propylene. Solvents in which such binders are dispersed (e.g., during cathode fabrication) may include, but are not limited to, water, n-methylpyrrolidone, ketones, glycols, dimethyl sulfoxide (DMSO), and esters. Co-solvents may also be used. Usable co-solvents include, but are not limited to, water, n-methylpyrrolidone, ketones, glycols, DMSO, and esters. Battery-capacitor hybrid

[0237] Battery-capacitor hybrids may be implemented using any of the aforementioned compositions of anode, cathode and / or electrolyte. Such systems may include one or more pseudocapacitor additives, including but not limited to graphene, graphene oxide, carbon nanotubes, fullerenes, carbon aerogels, vanadium oxide, titanium oxide, molybdenum oxide, ruthenium oxide, polypyrrole and poly(3,4-ethylenedioxythiophene), and / or dielectric additives, including but not limited to titanium oxide, silicon oxide, zirconium oxide, parylene or other conjugated polymers, polystyrene and polypropylene. The pseudocapacitor or dielectric material may comprise 0.1% to 90% by weight of the net electrode weight and may be in the form of a thin film, nanostructure, microstructure, particle, or combination of one or more of such structures.

[0238] An example of such a battery-capacitor hybrid concept is described as follows.

[0239] Anode structure: Aluminum foil is coated with a thin film of zirconium oxide, then with a film of aluminum, and finally with a film of aluminum oxide, for example as shown in panel (A) of FIG.

[0240] Cathode structure: A stainless steel current collector substrate is coated with a thin film of aluminum and then with a thin film of aluminum oxide. A thin film of manganese oxide cathode is then deposited on top of the stainless steel-aluminum-zirconium oxide structure, for example as shown in panel (B) of FIG.

[0241] Anode reactions during discharge (e.g., as shown in panel (C) of FIG. 14): When aluminum ions are transported from the anode to the cathode during discharge, the zirconium oxide acts as a dielectric layer with aluminum layer-1 acting as the aluminum ion source for the dielectric. Aluminum layer-2 acts as the aluminum ion source for the cell-reaction kinetics, including the transport of these ions from the anode to the cathode. The aluminum oxide layer acts as a protective oxide layer, preventing corrosion and undesirable side reactions with the underlying aluminum.

[0242] Cathodic reaction during charging (shown, for example, in panel (D) of FIG. 14): When aluminum ions are transported from the manganese oxide cathode back to the aluminum anode during charging, the zirconium oxide layer acts as a dielectric layer and the underlying aluminum film acts as the aluminum ion source for the dielectric.

[0243] The dielectric kinetics allows for very fast charge-discharge rates while the battery kinetics contributes to the high energy density, thus allowing such systems to combine both high power density and high energy density. EXAMPLES

[0244] In order to make the present disclosure more fully understood, the following examples are described.It should be understood that these examples are merely for illustrative purposes and should not be interpreted as limiting in any way, for example, with respect to any claims.Unless otherwise clear from the context, any one or more features from any one or more of the examples can be combined with any one or more features from any other example and / or with any one or more other features disclosed herein. Example 1 Experimental data on aqueous aluminum-ion batteries

[0245] FIG. 15 shows a current of approximately 20 μA / cm assembled against a polished aluminum anode. 2FIG. 1 shows the voltage profile of a hydrated sodium intercalated manganese oxide cathode cycled at a constant current density of 1000 mAh / g. The electrolyte composition is 0.1 M Al(NO3)3 + 2 M LiNO3, corresponding to a pH in the range of 3-3.5. The smaller the manganese oxide particle size, the more pronounced the voltage plateau becomes evident, corresponding to the subsequent improvement in charge storage capacity and rate capability. Particles with dimensions in the range of (a) less than 45 μm and (b) between 20-45 μm typically deliver capacities between 50-150 mAh / g, and sometimes higher than 200 mAh / g, at rates of C / 4 and slower (rate C / n indicates charge or discharge in n hours). When particle sizes are (c) <1 μm, manganese oxide cathodes can deliver capacities in excess of 150 mAh / g, and often higher than 200 mAh / g, at rates of C / 2 and slower.

[0246] In certain embodiments, the cell operates in a pH range of 3-5, although a much wider pH range is possible. For example, low pH (0.1-3) and higher pH (>3) may have certain advantages for certain embodiments. For example, an acidic electrolyte increases the mobility of ions and the rate of diffusion of aluminum, while a basic electrolyte is believed to improve the rate of transport of ions and the stability of ions in the electrolyte.

[0247] Manganese oxide is synthesized from permanganate and manganese salt precursors and guest ions are introduced and exfoliated from the host material (in this case, manganese oxide is in the δ phase) using basic and peroxide precursors. Guest ions (e.g., sodium, potassium, aluminum and / or other guest ions) are inserted by wet chemical reaction to occupy interstitial sites, resulting in exfoliation of the structure as evidenced by an increase in intersheet spacing. Panels (a) and (b) of FIG. 16 are graphs of x-ray diffraction results showing (a) the presence of sodium chloride residues in as-synthesized manganese oxide prepared by reaction between manganese salt and sodium permanganate, and (b) the x-ray diffraction results showing that after an extensive washing step, the crystal structure of manganese oxide becomes distinct and there is clear evidence of a very high degree of intersheet spacing.

[0248] FIG. 17 is a graph showing the results of thermogravimetric analysis (TGA) in air and vacuum, which confirms the presence of a significant concentration of water crystals within the manganese oxide structure. TGA in vacuum at 120° C. reveals a 7% weight loss. Additionally, TGA also shows that oxygen is lost in an inert atmosphere up to 800° C. However, in air, TGA shows a momentary gain of oxygen at 750° C., followed by a rapid loss of water / oxygen at 800° C. Example 2 Actual transport of aluminum ions between the electrodes

[0249] Several coin cells were assembled, each comprising the following components: (1) a cathode containing 80 wt% manganese oxide, 10 wt% conductive carbon, and 10 wt% sodium carboxymethylcellulose (CMC)-styrene butadiene rubber (SBR) binder (in a 1:1 wt / w ratio); (2) an aluminum anode; (3) a glass microfiber separator; and an electrolyte consisting of aluminum nitrate and lithium nitrate salts dissolved in grade II deionized water. Each coin cell was cycled through 10 to 50 charge-discharge steps to obtain uniform electrochemical equilibrium. Following this, one group of cells was discharged for 8 hours (to insert aluminum ions into the manganese oxide cathode), a second group of cells was discharged for 20 hours, a third group of cells was discharged for 32 hours, and a fourth group of cells was discharged for 40 hours. All cells were disassembled at the end of their discharge time, and the cathodes were washed with deionized water to remove traces of salt from their surfaces. Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) were used to analyze the penetration depth of aluminum ions into the manganese oxide cathode.

[0250] SEM and EDS cross-sectional analysis clearly confirms that aluminum ions have been inserted into the cathode. Moreover, the depth of insertion as a function of discharge rate is visually evident. As shown in panels (a) and (b) of FIG. 18, it can be seen that at shorter discharge times (8 hours, 20 hours, etc.), the aluminum ions are not able to diffuse through the entire thickness cross-section of the cathode, resulting in the accumulation of aluminum ions at the surface. However, as shown in panels (c) and (d) of FIG. 18, when the discharge time is increased to 32 hours and 40 hours, allowing the aluminum ions to diffuse deeper into the cathode, the EDS profile clearly illustrates that there is a gradual insertion and distribution of aluminum ions throughout the bulk of the cathode. Tracking and mapping of the aluminum ions into the cathode as a function of discharge time conclusively proves the actual physical transport of aluminum ions into the cathode. Example 3 Aluminum Alloy Anode

[0251] In a particular embodiment, the anode comprises an aluminum alloy containing one or more non-aluminum elements. An anode of an aluminum-based alloy containing 97 atomic % aluminum and 3 atomic % manganese was tested as the anode material. The electrolyte consisted of 13 wt% lithium sulfate, 1.6 wt% aluminum sulfate, 0.2 wt% magnesium hydroxide, 3.1 wt% N-methylpyrrolidone, and 0.1 wt% magnesium ethoxide in an aqueous solution. The anode was tested against a manganese oxide cathode, and a glass microfiber separator was used to separate the two electrodes. As shown in FIG. 19, the cell exhibited an average capacity of about 50 mAh / g at a charge-discharge rate of C / 20. Example 4 Guest ions / molecules within the manganese oxide structure

[0252] In certain embodiments, the cathode contains one or more guest ions and / or molecules stored between sheets of material (e.g., manganese oxide). In one method, potassium was introduced as a guest ion by an ion exchange process with a chemically leached lithium manganese oxide cathode. First, lithium was chemically leached from the lithium manganese oxide using a 1M HCl solution. This was followed by washing the chemically leached lithium manganese oxide cathode several times. Finally, a solution of 0.1-5M KOH was used as the medium for the ion exchange process. Panel (a) of FIG. 20 shows the SEM and EDS elemental concentrations of the as-synthesized manganese oxide containing potassium guest ions. The EDS results are summarized in Table 1 below.

[0253] Manganese oxide containing potassium guest atoms was cycled as the cathode in a coin cell configuration. The anode was battery grade aluminum metal foil (purity 99.5% or higher) and the electrolyte consisted of aluminum nitrate and lithium nitrate in grade II deionized water. Glass microfiber was used as the separator. The cathode delivered a reversible capacity of about 40 mAh / g at a charge-discharge rate of 4.5 h (voltage profile shown in panel (b) of Figure 20). [Table 1] Example 5 Binder Composition

[0254] In some embodiments, the cathode includes a binder. The binder can physically hold (e.g., adhere) one or more structures (e.g., particles) in contact with the current collector. In one example, a manganese oxide cathode was prepared using a combination of alginate and polyvinylpropylene (PVP) binder. A cathode coating prepared with only PVP binder served as a control experiment. SEM images show the presence of micron-scale pores in the cathode coated with PVP binder, as shown in panel (a) of FIG. 21. On the other hand, when alginate is combined with PVP, the cathode structure appears denser, as shown in panel (b) of FIG. 21. PVP and alginate were found to work together to improve the dispersibility of conductive carbon and the adhesive and cohesive forces between active particles and conductive carbon, respectively.

[0255] Cells assembled using manganese oxide prepared with PVP and PVP-alginate binders were tested against an aluminum anode. Additionally, a cathode incorporating a polyacrylic acid-based (PAA-based) binder with similar dense coating properties was also tested as a baseline (panel (c) of FIG. 21). As shown in panel (d) of FIG. 21, the cathode incorporating the PAA binder was cycled at a stable voltage of 1.2 V, while the cathode using the PVP-alginate binder showed a discharge voltage profile with a step slope with an average operating potential of about 0.9 V to 1.1 V, as shown in panel (e) of FIG. 21.

[0256] As an extension of this experiment, the cathode coated with PVP-alginate binder was immersed in a bath containing 3M manganese nitrate. In the presence of multivalent ions, such as manganese ions, alginate was found to show improved mechanical strength. Without wishing to be bound by any particular theory, it is likely that the improved mechanical strength can be attributed to the ability of alginate to form ionic associations within its structure and within the bond network between the chains. Other multivalent ions that can be used include, but are not limited to, magnesium and aluminum ions. Similar observations were also realized with some monovalent ions, including lithium, sodium and potassium ions. Ions that can be used for ionic pretreatment of the cathode, including binders such as PVP-alginate, include, but are not limited to, sodium, potassium, magnesium, manganese, aluminum, calcium, barium, strontium and zinc ions.

[0257] Additionally, other polymer binders have also been found to induce mechanical enhancement and / or electrochemical stability in conjunction with monovalent and / or multivalent ions. Some examples include, but are not limited to, polyvinylidene difluoride (PVDF), PTFE, polyaniline, epoxy, carboxymethyl cellulose, rubber, styrene butadiene rubber, polyacrylic acid, polyvinyl alcohol, and polyvinyl propylene. Solvents in which such binders are dispersed can include, but are not limited to, water, n-methylpyrrolidone, ketones, glycols, dimethyl sulfoxide (DMSO), and esters. Co-solvents may also be used. Usable co-solvents include, but are not limited to, water, n-methylpyrrolidone, ketones, glycols, DMSO, and esters. Example 6 Patterned anode structure:

[0258] The anode may include an oxide layer (e.g., a transitional aluminum oxide layer). In one example, a patterned aluminum anode (SEM images in panels (a) and (b) of FIG. 22) is used with a standard cathode containing manganese oxide active material, conductive carbon, and a CMC-SBR binder. A control experiment is used in which the anode consists of a non-patterned aluminum anode (SEM image in panel (c) of FIG. 22) and the cathode consists of manganese oxide active material, conductive carbon, and a CMC-SBR binder.

[0259] The cell is charged to 10 μA / cm 2The patterned aluminum anodes were cycled at a constant current density of 1000 mA / s. The voltage profiles of the patterned aluminum anodes show steady-state charge-discharge behavior for cycles 69-77 (panel (d) of FIG. 22) and cycles 30-34 (panel (e) of FIG. 22). On the other hand, the voltage profile of the unpatterned aluminum anode shows noticeable voltage hysteresis and noise between cycles 91-99 (panel (f) of FIG. 22). These profiles are constant over the entire cycle range, and only a specific range is illustrated for simplicity.

[0260] It has been found that patterned aluminum anodes facilitate efficient and uniform diffusion of ions in and out of the structure. Without wishing to be bound by any particular theory, it is generally believed that the large surface area realized by patterning and other similar techniques results in a thicker solid electrolyte interfacial film due in part to the presence of the larger surface area. This in turn results in an increase in impedance and internal resistance, resulting in an overall decrease in ion diffusion rate and capacity. However, unexpectedly, it has instead been observed that the electrochemical environment and precise cell composition promotes reaction rates in the proposed battery technology. Example 7 Anode secondary composition

[0261] The anode may include one or more oxide thin films and / or coatings (e.g., with nanoparticles and / or microparticles). In one example, an aluminum anode was sputter coated with a 60 nm film of zirconium oxide. The aluminum-zirconium oxide composite anode was tested in a three-electrode system against a manganese oxide (in this case, MnO2) counter electrode and an Ag / AgCl reference electrode. The electrolyte consisted of aluminum and lithium salts dissolved in grade II deionized water.

[0262] Cyclic voltammetry shows that there is a clear redox peak at ±1 V (vs. Ag / AgCl), corresponding to the extraction of aluminum from the anode and insertion into the cathode, as shown in FIG. Example 8 Anode secondary composition

[0263] In another test, an aluminum anode was coated with zirconium oxide using an aerosol spray coating method. The anode-zirconium oxide composite was measured to be approximately 70 μm thick. The anode-zirconium oxide composite was then calendered to reduce the cross-sectional thickness to approximately 40 μm. The cell was assembled against a manganese oxide cathode and cycled at different current densities. The nominal voltage was measured to be 20 μA / cm 2 at 1.18 V, 25 μA / cm 2 At 1.15 V and 30 μA / cm 2 24 shows a summary of the electrochemical performance of the aluminum anode coated with a zirconium oxide film, including the cyclic voltammetry profile (top left), the charge-discharge profile (top right), the voltage profile vs. current density (bottom left) and the voltage profile vs. capacity (bottom right). Example 9 Anode secondary composition

[0264] In another test, an aluminum anode was coated with a 50 nm film of Parylene-N. The coating was done using a chemical vapor deposition technique to coat a 70-100 nm film of Parylene-N, followed by a thermal annealing process to reduce the thickness to about 50 nm. The Parylene-coated aluminum anode was tested against a manganese oxide cathode in a single coin cell configuration.

[0265] The parylene-coated aluminum anode was run at a charge-discharge rate of C / 70 up to 190 mAh / g. At the lower rates of C / 3, C / 6, and C / 15, the capacity distribution ranged between 20 mAh / g and 40 mAh / g, as shown in Figure 25. Example 10 Patterned Substrate for Cathode

[0266] In some embodiments, the cathode is coated on a high surface area porous carbon. In one example, a manganese oxide cathode (80 wt%) was combined with conductive carbon (10 wt%) and CMC-SBR binder (10 wt%) to form an aqueous slurry and dip-coated onto pyrolytic graphite foam. Such a cathode was then assembled to an aluminum anode separated by a glass microfiber membrane. As shown in panels (a) and (b) of FIG. 26, the cell was cycled at C / 2.5 and C / 0.5 (discharge-discharge for 2.5 hours and 30 minutes, respectively) to run at 47 mAh / g and 21.5 mAh / g, respectively, while still maintaining an average working potential of about 1 V. Example 11 Cathode performance as a function of crystal structure and phase

[0267] To evaluate the effect of manganese oxide cathode structure, several phases of manganese oxide (e.g., MnO2) were tested, including but not limited to beta (β), delta (δ) and gamma (γ), as well as combinations thereof. Cathodes with specific phase compositions were mixed in an aqueous slurry, typically containing 10 wt% binder (CMC-SBR) and 10 wt% conductive carbon. The slurry was then mixed into a stable, uniform dispersion and coated onto a current collector substrate, such as aluminum, graphite foil, copper, nickel, or stainless steel. The cathodes were tested against an aluminum metal foil anode, with the two electrodes separated by a glass microfiber membrane. 10 μA / cm 2 ~30μA / cm 2 The cells were discharged at current densities ranging between 0.1 and 1.0 V.

[0268] Manganese oxide cathodes consisting of a majority (e.g., at least 70%) in the beta phase delivered reversible capacities ranging between 160-180 μAh at a charge-discharge rate of C / 6, as shown in panel (a) of FIG. 27. Panel (b) of FIG. 27 shows that manganese oxide consisting of a majority (e.g., at least 70%) in the delta (δ) phase delivered about 180 μAh of reversible capacity at a charge-discharge rate of C / 8. Panel (c) of FIG. 27 shows that manganese oxide consisting of a majority (e.g., at least 70%) in the gamma (γ) phase delivered about 300 μAh of reversible capacity at a charge-discharge rate of about C / 10. Example features from other approaches

[0269] There are certain unique features of various embodiments of the aqueous aluminum ion battery described herein - e.g., manganese oxide cathode. As described herein, the structural geometry of the cathode includes, for example, its porosity, wettability, particle shape (e.g., sphere, sheet-like, etc.), particle size, among others. These features contribute to the overall performance of the battery. For example, wettability is important because a poorly wettable electrode can result in dielectric effects, thereby significantly altering the reaction mechanism. In certain embodiments, lithiophorite and / or birnessite structures are used in the cathode.

[0270] In various embodiments, the manganese oxide structure is layered and has Na + , K + , Al +3However, these guest ions (or in some cases guest molecules) are only inserted into the manganese oxide to facilitate expansion of the manganese oxide structure (e.g., inter-sheet spacing greater than 10 Å). In certain preferred embodiments, at the end of the exfoliation, a significant majority of the guest ions / molecules are removed (e.g., by osmotic action), such that there are no visible traces of the guest ions after removal. In certain embodiments, the manganese oxide structure does not incorporate any form of copper or bismuth ions.

[0271] In certain embodiments where some guest ions / molecules are retained in the manganese oxide structure, these guest ions / molecules do not actively participate in the electrochemical reaction. Instead, these guest ions / molecules help open the manganese oxide structure to increase the aluminum ion storage capacity (e.g., where a larger inter-sheet spacing correspondingly increases the charge storage capacity). The lack of guest ion participation is evident from the experimentally observed voltage window that precludes any significant reaction of sodium, potassium and other guest ions. On the other hand, the operating window clearly falls within the known range for aluminum ion participation (about 1.6 V).

[0272] In certain embodiments, the diffusion coefficient of the manganese oxide structure is very high, e.g., at least 1×10 -12 cm 2 / sec, e.g. at least 1x10 -10 cm 2 / sec, e.g. at least 1x10 -9 cm 2 In one particular embodiment, the diffusion coefficient of the manganese oxide structure is 1.7x10 -10 cm 2 / sec~7x10 -9 cm 2 / seconds.

[0273] K + and Na +Experiments performed on manganese oxide cathodes containing various guest ions that were not removed from the host manganese oxide structure, including , show only a single redox peak during cyclic voltammetry (Figure 28). Furthermore, energy dispersive x-ray analysis (EDS) confirms that the guest element exists in a fully "aluminized" (aluminum intercalated into the manganese oxide) state (Figures 29A-29B, Table 2). The pristine sodium-manganese oxide shows an elemental sodium concentration of about 7.1 atomic %, further consistent with the hypothesis that the guest ion is not removed but rather accommodates the aluminum ion in certain embodiments of the sodium-manganese oxide cathodes described herein. [Table 2]

[0274] To further demonstrate that aluminum ions are not displaced by guest ions or molecules in certain embodiments of the cathodes described herein, tests were performed with partially exfoliated pyrolytic graphite cathodes. As can be seen in Figures 30A-30B, aluminum ions can successfully intercalate and interact with carbon, but the capacity was significantly lower than that obtained with sodium-manganese oxide and potassium-manganese oxide (the lower capacity may be due to the smaller inter-sheet spacing of pyrolytic graphite). If the aluminum intercalation rate were dominated by the exchange of guest ions, pyrolytic graphite cathodes would not show such activity. It is also believed that the electrolyte, pH, anode-cathode combination (and therefore the operating voltage window), and the specific type of anode and cathode may contribute to the establishment of a unique interaction mechanism that relies on the aluminum charge induced by stable hydroxides, oxide-hydroxides (etc.) being transported between the two electrodes. Aluminum ions (Al(OH)4 surrounded by hydroxides / oxide-hydroxides) can be easily intercalated by the hydroxides / oxide-hydroxides. -1Once the manganese oxide sheets (e.g., ZnO, NaOH, KOH, NaOOH, etc.) reach the cathode, the sodium or potassium guest ions interact with the oxide / hydroxide (e.g., forming NaOH, KOH, NaOOH, etc.), while the aluminum ions are neutralized and stored within the manganese oxide sheets, potentially avoiding the need to release guest ions into the electrolyte.

[0275] In various embodiments, excess aluminum salt in the electrolyte is avoided (e.g., 375 g or less per kg of water, e.g., 200 g or less per kg of water, 100 g or less per kg of water, 50 g or less per kg of water, or about 37.5 g or less per kg of water), and thus aluminum salt from the electrolyte does not actively participate in the electrochemical reaction. Rather, it relies on aluminum ions from the aluminum anode and not on the electrolyte salt.

[0276] In various embodiments, for example, when aluminum is the active electrode material (e.g., Al +3 In certain embodiments, an aluminum anode is utilized, for example, a source of an electrolyte (source of electrolyte), a lithium anode. In certain embodiments, the aluminum anode is anodized. In certain embodiments, a barrier layer is present on the aluminum anode, including, for example, an oxide layer and / or a passivation layer. In certain embodiments, a passivation layer of graphene (or carbon in general) is used. This barrier layer may affect performance, such as diffusion of aluminum ions and / or stabilization of aluminum, in an electrochemical environment. In certain embodiments, the aluminum anode is used in a battery having an acid electrolyte. In certain embodiments, the anode comprises a highly polished aluminum foil, for example, where the absence of surface defects and irregularities promotes a uniform reaction and avoids localized charge concentrations.

[0277] In certain embodiments, the electrolyte does not include halide ions. In this way, the corrosive nature of halogens can be avoided and hydroxides can be used instead of halide ions as charge carriers.

[0278] In certain embodiments, the cathode has a bimodal distribution of particles (e.g., manganese oxide particles). For example, the cathode can contain a first portion of particles having a particle size of about 20 micrometers (±20%) and a second portion of particles having a particle size of about 0.5 micrometers (±20%), the first and second portions constituting at least 80% of the particles of the cathode (e.g., as shown in FIG. 31).

[0279] Certain embodiments of the present disclosure have been described above. However, it should be clearly noted that the present disclosure is not limited to such embodiments, and rather, the intention is that additions and modifications to those explicitly described in the present disclosure are still included within the scope of the present disclosure. Furthermore, it should be understood that the features of the various embodiments described in the present disclosure are not mutually exclusive, and that various combinations and variations may exist, even if not expressed, without departing from the spirit and scope of the present disclosure. Having described certain implementations of the aqueous aluminum ion battery, battery-capacitor hybrid, cathode composition, anode composition, binder composition, and methods of making and using the same, it will be apparent to those skilled in the art that other implementations incorporating the concepts of the present disclosure may be used. Thus, the present disclosure should not be limited to any particular implementation, but rather should be limited only by the spirit and scope of the following claims.

Claims

1. A cathode for an ion battery, the cathode comprising: A current collector, and One or more structures each containing manganese oxide Equipped with the one or more structures are disposed on and in electrical contact with the current collector; one or more columnar forming agents are stored between the manganese oxide sheets; Cathode.

2. The cathode of claim 1, wherein the sheets comprise at least 20% by weight manganese oxide with an inter-sheet separation distance of 1 angstrom or greater.

3. The cathode of claim 1, wherein the one or more structures include a spinel structure, a tunnel structure, a sandwich structure, an encapsulation structure, a capture structure, or a combination thereof.

4. The cathode of claim 1, wherein the one or more structures include a turbostratic structure.

5. The cathode of claim 1, wherein the one or more structures include one or a combination of lithiophorite structures, phyllomanganate structures, and tectomanganate structures, one or more of which may be in a pristine state or disordered and may contain vacancies.

6. The one or more structures comprising particles, wherein at least 80% of the particles of the cathode have a surface area within the following range: (i) 50 nm or more, (ii) 100nm to 250nm, (iii) 500 nm to 5 micrometers; (iv) 1 micrometer to 10 micrometers; (v) 5 micrometers to 30 micrometers 13. The cathode of claim 1 having a dimension within one of the following ranges:

7. The cathode of claim 1, comprising one or more non-aluminum guest ions stored between the sheets of manganese oxide.

8. The cathode of claim 1, comprising one or more non-aluminum guest ions disposed in sites and / or vacancies in the manganese oxide crystal lattice.

9. The cathode of claim 7, wherein the guest ions comprise one or more members selected from the group consisting of protons, sodium, lithium, potassium, zinc, bismuth, copper, lead, cobalt, nickel, calcium, potassium, magnesium, hydrogen, hydronium, hydroxide, oxide-hydroxide, sulfate, sulfide, nitride, nitrate, phosphide, phosphate, acetate, polyoxometalates (POMs) and pillar-forming agents.

10. The cathode of claim 1, comprising one or more aluminum guest ions stored between said sheets of manganese oxide.

11. The cathode of claim 1, comprising one or more non-aluminum guest molecules stored between the sheets of manganese oxide.

12. The cathode of claim 1, comprising one or more non-aluminum guest ions disposed in sites and / or vacancies in the manganese oxide crystal lattice.

13. The cathode of claim 11, wherein the guest molecules comprise one or more members selected from the group consisting of oxides, hydroxides, oxide-hydroxides, sulfides, sulfates, nitrides, nitrates, chlorides, chlorides, phosphates and phosphides.

14. The cathode of claim 11, wherein the guest molecules comprise one or more phosphates.

15. The cathode of claim 14, wherein the one or more phosphates are members selected from the group consisting of sodium phosphates, lithium phosphates, potassium phosphates, calcium phosphates, magnesium phosphates and manganese phosphates.

16. The cathode of claim 1, comprising aluminum phosphate stored between the sheets of manganese oxide or disposed in sites and / or pores of the manganese oxide crystal lattice.

17. The cathode of claim 1, wherein the one or more pillar-forming agents comprise one or more members selected from the group consisting of polyoxometalates (POMs), amphiphilic molecules, polar organic molecules, and non-polar organic molecules.

18. The cathode of claim 1, wherein the one or more structures each comprise an aluminum-receptive polymer.

19. The cathode of claim 18, wherein the aluminum-receptive polymer comprises a member selected from the group consisting of alizarins, alginates, amidinates, quinones, quinolones, hydroxyquinones, crown ethers and hydroxyquinolines.

20. The cathode of claim 18, wherein the aluminum-receptive polymer is present as a complex with one or more members selected from the group consisting of lithium, sodium, lead, chromium, copper, bismuth, cobalt, zinc, potassium, calcium, magnesium, manganese, iron, cobalt, titanium, tin, vanadium and tungsten.

21. The cathode of claim 1, wherein the one or more structures include particles.

22. The cathode of claim 1, wherein the one or more structures include a film.

23. The cathode of claim 1, wherein the current collector is porous.

24. The cathode of claim 23, wherein the one or more structures are disposed within or on the pores of the current collector.

25. The cathode of claim 1, wherein the one or more structures are coated onto one or more porous carbon structures.

26. The cathode of claim 25, wherein the one or more porous carbon structures comprise one or more members selected from the group consisting of carbon fibers, nanofibers, carbon nanotubes (CNTs), fullerenes, graphene, partially reduced graphene oxide, aerogels, xerogels, and interpenetrating multiphase materials.

27. The cathode of claim 1, further comprising a binder in contact with the current collector to physically maintain the one or more structures.

28. The cathode of claim 27, wherein the binder is selected from the group consisting of carboxymethyl cellulose, styrene butadiene rubber, polyvinyl alcohol, alginate, polypropylene, polytetrafluoroethylene, polyvinylidene difluoride, polyaniline, epoxy, rubber, polyacrylic acid and polyvinyl propylene.

29. The cathode of claim 27, wherein the binder is selected from the group consisting of alginate, PVDF, PTFE, polyaniline, epoxy, carboxymethyl cellulose, rubber, styrene butadiene rubber, polyacrylic acid, polyvinyl alcohol and polyvinyl propylene.

30. The cathode of claim 27, wherein the binder is pretreated with one or more species of multivalent ions.

31. The cathode of claim 30, wherein the one or more species of multivalent ions include one or more ions of manganese, magnesium, calcium, zinc, barium and aluminum.

32. The cathode of claim 27, wherein the binder is pretreated with one or more species of monovalent ions.

33. The cathode of claim 32, wherein the one or more species of monovalent ions include one or more ions of lithium, sodium, and potassium.

34. The cathode of claim 27, wherein the binder comprises ions of one or more members selected from the group consisting of sodium, potassium, magnesium, manganese, aluminum, calcium, barium, strontium and zinc.

35. The cathode of claim 27, wherein the binder is deposited from a solution comprising one or more of water, n-methylpyrrolidone, ketones, glycols, dimethylsulfoxide (DMSO) and esters, and optionally a co-solvent selected from the group consisting of water, n-methylpyrrolidone, ketones, glycols, DMSO and esters.

36. The cathode of claim 1, wherein the cathode is binder-free.

37. The cathode of claim 1, further comprising a conductive additive in electrical contact with the current collector and the one or more structures.

38. The cathode of claim 1, wherein the current collector comprises one or more members selected from the group consisting of stainless steel, copper, carbon, silver, gold, platinum, tin, vanadium, zinc, tin oxide, indium, indium tin oxide (ITO), aluminum, nickel, tungsten, chromium and titanium.

39. The cathode of claim 1, wherein the current collector comprises a coating of an adhesion promoter, a conductivity promoter, or both an adhesion promoter and a conductivity promoter.

40. The cathode of claim 1, wherein the current collector comprises one or more coatings of carbon, metal, metal oxide or polymer, the coating acting as one or more of an adhesion promoter, an electronic conductivity promoter and an ionic conductivity inhibitor.

41. A cathode for an ion battery, comprising: A current collector; one or more structures, each comprising one or more members selected from the group consisting of manganese oxide, aluminosilicate, and aluminum-receptive polymer, the one or more structures comprising particles; a plurality of conductive posts extending from the current collector; Equipped with the one or more structures are disposed on and in electrical contact with the current collector, and the particles are disposed on the plurality of conductive posts. Cathode.

42. A cathode for an ion battery, comprising: A current collector; one or more structures, each comprising one or more members selected from the group consisting of manganese oxide, aluminosilicate, and aluminum-receptive polymer, the one or more structures comprising a film; a plurality of conductive posts extending from the current collector; Equipped with the one or more structures are disposed on and in electrical contact with the current collector, and the film is disposed on the plurality of conductive posts. Cathode.

Citation Information

Patent Citations

  • Aluminum battery

    JP2002298862A

  • Method for manufacturing laminated manganese oxide nanocomplex

    JP2003201121A

  • Manganic acid nanosheet and production method therefor

    JP2003335522A

  • Non-aqueous electrolyte for secondary battery and non-aqueous electrolyte secondary battery

    JP2004296103A

  • Positive electrode and lithium secondary battery

    JP2009076278A